Collaborative science narrows knowledge gaps in marine biological invasions to advance a national framework - Romeu S. Ribeiro; Cristina Espírito Santo; Susana Celestino; Marta Mamede; João J. Castro; Teresa Cruz; Teresa Silva; David Jacinto; Cátia Bartilotti; Jorge Lobo-Arteaga; Miriam Tuaty-Guerra; João Canning-Clode; et al. (Marine Pollution Bulletin, 2026)

Recreational ketamine exposure disrupts redox and inflammatory homeostasis in salivary glands and plasma leading to salivary dysfunction - Emanuelly Camilly Soares Lima-da-Silva; Cristian Kallahan Silva Chagas; Wallacy Watson Pereira Melo; Ana Paula de Andrade Silva; Sabrina Carvalho Cartágenes; Nair Correia de Freitas Castro; Fernando Bezerra; Rommel Rodrigues Burbano; Antonio Hernandes Chaves-Neto; Renata Duarte Souza-Rodrigues; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Food and Chemical Toxicology, 2026)

Relationships between surface urban heat island and vegetation across a regional climatic gradient: the case of southeastern Brazil - Ana Kellen Nogueira Campelo; Humberto Ribeiro da Rocha; Denise Helena Silva Duarte; Rodrigo Lustosa (Sustainable Cities and Society, 2026)

Valorization of grape stalks into activated hydrochar for meropenem adsorption: From batch to fixed-bed column - José L.S. Duarte; Ana Hayat; Mario de la Fuente; Carmen M. Domínguez; Aurora Santos; Salvador Cotillas (Journal of Water Process Engineering, 2026)

Electrochemical treatment of dacarbazine and paracetamol in synthetic multi-pharmaceutical hospital wastewater: By-product control and operational window - Ana Hayat; Giovanni Scaggiante; Jose L.S. Duarte; Daniela Zingaretti; Carmen M. Domínguez; Renato Baciocchi; Aurora Santos; Salvador Cotillas (Journal of Environmental Chemical Engineering, 2026)

Degradation pathways and in silico ecotoxicity assessment of meropenem by-products generated by electrochemical oxidation - José L.S. Duarte; Ana Hayat; Carmen M. Domínguez; Aurora Santos; Salvador Cotillas (Journal of Environmental Chemical Engineering, 2026)

A comparative evaluation of new prebiotic candidates. Part 2: In vitro assays using faecal inoculum from IBD patients - Sergio Martínez-Gómez; Joana Sousa; Ana Cordeiro; Sónia G. Barbosa; Ricardo Franco-Duarte; Ana C. Pinheiro; Ligia R. Rodrigues; Sara C. Silvério; Remedios Yáñez; José Luis Alonso (Food Research International, 2026)

Impact of parabens, individually and in mixture, on human neutrophil oxidative burst under physiological and hyperglycemic conditions - Ana Ramalho; Diana Dias da Silva; José Alberto Duarte; Félix Carvalho; Eduarda Fernandes; Marisa Freitas (Food and Chemical Toxicology, 2026)

Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Nematodal otitis by Stenurus globicephalae in a melon-headed whale (Peponocephala electra) stranded in Northeastern Brazil: case report and literature update - Hodias S. Oliveira Filho; José Lucas Costa Duarte; Raquel Mota Freitas Pereira; Pedro Lucas Jordão de Luna Araújo; Naftali Camily Fernandes de Lima; Raquel de Oliveira Simões; Bruno de Oliviera Telles Ferreira; Carlos Iberê Alves Freitas; Augusto Carlos da Bôaviagem Freire; Ana Bernadete Lima Fragoso; Flávio José de Lima Silva; Josué Díaz-Delgado; et al. (Veterinary Research Communications, 2026)
Cetaceans are highly adapted marine mammals whose survival depends on precise auditory and echolocation systems. Therefore, disease processes affecting these systems, including parasitic infections pose significant morbidity and may result in stranding and death. Here, we describe the pathologic and parasitological findings in an adult, male melon-headed whale ( Peponocephala electra ) stranded dead on the Brazilian coast. The main gross pathologic findings consisted of bilateral otitis media associated with numerous nematodes in the tympanic bullae that occluded the tympanic lumen and resulted in compression of the tympanic membrane. Other relevant gross findings were abdominal effusion, visceral congestion, pulmonary petechiae, and lack of ingesta. Histopathologic examination of the tympanic membrane and middle ear soft tissue revealed chronic otitis and myringitis with epithelial hyperplasia and multifocal ulceration with intralesional nematodes. These nematodes were morphologically identified as Stenurus globicephalae through direct microscopy and electron microscopy analyses. In this case, severe parasitism of the tympanic apparatus was considered the primary pathologic condition. We surmise that the severity of the lesions noted in the auditory system could have resulted in disorientation and stranding, and, together with the physiological stress response associated with live stranding, ultimately led to death in this individual. This report underscores the role of parasitic otitis caused by S. globicephalae as a differential etiological diagnosis for stranding and death in cetaceans along the Brazilian coast and provides an updated overview of the literature on otic parasitism in cetaceans.

Effect of contrasting climatic conditions in Brazil on heartwood and sapwood production and chemistry in young Eucalyptus clones - Sâmara Magdalene Vieira Nunes; Stéffany Lima Araujo; Gustavo Jaske da Conceição; Thayanne Caroline Castor Neto; Gabriela Goldner Gimenez; Yasmin Aparecida de Oliveira Figueiredo; Renata Guilherme Candido da Silva; Aguinaldo José de Sousa; Jorge Gominho; Ana Lourenço; Duarte Miranda Neiva; Maria Naruna Félix de Almeida; et al. (European Journal of Forest Research, 2026)

Intestinal Histomorphometric Alterations During Experimental Strongyloidiasis in Mice Treated with Rosmarinus officinalis Essential Oil - Lorena Q. A. Tanaka; Kamilla A. M. Dutra; Nicolas M. H. da Silva; Izadora M. Assis; Gabriela A. C. Duarte; João B. A. Souza; Eleuza R. Machado; Ana Paula S. Perez; Rosângela M. Rodrigues (Acta Parasitologica, 2026)
Purpose Strongyloidiasis is an intestinal helminthiasis that can induce structural alterations in the intestinal mucosa during infection. The present study evaluated histomorphometric alterations of the small intestine in mice experimentally infected with Strongyloides venezuelensis and treated with Rosmarinus officinalis essential oil. Methods Infected animals were treated orally with R. officinalis essential oil (200 or 400 mg/kg), ivermectin or control treatments. Histomorphometric parameters of the small intestine were evaluated, including villus height, epithelial height, crypt depth, muscular layer thickness, brush border height and goblet cell counts. Parasitological parameters were also assessed to characterize the infection model. Results Histomorphometric analysis demonstrated that treatment with essential oil at 200 mg/kg was associated with recovery of villus and epithelial height, increased brush border and goblet cell numbers, as well as attenuation of muscular layer hypertrophy, suggesting preservation of mucosal structure during infection. The 400 mg/kg dose, although associated with greater reduction in parasite burden, was accompanied by increased crypt depth, indicating more intense proliferative remodeling of the intestinal mucosa. Ivermectin promoted the greatest reduction in parasite burden with marked elimination of eggs and females. Conclusion These findings indicate that R. officinalis essential oil modulates intestinal mucosal architecture during experimental strongyloidiasis and highlight its potential influence on host intestinal responses during infection.

Spatial gradients of response to the indirect effects of forest fires on vegetation in the Pantanal - Antonio Henrique Cordeiro Ramalho; Ronie Silva Juvanhol; Vinicius Duarte Nader Mardeni; Evandro Ferreira da Silva; Nilton Cesar Fiedler; William Masioli; Leonardo Duarte Biazatti; Ana Julia Santos Brito (International Journal of Remote Sensing, 2026)

Mitigation of pesticide residues in rice: influence of cooking methods on long-grain, brown, and Basmati varieties - Filipa Carreiró; Sílvia Cruz Barros; Carla Brites; Patrícia Cazón; Duarte Torres; Fernando Ramos; Ana Sanches Silva (Food Additives & Contaminants: Part A, 2026)

Venom characterization and structural insights into phospholipase D isoforms from the spider Loxosceles aff. variegata - Ana Luiza Silva-Araújo; Rafaela Silva-Magalhães; Pamella Peres-Damásio; Elaine Henriques Teixeira Pereira; Ramon de Oliveira Souza; Luana Silveira da Rocha Nowicki Varela; Luiz Marcelo Ribeiro Tomé; Felipe Campos de Melo Iani; Adriano Lima Silveira; Márcia Helena Borges; Raíssa Medina-Santos; Carlos Chavez-Olórtegui; et al. (Toxicon, 2026)

Climate extremes, WASH deficits, and infectious diseases in the Brazilian Amazon: Insights from explainable machine learning (2010−2022) - Ana Karoline Duarte dos Santos Sá; Marco Valerio Jansen Cutrim; Rafael Diego Barbosa Soares; Quedyane Silva da Cruz; Andrea Christina Gomes de Azevedo Cutrim; Yago Bruno Silveira Nunes; Paulo Henrique Rocha Aride; Jeniffer Hachiley de Sousa Torquato; Antonio Ronnilson Dias Carneiro Sá (Science of The Total Environment, 2026)

Functional redundancy and structural flexibility as contrasting plankton strategies under macrotidal pulses - Quedyane Silva da Cruz; Marco Valério Jansen Cutrim; Pedro Augusto Mendes de Castro Melo; Ana Karoline Duarte dos Santos Sá; Yago Bruno Silveira Nunes; Bruna Oliveira Ferreira; Francisco José da Silva Dias; Vinicius Henrique Maciel dos Santos; Taiza Pimentel Santos (Marine Environmental Research, 2026)

A comparative evaluation of new prebiotic candidates. Part 1: Chemical and structural characterization, digestibility, and in vitro fermentation using faecal inoculum from healthy donors - Sergio Martínez-Gómez; Joana Sousa; Ana Cordeiro; Sónia G. Barbosa; Ricardo Franco-Duarte; Ana C. Pinheiro; Ligia R. Rodrigues; Sara C. Silvério; Remedios Yáñez; José Luis Alonso (Food Research International, 2026)

Potato protein-based meat analogues fortified with upcycled fruit flours: Functional, textural, and antioxidant insights - Ana Rita Pereira; Vasco Trincão da Silva; Duarte Torres; Ana A. Vilas-Boas; Débora A. Campos; Inês Cruz; Adriana Ferreira; Nuno Mateus; Victor de Freitas; Ana Fernandes (Food Chemistry, 2026)

Bioaccumulation and elimination kinetics of metals and polycyclic aromatic hydrocarbons in Hermetia illucens larvae: Implications for risk mitigation of selected contaminants in insect farming - Amid Mostafaie; Patricia V. Silva; Marija Prodana; Ana Rita R. Silva; José N. Pinto; Regina M.B.O. Duarte; Paula Alvito; Inês Coelho; Andreia Rego; Iva G. Lopes; Bryan W. Brooks; Susana Loureiro; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Comprehensive Genomic Characterization and Probiotic Properties Evaluation of Limosilactobacillus fermentum JAC 231 Isolated from Vaginal Microbiota - Carmem Duarte Lima Campos; Amanda Graziella Goncalves Mendes; José Lima Pereira-Filho; Viviane da Silva Sousa Almeida; Ana Beatriz Santos Sousa; Israel Viegas Moreira; João Lucas do Carmo Lima; Aleania Polassa Almeida Pereira; Allysson Kayron Carvalho Silva; Laís Araújo Souza Wolff; Kátia Regina Assunção Borges; Cristianne Roberta Rhoden; et al. (Probiotics and Antimicrobial Proteins, 2026)

Filling gaps in the biology of the critically endangered killifish Leptopanchax itanhaensis (Aplocheiloidei: Rivulidae) - João Henrique Alliprandini Costa; Amanda Selinger; Thomas Alves Vidal; Ana Gabriela Castilho; Ursulla Pereira Souza; Rafael Mendonça Duarte (Environmental Biology of Fishes, 2026)
Leptopanchax itanhaensis is a critically endangered annual killifish endemic to temporary aquatic habitats of the Atlantic Forest in southeastern Brazil, yet its biology and ecology remain poorly known. Here, we provide preliminary natural history data based on a 14-month monitoring effort in the Preto River sub-basin, the only region where the species is currently known to occur. We monitored one temporary pool and two roadside ditches, recording a total of 32 individuals, with most captures occurring during the rainy season. The species was repeatedly detected in both natural and artificial temporary habitats, which differed in their physicochemical conditions. Critical thermal maximum values ranged from 33.3 to 37.7 °C, and the thermal safety margin was estimated at 7.41 °C. Diet analysis indicated frequent consumption of Chironomidae larvae and Ostracoda, although most food items were classified as occasional. Eight mature females were analyzed for reproductive traits, revealing low batch fecundity and a bimodal distribution of oocyte diameters, consistent with batch spawning. Female body size was positively associated with oocyte diameter, but not with fecundity. Together, these findings provide the first integrated natural history account for L. itanhaensis and help fill key knowledge gaps for the conservation of this highly threatened species.

A global synthesis of ecosystem services records and their associations with marine and coastal habitats - Joana Martelo; Sandra A. Ferreira; Ronaldo Sousa; Sílvia B. Carvalho; Manuel Hidalgo; Henrique Cabral; Marina Dolbeth; Martin Lindegren; Ana Veríssimo; Anne E. Magurran; Bernardo Duarte; Sofia Henriques; et al. (Ecosystem Services, 2026)

Ecosystem Services of Freshwater Swamp Forests: Mechanisms of Hydrological Regulation and Impacts of Global Environmental Change - Ana Paula Roschildt; Daniel Burd Villanova; Caroline Igansi Duarte; Saimon Branco Bueno; Marcos Antonio Bacarin; Tanise Luisa Sausen; Junior Borella (Wetlands, 2026)
Freshwater swamp forests (FSFs) are flood-prone ecosystems on nutrient-rich alluvial soils that provide important ecosystem services, yet remain underrepresented in wetland research and management. This integrative review synthesizes current knowledge on FSFs with emphasis on three interconnected themes: (i) ecological definition, classification, and hydrological dynamics; (ii) the role of microtopography and evapotranspiration in regulating water storage and fluxes; and (iii) potential responses of these coupled processes to climate change. Although the “sponge” metaphor is seldom explicitly applied to FSFs, the reviewed literature consistently shows that water retention, delayed release, and vegetation-mediated fluxes are functionally linked, albeit often studied separately. Fine-scale surface heterogeneity, particularly hummocks and depressions, emerges as a key mechanism promoting water redistribution, groundwater recharge, and the persistence of localized refugia and microhabitats. At the same time, climate change-driven shifts in precipitation, drought frequency, heat stress, and disturbance regimes may weaken these regulatory functions and reduce ecosystem resilience. We therefore propose the “sponge–pump framework” as a conceptual model linking hydrological storage (“sponge”) and vegetation-driven water fluxes (“pump”) to explain how FSFs regulate water movement, support biodiversity, and contribute to ecosystem services across spatial and temporal scales. The framework also highlights the need for standardized quantification, broader geographic coverage, and greater integration of microtopographic processes in wetland conservation, restoration, and climate adaptation strategies.

HTLV-1 infection in patients with neurological manifestations in Northeast Brazil - Artur Fernando Soares da Silva; Yan Charles da Silva Bastos; Juliana Tiemi Oikawa; Ana Eliza Vargas Eskinazi Sant’Anna; Gabriel Galindo Cunha; Clarice Neuenschwander Lins de Morais; Elisa de Almeida Neves Azevedo; Maria Rosângela Cunha Duarte Coêlho (Journal of NeuroVirology, 2026)
Human T-lymphotropic virus type 1 (HTLV-1) infection is associated with a broad spectrum of neurological manifestations, including conditions that may precede the development of HTLV-1–associated myelopathy/tropical spastic paraparesis (HAM/TSP). This analytical, descriptive cross-sectional study aimed to estimate the prevalence of HTLV-1 infection and describe associated sociodemographic, socioeconomic, behavioral, and clinical characteristics among patients with neurological disorders followed at a tertiary public hospital in Northeast Brazil between 2024 and 2025. A total of 300 patients underwent serological screening using an enzyme-linked immunosorbent assay (ELISA) with a commercial kit (DiaSorin Murex HTLV-1 + 2). Samples with positive or indeterminate results underwent DNA extraction and molecular confirmation by polymerase chain reaction (PCR) to differentiate viral types. Three patients tested positive for HTLV-1, resulting in an overall prevalence of 1.0%. All HTLV-1-positive individuals were women aged 43 to 72 years with low educational attainment and income. Univariate analyses identified significant associations with injection drug use, history of blood transfusion, and family history of HTLV-1 infection. Clinically, HTLV-1-positive patients presented heterogeneous neurological manifestations, ranging from urinary dysfunction and lower limb sensory and motor impairment to musculoskeletal and inflammatory symptoms. These findings highlight the broad spectrum of neurological involvement associated with HTLV-1 infection. Early identification of HTLV-1 may contribute to improved clinical management and inform public health strategies.

N-acetylcysteine mitigates oxidative stress and reduces alveolar bone damage on experimental periodontitis in rats - Ana Paula de Andrade Silva; Erick Alves dos Santos; Deborah Ribeiro Frazão; Vinicius Ruan Neves dos Santos; José Mario Matos-Sousa; Beatriz Risuenho Peinado; Deiweson Souza-Monteiro; Wallacy Watson Pereira Melo; Zuleni Alexandre da Silva; Everton Luiz Pompeu Varela; Jorddy Neves da Cruz; Carina Maciel da Silva-Boghossian; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study evaluated the effect of N-acetylcysteine ​​on oxidative biochemistry and bone damage during the development of ligature-induced experimental periodontitis in rats. The rats were divided into three groups (n = 8/group): control, experimental periodontitis (EP), or experimental periodontitis plus daily N-acetylcysteine administration (EP + NA) (100 mg/kg/day). Periodontitis was induced by bilateral silk ligatures on the mandibular first molars for 14 days. The antioxidant capacity of N-acetylcysteine ​​was measured by (2,2-azinobis [3-ethylbenzothiazoline-6-sulfonate] (ABTS• +) and 1,1-dipheny-2-picrylhydrazyl (DPPH•) assays. Gingival samples were collected for analysis of oxidative parameters, while mandibles were used for histopathological evaluations of inflammation and collagen content, as well as for micro-computed tomography assessments of bone quality and vertical bone loss. Data were analyzed by Analysis of Variance (ANOVA), Multivariate Analysis of Variance (MANOVA), and Pearson’s correlation ( p

Effects of high- and low-phenolic pea and field bean residues at contrasting doses on soil respiration, mineral N dynamics, microbial biomass, and subsequent barley growth - Rafael D. C. Duarte; Sandra Caul; Madeline E. Giles; Eric Paterson; Pietro P. M. Iannetta; Ana M. Gomes; Marta W. Vasconcelos (Plant and Soil, 2026)
Background and aims Legume residues are important organic inputs, but their effects depend on residue chemistry and application rate. This study examined how pea ( Pisum sativum ) and field bean ( Vicia faba ) residues with contrasting phytochemical compositions influenced soil functioning and subsequent barley growth, assessing how residue quality and dose shape soil responses. Methods A sandy loam soil was amended with residues from four legume genotypes with contrasting phytochemical profiles but similar C:N ratios, applied at low (5 t ha⁻ 1 ) and high (20 t ha⁻ 1 ) rates. Unamended and mineral fertilization treatments were included for comparison. Barley was then grown in a microcosm setup for 8 weeks, and soil CO₂ efflux, microbial biomass C, inorganic N dynamics, and plant biomass were assessed. Results High-dose applications substantially increased cumulative CO₂ emissions but led to reduced microbial biomass, lower nitrate availability, and significantly suppressed barley growth, particularly for high-phenolic genotypes. In contrast, low-dose low-phenolic residues increased microbial biomass, promoted nitrification, and supported barley growth comparable with mineral fertilizers. Phenolic-rich residues maintained higher ammonium levels and showed reduced microbial and plant responses, indicating inhibitory effects of certain phytochemicals on soil processes. Conclusion Residue impacts on soil processes and crop performance depend strongly on both phytochemical composition and application rate. Low-phenolic residues applied at moderate doses have positively impacted microbial functioning, nitrogen cycling, and barley biomass, whereas high doses, especially of high-phenolic material, were detrimental to microbial activity and plant growth. Integrating residue chemistry into nutrient management could enhance the sustainability of legume-based cropping systems.

Unraveling the origin of the Azorean viral nervous necrosis 2024 outbreak through spatiotemporal and time-resolved phylogenetic analysis - Tiago Luís; Ana Margarida Henriques; Ana Duarte; Teresa Fagulha; Bernardo Almeida; Fábio Abade dos Santos; Sílvia Barros; Inês Caetano; Soraia Estácio; Paula Ramos; Margarida Duarte (Frontiers in Marine Science, 2026)
In late 2024, a mortality event affecting wild dusky grouper ( Epinephelus marginatus ) was reported across multiple islands of the Azores archipelago, Portugal. Following the previous report of the initial detection of nervous necrosis virus (NNV) infection, biological material was submitted to the National Reference Laboratory, where the outbreak was confirmed and the virus was comprehensively characterized through molecular approaches. Phylogenetic analyses based on RNA1 and RNA2 genomic segments consistently classified the detected virus within genotype I (RGNNV), the most widespread betanodavirus genotype. Maximum likelihood reconstructions revealed strong clustering of the Azorean sequences within the RGNNV lineage, with high bootstrap support and no evidence of genomic reassortment. To further investigate the origin and spread of the outbreak, a spatiotemporal and time-resolved phylogenetic analysis was conducted using the INSaFLU/Nextstrain framework. This approach identified a well-supported monophyletic cluster corresponding to the Azorean outbreak, suggesting a recent common ancestor and local expansion. Comparative analyses indicated closest genetic similarity to strains previously reported in the Indo-Pacific, supporting the hypothesis of long-distance viral dissemination followed by regional emergence, rather than direct transmission from geographically closer European outbreaks. This study provides the first spatiotemporal reconstruction of an NNV outbreak in the Azores and highlights the potential epidemiological interface between aquaculture-associated viral reservoirs and wild marine populations. These findings underscore the need for enhanced surveillance and integrated management strategies to mitigate the impact of viral diseases on vulnerable marine species.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Methane mitigation, nutritional evaluation, and in vitro degradation kinetics of diets based on tropical grass haylage treated with xylanase - Ana Beatriz de Almeida Duarte; Tairon Pannunzio Dias-Silva; Wesleyson Cristian Correa Viana; Antonio Leandro Chaves Gurgel; Marcos Jácome de Araújo; Adibe Luiz Abdalla; Leílson Rocha Bezerra; Ricardo Loiola Edvan; Romilda Rodrigues Nascimento; Sheila Vilarindo de Sousa; Carlo Aldrovandi Torreão Marques; Luis Carlos Vinhas Ítavo; et al. (Tropical Animal Health and Production, 2026)
The aim of this study was to evaluate the effect of xylanase addition (1.8 g/kg dry matter [DM]) to tropical grass haylage used in total mixed rations (TMR) on in vitro organic matter degradability, ruminal fermentation kinetics, and methane (CH4) emission. A completely randomized design was adopted in a 4 × 2 factorial arrangement, corresponding to four tropical grass cultivars (Andropogon, Mombaça, Massai, and Marandu) with or without xylanase addition and five replications per treatment (haylage bales), totaling 40 experimental bales. Ninety days after baling, the bales were opened and used to formulate total mixed rations, which were used as substrates for the in vitro incubations, according to the experimental treatments, totaling 40 TMR units (experimental diets). Chemical composition and ruminal fermentation parameters differed among grass cultivars. TMR based on Andropogon haylage showed greater crude protein concentration and higher acetate production ( P < 0.0001), whereas Mombaça haylage promoted greater propionate production and a more favorable acetate: propionate ratio ( P < 0.0003). The addition of xylanase did not alter organic matter degradability or total gas production ( P > 0.05). However, xylanase tended to reduce CH4 emission ( P = 0.0882) and improve CH4 efficiency ( P = 0.0701), indicating a potential mitigation effect on enteric methane production. Diets based on Massai haylage without xylanase showed lower gas production and faster fractional fermentation rates. Overall, the results indicate that tropical grass haylage can be successfully used in TMR systems, and xylanase supplementation may contribute to improved ruminal fermentation efficiency and methane mitigation, although further studies evaluating different enzyme levels are still required.

Nutritional quality of typical dishes from the American continent: a scoping review - Audrey Araujo Duarte; Bruna Teles Soares Beserra; Ana Júlia Pontes Aguiar; Natália Caldeira de Carvalho; Juliana Costa Liboredo (International Journal of Gastronomy and Food Science, 2026)

Aluminum tolerance and secondary metabolites modulation in Ilex paraguariensis: implications for mate composition - Thalía P. Birck; Gerâne S. Wertonge; Allan A. Kokkonen; Patrícia G. Machado; Andressa D.W.V. Martinez; Felipe K. Ricachenevsky; Jean M. Moura-Bueno; Cristiano A. Ballus; Fabio A. Duarte; Gustavo Brunetto; Luciane A. Tabaldi; Ana Lúcia A. Segatto (Food Research International, 2026)

Recurrent painful ophthalmoplegic neuropathy with alternating cranial nerve palsies: a diagnostic challenge - Miguel Saianda Duarte; Joana Neiva Correia; Margarida Palermo; Vasco Fonseca; Ana Cláudia Ribeiro (Acta Neurologica Belgica, 2026)

Betulinic acid derivatives in melanoma therapy: pharmacological assessment in a preclinical approach - Elenilson Figueiredo da Silva; Jessica Gotardi; Artur Stramari de Vargas; Cristiane Bernardes de Oliveira; Krist Helen Antunes Fernandes; Laura Trevizan Corrêa; Fabio Luiz Dal Moro Maito; Gloria Narjara Santos da Silva; Aline Rigon Zimmer; Ana Paula Duarte de Souza; Rafael Fernandes Zanin; Simone Cristina Baggio Gnoatto (Natural Product Research, 2026)

Himatanthus drasticus (Mart.) Plumel (APOCYNACEAE): phytochemical profile, evaluation of antibacterial and drug-potentiating activity, and toxicity of stem bark extracts - Maraiza Gregorio de Oliveira; Adrielle Rodrigues Costa; Jailson Renato de Lima Silva; Carlos Alonso leite dos Santos; Ana Raquel Pereira da Silva; Daniel Sampaio Alves; José Weverton Almeida-Bezerra; Ademar Maia Filho; José Walber Gonçalves Castro; Bárbara Fernandes Melo; Francisca de Fátima Silva de Sousa; Marcos Santos; et al. (Vegetos, 2026)

Unraveling the ecological impact of textile microfibers: Current knowledge and research challenges - Khawla Chouchene; Ana L. Patrício Silva; Ana Costa; Andréa Marinho; Armando C. Duarte; Teresa Rocha-Santos; João P. da Costa (Marine Pollution Bulletin, 2026)

Advancing secondary raw material flows through cleaner production: integrating mechanical recycling and eco-design of post-industrial textile waste - Duarte Brás; Ana Catarina Silva; Tiago Azevedo; Raúl Fangueiro; Diana P. Ferreira (Journal of Cleaner Production, 2026)

Decades of conservation and monitoring reveal population recovery in a globally important loggerhead rookery - Cassandra Roch; Carlos Angulo-Preckler; Kenydjeer Lima Rodrigues; Hugo Mann; Hector Barrios-Garrido; Natalie Wildermann; Luis F. López-Jurado; Ana Liria-Loza; Maria Medina-Suarez; Carlos M. Duarte (Biological Conservation, 2026)

Revealing microplastic and anthropogenic microparticles contamination in tidal blue carbon ecosystems from eastern Brazil - Daniela Gadens Zanetti; Luiz Eduardo de Oliveira Gomes; Mitchael Micael Silva Gomes; Eduardo Nery Duarte de Araújo; Ana Carolina de Lima Barizão; Anderson Antônio Batista; Jessica Dipold; Niklaus Ursus Wetter; Anderson Zanardi de Freitas; Fabio Cavalca Bom; Fabian Sá (Marine Pollution Bulletin, 2026)

In vitro osteogenic potential of magnesium alloy without and with calcium phosphate coating - Mariana de Oliveira Viana Veras; Fátima Regina Nunes de Sousa; Conceição Silva Martins; Gildênio Estevam Freire; Ana Beatriz Graça Duarte; Thâmara Manoela Marinho Bezerra; Yves Ramos Costa Beviláqua; Stephany Ellen de Castro; Matheus Brandão dos Santos Lopes; Rosemayre Souza Freire; Pierre Basílio Almeida Fechine; Abrahão Cavalcante Gomes de Souza Carvalho; et al. (Tissue and Cell, 2026)

Effect of probiotic microparticles formed by alginate and ora-pro-nobis mucilage on the quality of ice cream - Larissa Carolina de Morais; Ana Cristina Freitas de Oliveira Meira; Talma Duarte Freitas; Fabiano Freire Costa; Lanamar de Almeida Carlos; Diego Alvarenga Botrel; Lizzy Ayra Alcântara Veríssimo; Jaime Vilela de Resende (Food Control, 2026)

Physicochemical and biological properties of carboxymethyl cellulose/locust bean gum composite films reinforced with nano- or microfibrillated cellulose loaded with essential oil - Kamila Ferreira Chaves; Walter Cesar Celeri Bigui; Jhennifer Capichoni Zampilli; Ana Flávia Batista Silva; Bianca de Oliveira Botelho Vital; Carlos Eduardo de Souza Duarte; Mariana Drummond Costa Ignacchiti; Juliana Alves Resende; Michel Picanço Oliveira; Adilson Vidal Costa; Lucas de Souza Soares; Vagner Tebaldi de Queiroz (Carbohydrate Polymers, 2026)

Chemical modification of starch for high-performance bioplastics: A critical review of structure–property relationships and scalable processing - Maria Eduarda Costa; Ana Maria Sarinho; Janaina Lima; Rogério Andrade; Leonardo Baptista; Renata Duarte Almeida; Hugo M. Lisboa (Carbohydrate Polymers, 2026)

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

First report of Colletotrichum fructicola causing anthracnose on Lippia alba in Brazil - André Nunes de Oliveira; Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Bruno Leonardo Mendes; Lavinia Gabriely de Albuquerque Freitas; Rosana Blawid; Paolo Margaria; Marcos Paz Saraiva Câmara (Journal of Plant Pathology, 2026)

Seasonal bottom-up and top-down control of plankton in a hypereutrophic macrotidal lagoon on Brazil’s equatorial coast - Marco Valério Jansen Cutrim; Yago Bruno Silveira Nunes; Ana Karoline Duarte dos Santos Sá; Quedyane Silva da Cruz; Andrea Christina Gomes de Azevedo-Cutrim; Jordana Adorno Furtado (Environmental Monitoring and Assessment, 2026)
Tropical coastal lagoons often show pronounced seasonal forcing that modulates nutrient supply, light climate, and grazer pressure. We surveyed hypereutrophic Jansen Lagoon (São Luís Island, Brazil) in four campaigns during 2017 (rainy: March and April; dry: September and November) at nine near-surface stations sampled on ebb tide. Phytoplankton and zooplankton were collected and analyzed together with chlorophyll-a and nutrients to assess short-term community responses. Clustering and nMDS revealed clear rainy–dry segregation of communities, and dbRDA linked dry-season samples to higher salinity, turbidity, TP, and silicate, whereas rainy-season samples were associated with higher dissolved oxygen, Secchi depth, ammonium, and DIN. Generalized linear models explained 65% of phytoplankton variance: density increased with DIP and decreased with dissolved oxygen and with the rotifer Filinia longiseta , indicating concurrent bottom-up (nutrients, light/renewal) and top-down (grazing) controls. Microcystis wesenbergii and M. aeruginosa exhibited frequent peaks, underscoring eutrophic risk, though values remained below the bloom threshold applied here. Overall, bottom-up control predominated in the rainy season, whereas grazer pressure intensified in the dry season. Management should couple nutrient-load reductions with measures that shorten residence time, reduce resuspension, and restore macrophytes, with priority to urban margins and semi-enclosed embayments; routine tracking of DO percent saturation, DIN/DIP, Secchi depth, and chlorophyll-a is recommended for long-term assessment.

Enhanced removal of organic micropollutants in earthworm-assisted sludge treatment reed beds - Amir Gholipour; Vaidotas Kisielius; Rita Fragoso; Ana Galvão; Elizabeth Duarte; Pedro N. Carvalho (Water Research, 2026)

Spatiotemporal assessment of wildfire smoke exposure using a low-cost air quality monitoring system in a developing Amazonian city - Domingas de Oliveira Almeida; Ana Carla dos Santos Gomes; Sarah Suely Alves Batalha; Tiago Bentes Mandú; Fernanda Souza do Nascimento; Glauce Vitor da Silva; Maria João Costa; Ediclê de Souza Fernandes Duarte (Journal of Environmental Management, 2026)

Biopolymer-based strategies to improve delivery properties of B12 in alginate gels: Role of protein fillers and chitosan - Raquel de Freitas Agondi; Ludmila Meskelis; Larissa Graziele Rauber Duarte; Ana Carla Kawazoe Sato; Carolina Siqueira Franco Picone (Food Bioscience, 2026)

Synergistic use of NADES and assisted extraction technologies for recovery and stabilization of bioactive compounds in Beta vulgaris L. peels - D. Rente; R. Craveiro; A. Paiva; Ana Rita C. Duarte (Food and Bioproducts Processing, 2026)

Ecotrends: an R package for estimating habitat suitability trends over time - Neftalí Sillero; João Alírio; Nuno Garcia; Inês Freitas; João C. Campos; Lia Bárbara Duarte; Isabel Pôças; Ana Cláudia Teodoro; Salvador Arenas-Castro; A.Márcia Barbosa (Ecological Modelling, 2026)

Spatial Pattern of Litter Decomposition and Soil Carbon and Nitrogen Stocks in an Agrosilvopastoral System in the Cerrado Biome - Jaqueline de Cássia de Oliveira; Igor Costa de Freitas; Evander Alves Ferreira; Ana Clara Santos Duarte; Juliana Martins Ribeiro; Demerson Luiz de Almeida Barbosa; Warley Rodrigues Oliveira; Diana Signor; Miguel Marques Gontijo Neto; Elaine Cristina Teixeira; Luiz Arnaldo Fernandes; Leidivan Almeida Frazão (Journal of Soil Science and Plant Nutrition, 2026)
Purpose This study evaluated the effects of eucalyptus trees in an agrosilvopastoral (ASPS) system on litter dynamics, CO₂ efflux, soil fertility, and soil carbon (C) and nitrogen (N) stocks, in order to understand how these factors contribute to nutrient cycling and the restoration of soil quality, comparing it with nominal pasture (NP) and native vegetation (NV). Methods Five treatments were assessed, including three locations within a nine years-old ASPS established with double-row eucalyptus planting, based on proximity to the trees: P1 (area between the double rows), P2 (2.5 m), and P3 (7.0 m). Litter deposition and decomposition and CO 2 efflux were monitored monthly for one year. Soil samples collected up to 50 cm depth were analyzed for bulk density, fertility attributes, and carbon and nitrogen stocks. Results Annual litter deposition was highest at P1 (5.85 Mg ha⁻¹ yr⁻¹), decreasing with distance from trees. Decomposition rates were highest at P3 and P1, with faster turnover (half-life ~ 203–224 days), and lowest at P2 (279 days). CO₂ efflux was highest at P1 (6.798 µmol m⁻² s⁻¹), likely due to increased soil moisture near the trees. Litter input contributed to maintaining K and P levels, despite no fertilisers being applied after the first five years of ASPS establishment. Soil C and N stocks were highest in NV (115.4 and 11.3 Mg ha⁻¹, respectively), and similar between NP (92.4 and 8.7 Mg ha⁻¹) and ASPS (89.9 and 8.9 Mg ha⁻¹). The findings highlight the role of litter in nutrient cycling and maintaining soil C and N in ASPS. Conclusion Our findings highlight the significant potential of agrosilvopastoral systems to enhance soil fertility and boost carbon and nitrogen stocks in tropical environments. However, these benefits are strongly contingent upon the effective and integrated management of both tree and pasture components. Without appropriate management practices, the full benefits of such systems may not be achieved, limiting their potential to enhance soil quality over time compared to conventional pastures and native vegetation. Graphical Abstract

Time-Series Niche Modelling Reveals Declining Tendencies of Habitat Suitability and Ecological Functions in a Mountainous Protected Area - Inês Freitas; João Alírio; Nuno Garcia; João C. Campos; Salvador Arenas-Castro; Isabel Pôças; Lia Duarte; Ana C. Teodoro; Neftalí Sillero (Environmental Management, 2026)
Monitoring biodiversity in protected areas is essential to mitigate biodiversity loss and evaluate the effectiveness of conservation policies. Integrating satellite remote sensing technologies, ecological niche models, and time-series analyses of biodiversity trends offers a fast and robust approach for assessing habitat suitability changes and species vulnerability over time. In this study, we implemented a framework combining these tools to monitor biodiversity in the Montesinho/Nogueira Special Conservation Area (Northeast Portugal). Using the MaxEnt algorithm, we generated ecological niche models for 342 species based on a time series (2001–2023) of remote sensing data from the Moderate-Resolution Imaging Spectroradiometer (MODIS) sensor. We analysed habitat suitability trends with the Mann-Kendall test to detect changes in habitat quality, as a metric of species vulnerability for individual species, five major taxonomic groups (vascular flora, amphibians, reptiles, birds, and mammals), functional groups (e.g. climate affinity, habitat type, diet, activity, reproduction), and conservation status (regional and European levels). Our study revealed a significant decline in habitat suitability over the past two decades, impacting all taxonomic groups and ecological functions. We observed a high variability in habitat suitability trends among species and taxonomic/functional groups, highlighting the complexity of biodiversity responses to environmental changes. Functional traits such as climatic affinity, trophic level or habitat specialisation were associated with variable rates of habitat decline, with species of Atlantic affinity, species associated with croplands and wetlands, and species specialised in insectivorous diets being at higher risk. Overall, these findings emphasise the need for comprehensive biodiversity monitoring programmes and demonstrate the utility of our approach to inform evidence-based conservation strategies in protected areas globally.

Fights in a tight space: wax scale Ceroplastes deodorensis Hempel (Hemiptera: Coccidae: Ceroplastinae) and associated parasitoids (Hymenoptera: Chalcidoidea) on a new host plant (Arecaceae) - Nyeppson de Sousa Soares; Anne Caroline Santos Küll; Alexandre Santos Araújo; Gabriel Silva Dias; Ana Lúcia Benfatti Gonzalez Peronti; Leonardo Souza Duarte; Bianca Mendes de Almeida; Yanka Silva de Sousa; Valmir Antonio Costa; Roberto Antonio Zucchi; Marcoandre Savaris (International Journal of Tropical Insect Science, 2026)
The hosts of Ceroplastes deodorensis Hempel (Hemiptera: Coccidae) belong to the families Annonaceae and Moraceae, which are exclusively recorded in Brazil. In this report, we document for the first time the occurrence and impact of C. deodorensis on adult plants of the dwarf date palm, Phoenix roebelenii O’Brien (Arecaceae), in Brazil. The wax scale was collected and examined on P. roebelenii at the “Luiz de Queiroz” campus in Piracicaba, São Paulo, Brazil, between April 2024 and March 2025. The population of C. deodorensis peaked from April to October 2024, causing damage solely to the leaves (leaflets) of the dwarf date palm, which manifested as yellowing and drying. The scale insect was found to be parasitized by four species of Chalcidoidea from four families: Aprostocetus sp. (Eulophidae), Brasema sp. (Eupelmidae), Metaphycus floridensis Santos & Tavares (Encyrtidae) (new record), and Scutellista caerulea (Fonscolombe) (Eunotidae) (new record). Notably, M. floridensis and S. caerulea comprised over 90% of the total parasitoids collected. This study serves to compile and update information regarding the hosts and parasitoids of C. deodorensis.

Novel herpesvirus potentially associated with oral lesions in a two-toed sloth (Choloepus didactylus) - Carlos Sacristán; Laura Reisfeld; Aricia Duarte-Benvenuto; Roberta Zamana-Ramblas; Paloma Canedo; Islene Silva Santos; Jordana Barros; Fabiana Padilha; José Luiz Catão-Dias; Ana Carolina Ewbank (Veterinary Research Communications, 2026)
The superorder Xenarthra comprises anteaters, sloths and armadillos, all endemic of the Americas. Despite their distinctive evolutionary history, information regarding viruses affecting this group remains scarce. Herein, we report a gammaherpesvirus infection in a two-toed sloth ( Choloepus didactylus ) under human care that presented recurrent oral vesicular lesions and oral candidiasis. The gammaherpesvirus identified in oral swab sample likely represents a novel species, due to the large genetic divergence when compared to the closest sequences available on public databases, and its identification in a novel host species. This finding broadens the herpesvirus host range in Xenarthra, representing the third description in this taxonomic group. Future studies should elucidate the pathogenicity of this novel herpesvirus.

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Ocean transport and vertical mixing connect Greenland's macroalgae to deep ocean carbon sinks - Daniel F. Carlson; Nobuhiro Suzuki; Ruben Carrasco; Karen Filbee-Dexter; Laura C. Gillard; Paul G. Myers; Ana M. Queirós; Jorge Assis; Carlos M. Duarte; Mikael Sejr; Dorte Krause-Jensen (Science of The Total Environment, 2026)

The social environment and female mate choice - Samuel J. Lymbery; Ana Drago-Rosa; Nick J. Royle; Ana Duarte; David J. Hosken; C. Ruth Archer (Journal of Ethology, 2026)
Female mate choice is a major mechanism of sexual selection, influencing the evolution of behaviour, morphology and life-history. Despite being so important, much about female mate choice remains unclear. Crucially, we have a limited understanding of how mating decisions are affected by the social environment within which these decisions inevitably occur. Here, we review how the social environment influences female mate choice and discuss the wider evolutionary consequences of these effects. We examine important social environment influences on female choosiness (i.e. how much females invest in assessing potential mates), the direction of female preferences (i.e. which phenotypes females prefer) and preference strength (i.e. how strident females are in their preferences). We also consider potential coevolution between mate choice and the social environment arising because both include genes. Finally, we highlight some outstanding questions that help us more fully understand social environment impacts on female mating decisions and emphasize the need for tests of current theoretical predictions.

Toward Ocean Model-Driven Robotic Exploration - Renato Mendes; Ana Duarte; Leonardo Azevedo; Lucrezia Bernacchi; João Borges de Sousa; João Pereira; Bernardo Gabriel; João Bogas; Marina Cunha; Clara Rodrigues; Ajit Subramaniam; Fernando Esteves; et al. (Oceanography, 2026)
This interdisciplinary work demonstrates the viability of coupling ocean models with in situ robotic sampling in a dynamic coastal region as a means to increase model skill and prediction. Model-driven exploration closes the sample-assimilate-​predict-direct loop within a virtuous cycle to refine prediction for a range of applications in a region characterized by harsh conditions, high variability, and diverse physical forcings, including bathymetry and coastal topography. By exploring the feasibility of coupling high-resolution autonomous underwater vehicle (AUV) sampling and data assimilation with a geostatistical model in a continuous loop, we aim to provide a new approach to understanding coastal dynamics and processes, while using modest computational resources. The novelty of this effort is threefold: the demonstration of coupling models with AUV sampling, the importance of targeted sampling, and the impact of loop closure toward model prediction.

Natural deep eutectic systems-based Ginkgo biloba extracts: A natural and sustainable solution for skin care - Marta Marques; Ana Rita Jesus; Ana Rita C. Duarte; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2025)

Arsenic, cadmium, copper and zinc in two marlin species from the southern Gulf of California: Risk assessment and variations with environmental factors - Jorge Ruelas-Inzunza; Brigitte Gil-Manrique; María Mercedes Meza-Montenegro; Sofía Ortega-García; Leticia García-Rico; Ana Lilia López-Duarte; Pamela Spanopoulos-Zarco; Nydia Zamora-Arellano; Brisa Vega-Sánchez (Regional Studies in Marine Science, 2025)

Dissemination of arr-2 and arr-3 is associated with class 1 integrons in Klebsiella pneumoniae clinical isolates from Portugal - Rita Elias; Ana Modesto; Diana Machado; Bruna Pereira; Jody Phelan; José Melo-Cristino; Luís Lito; Luísa Gonçalves; Isabel Portugal; Miguel Viveiros; Susana Campino; Taane G. Clark; et al. (Medical Microbiology and Immunology, 2025)

Beneficial Use of Marine Gypsum in Cantaloupe Culture and its Environmental Impact on Sandy Soil - Maria Valdete da Costa; José Francismar de Medeiros; Ana Kaline da Costa Ferreira; Paula Romyne de Morais Cavalcante Neitzke; Cíntia Raquel Duarte de Freitas; Fernando Henrique Alves da Silva; Eveline de Almeida Ferreira; Diana Ferreira de Freitas; Jessica Crhistie de Castro Granjeiro; Rita Oliveira Magally da Silva Marcelino; Luiz Fernando de Sousa Antunes; Rafael Oliveira Batista; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Evolution of SAMD9 and SAMD9L genes in primates: a complex history of gene loss, gene duplication and pseudogenization - António Duarte; Ana Pinheiro; Pedro José Esteves (Immunogenetics, 2025)

Impact of climate change on the distribution of Tityus scorpions (Buthidae) in the Amazon: Implications for conservation units and indigenous territories - Thais de Andrade Moura; Jônatas Chaves-Silveira; Irene Barbosa da Fonseca Teixeira; Franciely Fernanda da Silva; Maria Carolina Lima Farias Duarte; Diene Oliveira; Ana Paula Siqueira Dornellas; Pablo Ariel Martinez (Toxicon, 2025)

Fertility and carbon stocks in Oxisols under Urochloa pastures and Eucalyptus-based agrosilvopastoral systems established in the Brazilian Cerrado - Jaqueline de Cássia de Oliveira; Igor Costa de Freitas; Ana Clara Santos Duarte; João Gabriel Figueiredo Moreira; Alex José Silva Couto; Marcos Fernando Gonçalves Lessa; Miguel Marques Gontijo Neto; Márcia Vitória Santos; Mauricio Roberto Cherubin; Carlos Eduardo Pellegrino Cerri; Leidivan Almeida Frazão (Soil and Tillage Research, 2025)

Decoding climate-induced phytoplankton dynamics in a tropical macrotidal estuary using explainable machine learning - Ana Karoline Duarte dos Santos Sá; Marco Valério Jansen Cutrim; Quedyane Silva da Cruz; Ricardo Luvizotto-Santos; Andrea Christina Gomes de Azevedo-Cutrim; Yago Bruno Silveira Nunes; Bruna Oliveira Ferreira; Antonio Ronnilson Dias Carneiro Sá (Science of The Total Environment, 2025)

Occurrence of Listeria spp. and Listeria monocytogenes in half-carcasses, meat cuts, equipment, and the environment of bovine slaughterhouses in Brazil - Leonardo França; Ursula Nunes Rauecker; Daniel Lucino Silva dos Santos; Naara Aparecida Almeida; Clarice Gebara; Cristiano Sales Prado; Valéria Quintana Cavicchioli; Moacir Evandro Lage; Francine Oliveira Duarte; Cíntia Silva Minafra e Rezende; Ana Maria de Souza Almeida; Iolanda Aparecida Nunes (Research in Veterinary Science, 2025)

Dynamics of phytoplankton functional groups and carbon concentrations in an estuary on the Brazilian equatorial margin - Danielle Stephane Campos Souza; Andrea Christina Gomes de Azevedo-Cutrim; Ana Karoline Duarte dos Santos Sá; Marco Valério Jansen Cutrim; Ana Virgínia Gomes de Oliveira; Quedyane Silva da Cruz; Rayane Serra Rosas; Christyélen Campos Souza (Marine Environmental Research, 2025)

Functional diversity and spatial distribution of zooplankton communities on the Maranhão continental shelf, Brazilian equatorial Atlantic - Yago Bruno Silveira Nunes; Marco Valério Jansen Cutrim; Xiomara Franchesca Garcia Dias; Nuno Filipe Alves Correia de Melo; Ana Karoline Duarte dos Santos Sá; Quedyane Silva da Cruz (Marine Environmental Research, 2025)

The role of Penicillium brevicompactum in bioprocessing plastic and metals from printed circuit boards - Diogo A. Ferreira-Filipe; Marta Carvalho; António J.S. Fernandes; Florinda M. Costa; Carla Patinha; Pedro Pato; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Environmental Pollution, 2025)

The biological potential and health-benefits of flavonoids: A review and development opportunities - Marco Duarte; Sílvia Santos Pedrosa; P Raaj Khusial; Ana Raquel Madureira (Chemico-Biological Interactions, 2025)

The effect of smoking on lung function changes during a 16-week combined exercise program in middle-aged workers: a latent growth curve analysis - Fernanda M. Silva; José P. Ferreira; Ana M. Teixeira; Diogo Monteiro; Pedro Duarte-Mendes (European Journal of Applied Physiology, 2025)

Guiding Elements for Strengthening Cumulative Impact Assessment Regulations for Offshore Wind Energy - Ana Paula Alves Dibo; Juliana Siqueira-Gay; Carla Grigoletto Duarte; Alexander Turra; Luis Enrique Sánchez (Environmental Management, 2025)

Geostatistical uncertainty maps for real-world efficient AUV data collection - Ana F. Duarte; Lucrezia Bernacchi; Renato Mendes; João Borges de Sousa; Leonardo Azevedo (Frontiers in Marine Science, 2025)
Autonomous Underwater Vehicle (AUV) trajectory planning for oceanographic surveys is challenging and requires comprehensive and efficient data collection for enhanced mission success. By strategically navigating and targeting high-value data points, the AUV can operate longer and gather more essential information for numerical ocean model calibration. Here, we propose a geostatistical modelling workflow with two complementary objectives. First, to jointly predict ocean temperature and spatial uncertainty maps, representing regions with limited knowledge about the ocean properties of interest, from where optimized navigation paths can be devised and updated. Second, to efficiently assimilate the collected data and update an ocean model with the new data. An autonomous oceanographic survey performed off W. Portugal illustrates the proposed modelling workflow. We use the CMEMS product of Atlantic-Iberian-Biscay-Irish-Ocean Physics Analysis and Forecast as a priori and conditioning data of the spatial predictions. During the survey, the data acquired by the AUV are assimilated and used in new geostatistical predictions for the day after the data acquisition. The results show that the proposed methodology efficiently predicts daily ocean temperature and its spatial uncertainty, allowing data assimilation from different sources (i.e., numerical models of ocean dynamics and AUV sampling). This approach enables the assimilation of AUV measurements and the model prediction to have higher value and greater reliability.

Potential immunoprophylactic use of a multi-epitope protein of CD4+ and CD8+ T cells against visceral leishmaniasis in Balb/c mice - Scarleth Silva Costa; Naianda Rezende Ribeiro; Luiza dos Reis Cruz; Gabriel José Lucas Moreira; Vivian Tamietti Martins; Daniela Pagliara Lage; Danniele Luciana Vale; Camilly Vitória Silva Costa; Nathalia Coral Galvani; Gabriel Paulino Luiz; Maria Eduarda de Oliveira; Ricardo Andrez Machado-de-Ávila; et al. (Research in Veterinary Science, 2025)

Removal of meropenem from hospital wastewater using biochar derived from grape stalks - José L.S. Duarte; Ana Hayat; Mario de la Fuente; Carmen M. Domínguez; Aurora Santos; Salvador Cotillas (Journal of Environmental Management, 2025)

Feline botulism: two decades and two reports - Ísis Assis Braga; Nicoly Ferreira de Urzedo; Guilherme Oliveira Maia; Ana Paula Carvalho Gomes; Raiany Borges Duarte; Bruna Samara Alves-Ribeiro; Andressa da Silva Martins; Tamires Ataides Silva; Luiz Henrique Barbosa Pires; Stéfanne Rodrigues Rezende; Nathalia de Assis Pereira; Raquel Loren dos Reis Paludo; et al. (Veterinary Research Communications, 2025)

Biotechnological potential of pineapple-Serendipita co-cultivation for salinity resilience in agriculture - Danielle da Silva; Ana Kelly de Sousa Silva; Fernanda Vidigal Duarte Souza; Yohan Fritsche; Valdir Marcos Stefenon (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Comparative analysis of bacterial and microalgal natural astaxanthin: Part II — Biocompatibility, bioaccessibility, encapsulation, mutagenicity, and aquatic toxicity - Cassamo U. Mussagy; Ana L.R. Gini; Cauê B. Scarim; Jonatas L. Duarte; Marlus Chorilli; Gabriely F.G. Militão; Amanda dos Santos; Nayara P. Lima; Isabela S. Ribeiro; Charles W.I. Haminiuk; Fabiane O. Farias; Gisela de A. Umbuzeiro; et al. (Algal Research, 2025)

Physical Interactions between Cancer Cells and Tumor Microenvironment - Andressa Beatriz Apolinário da Silva Correia; Beatriz Medeiros de Souza Melo; Bruna Alves da Silva; Giovana Cruz Maciel; Guilherme Matheus Santos Marques Cavalcante; João Pedro Almeida dos Santos; Layza Maria Barbosa Silva; Luís Filipe Pereira Rocha; Maria Beatriz Cavalcante Brêda; Maria Eduarda Teixeira de Oliveira; Kayo Felipe Barbosa Lima; Luiz Ben-Hur de Oliveira Wanderley Nepomuceno; et al. (Cell Biochemistry and Biophysics, 2025)

Decoding Tupiperla illiesi Froehlich 1998 (Plecoptera: Gripopterygidae): Insights into Morphological Variation and Molecular Species Delimitation - Felipe Ribeiro Pereira Sarmento; Tácio Duarte; Ana Clara Pereira Teixeira; Frederico Falcão Salles (Neotropical Entomology, 2025)

The role of ayahuasca in cell viability and oxidative stress in gastric adenocarcinoma cell line - Joana Gonçalves; José Francisco Cascalheira; Patrícia Valentão; Ângelo Luís; Eugenia Gallardo; Ana Paula Duarte (Natural Product Research, 2025)

Chemical composition and toxicity of Hedyosmum brasiliense essential oil against storage pests and fungi - Rubens Candido Zimmermann; Carolina Gracia Poitevin; Ana Marta Schafaschek; Milena Ielen; Sofia Bin Macedo; Wanderlei do Amaral; Greissi Tente Giraldi; Edson José Mazarotto; Alessandra Benatto; Carlos Eduardo Nogueira Martins; Beatriz Helena L.N. Sales Maia; Elaine Fernanda Dos Santos; et al. (Journal of Stored Products Research, 2025)

Insights on microalgae-based technologies with potential impact on global methane budget – Perspectives for industrial applications - Leandro Madureira; Ana Soares; M. Salomé Duarte; Francisco Pereira; Diogo Francisco; Filipe Maciel; António A. Vicente; Vítor Vasconcelos; M. Alcina Pereira; Pedro Geada (Bioresource Technology, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

Revisiting the emergence of the Chikungunya virus in Alagoas, Northeast of Brazil - Mykaella Andrade de Araújo; Ana Carla Eugênio Lima; Jean Phellipe Marques do Nascimento; Ana Paula Andreolla; Thiago Pina Goes de Araújo; Michel Alves do Nascimento; Ana Rachel Vasconcelos de Lima; Magliones Carneiro de Lima; Hazerral de Oliveira Santos; Anderson Brandão Leite; Juliano Bordignon; Claudia Nunes Duarte dos Santos; et al. (Brazilian Journal of Microbiology, 2025)

In Silico Development of a Multi-epitope Vaccine Targeting TFDP3: A Novel Approach for Cancer Immunotherapy - Genilda Castro de Omena Neta; Jose Wilson Batista da Silva Junior; Rodger Marcel Lima Rocha; Ana Kelly da Silva Fernandes Duarte; Emisael Stenio Batista Gomes; Fernando Berton Zanchi; Carolinne de Sales Marques; Carlos Alberto de Carvalho Fraga (Cell Biochemistry and Biophysics, 2025)

Novel paramyxovirus in wild pinnipeds, Brazil - Samira Costa-Silva; Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Carlos Sacristán; Rodrigo M. Soares; Angélica M. Sánchez-Sarmiento; Natália Silvestre-Perez; Pedro Volkmer Castilho; Cristiane K. M. Kolesnikovas; Caroline Freitas Pessi; Rafael Sardinha Murro; Carla B. Barbosa; et al. (Veterinary Research Communications, 2025)
Most emerging zoonotic viral infections originate in wildlife. The Paramyxoviridae and Coronaviridae families are important in terms of zoonotic potential and diversity of host susceptibility. To date, the only paramyxoviruses described in pinnipeds are within the genus Morbillivirus . An alphacoronavirus has been reported in pinnipeds. Herein, we surveyed for Paramyxoviridae and Coronaviridae in 46 animals of four pinniped species stranded along the coasts of Santa Catarina and São Paulo states, Brazil, between 2016 and 2022. A novel paramyxovirus (family Paramyxoviridae ) was detected in an Antarctic fur seal ( Arctocephalus gazella ) and in two South American fur seals ( Arctocephalus australis ). The sequences presented with less than 83% amino acid identity to the closest published paramyxovirus sequences, amplified in Microchiroptera sp. in Vietnam and in Asiatic yellow bats ( Scotophilus kuhlii ) in Cambodia. Phylogenetic analysis of the paramyxovirus sequences clustered into the genus Jeilongvirus . Gross and histopathological analyses did not identify any related lesions and the viral zoonotic potential is unknown. None of the animals were PCR-positive to coronavirus. To our knowledge, this is the first report of paramyxovirus infection in pinnipeds in Brazil and the first paramyxovirus not classified as Morbillivirus in seals, sea lions and walruses. To better understand the natural history of this novel virus, future pathological, serological, and molecular studies based on pan- Paramyxoviridae RT-PCRs are recommended.

Cleaning validation in pharmaceutical quality control laboratories: a structured protocol for contamination risk mitigation - Maria J. Moura; André D. Pereira; Daniel J. F. Santos; Ana G. Silva; Carla C. A. D. Paiva; Belmiro P. M. Duarte (DARU Journal of Pharmaceutical Sciences, 2025)
Background Cleaning activities are critical in pharmaceutical manufacturing to prevent cross-contamination of Active Pharmaceutical Ingredients (APIs). Traditionally, cleaning validation protocols have focused on production lines. However, there is a growing trend toward extending these protocols to Quality Control (QC) laboratories, encompassing both glassware and stainless-steel equipment. Objectives This paper presents a systematic approach for developing cleaning validation protocols specifically designed for QC laboratory equipment, aimed at improving cleaning effectiveness and ensuring regulatory compliance. Methods The proposed methodology includes: (i) identifying the worst-case API; (ii) performing recovery studies to optimize sampling methods and solvent selection; and (iii) employing statistical tools such as descriptive analysis and hypothesis testing to refine the protocol in line with current industry standards. Results A case study involving Oxcarbazepine demonstrates the application of the proposed protocol, evaluating surface contamination across various QC instruments and assessing detergent residues to validate cleaning effectiveness. Conclusion The proposed strategy provides a structured, statistically grounded framework for developing cleaning validation protocols in QC laboratories, promoting effective contamination control and adherence to regulatory standards. Graphical abstract

The essential oil of Drimys brasiliensis (Winteraceae) from Atlantic forest as an alternative biopesticide against stored pests and seedborne diseases - Rubens Candido Zimmermann; Carolina Gracia Poitevin; Ana Marta Schafaschek; Milena Ielen; Sofia Bin Macedo; Wanderlei do Amaral; Greissi Tente Giraldi; Edson José Mazarotto; Alessandra Benatto; Carlos Eduardo Nogueira Martins; Beatriz Helena L. N. Sales Maia; Elaine Fernanda Dos Santos; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Molecular landscape of therapeutic deep eutectic systems selective toxicity towards colorectal cancer - Filipe Oliveira; Joana Pinto; Filipa Amaro; Joana Pereira; Inês Ferreira; Mário S. Diniz; Paula Guedes de Pinho; Ana Rita C. Duarte (Sustainable Chemistry and Pharmacy, 2025)

Rainfall variability, land use and land cover dynamics, and implications for climate risk through a theoretical-conceptual model for the Eastern Northeast of Brazil - Micejane da Silva Costa; José Francisco de Oliveira Júnior; Bárbara Godoy de Barros; Luís Felipe Francisco Ferreira da Silva; Kelvy Rosalvo Alencar Cardoso; Akza Hellen dos Santos Silva; Ana Carla do Santos Gomes; Maytê Duarte Leal Coutinho; Edson de Oliveira Souza; Michelyne Duarte Coutinho de Morais; Ninu Krishnan Modon Valappil; Vijith Hamza; et al. (Journal of South American Earth Sciences, 2025)

Ecotoxicity of the non-dioxin-like PCB-153 in the model marine diatom Phaeodactylum tricornutum - Bernardo Duarte; João Cardoso; Eduardo Feijão; João Albuquerque Carreiras; Ricardo Cruz de Carvalho; Ana Rita Matos; Vanessa F. Fonseca; Paula Santos; Carla Palma (Journal of Hazardous Materials, 2025)

Cytotoxic and metabolic effects of organic extracts from airborne fine particulate matter (PM2.5) in neuronal cells - Tatiana Silva; Célia Alves; Margarita G. Evtyugina; Ana S. Dias; Guilherme Martins Pereira; Pérola de Castro Vasconcellos; Maria de Fátima Andrade; Helena Oliveira; Iola F. Duarte (Environmental Toxicology and Pharmacology, 2025)

Monoterpene indole alkaloids with anticancer activity from Tabernaemontana species - Bruno M. F. Gonçalves; Noélia Duarte; Cátia Ramalhete; Filipa Barbosa; Ana Margarida Madureira; Maria-José U. Ferreira (Phytochemistry Reviews, 2025)
Indole alkaloids, predominantly found in plants, are a large group of natural product-derived compounds characterized by a remarkable chemical diversity associated with significant biological properties. Among these, terpenoid indole alkaloids are the largest group of secondary metabolites. Tabernaemontana species (Apocynaceae) are widely distributed in tropical and subtropical regions of the world and used in traditional medicine to treat a variety of illnesses, including tumours. These species biosynthesize large quantities of structurally complex monoterpene indole and bisindole alkaloids. Given the compelling biological properties of indole alkaloids, the phytochemical study of Tabernaemontana species has been widely addressed to identify potential anticancer compounds. Several indole alkaloids have shown antiproliferative effect due to different mechanisms, namely by inducing apoptosis or arresting cell cycle, in diverse cancer cell lines, including multidrug-resistant phenotypes. This review primarily aims to underscore the anticancer activity of indole and bisindole alkaloids isolated from several Tabernaemontana species. Moreover, our recent contributions to the field are also highlighted, focusing on the study of Tabernaemontana elegans . The anticancer evaluation, namely the reversion of P-glycoprotein-mediated multidrug resistance, of two sets of monoterpene indole alkaloid derivatives, obtained by modification of some functional groups of two major monoterpene indole alkaloids, is reviewed, as well as the results obtained for a derivative that targeted homologous recombination DNA repair defects.

Toxicity of Melaleuca rhaphiophylla essential oils against Sitophilus zeamais and Sitophilus oryzae - Rubens Candido Zimmermann; Ana Marta Schafaschek; Adélia Maria Bischoff; Matheus Beger; Julia Sant’ana; Sofia Bin de Macedo; Milena Ielen; Carlos Eduardo Nogueira Martins; Sarah da Costa Amaral; Rilton Alves de Freitas; Alessandra Benatto; Carolina Gracia Poitevin; et al. (Journal of Pest Science, 2025)

Cultivation of Ulva sp. and Gracilaria sp. associated with a recirculating aquaculture system - Aires M. Duarte; Guilherme Carvalhal; Joana Assunção; Ana Catarina Guedes; Isabel Sousa Pinto; Isabel Costa (Journal of Applied Phycology, 2025)

Rethinking Pharmaceutical Industry with Quality by Design: Application in Research, Development, Manufacturing, and Quality Assurance - Joana Galvão Duarte; Maria Galvão Duarte; Ana Paula Piedade; Filipa Mascarenhas-Melo (The AAPS Journal, 2025)
Quality by Design (QbD) is a transformative and systematic approach to developing top-tier pharmaceutical products, ushering in a departure from traditional trial-and-error methods toward a more science-based, risk-oriented, and holistic strategy. Central to QbD implementation is the meticulous development of formulations and manufacturing processes, consistently fulfilling predefined quality objectives. The core objective of QbD remains unwavering — to guarantee the steadfast alignment of the final pharmaceutical product with predetermined quality attributes, thereby mitigating batch-to-batch variations and potential recalls. This article succinctly explores the multifaceted application of QbD methodology within the pharmaceutical industry. Emphasizing its pivotal role in research and development, manufacturing, quality control, and quality assurance, the discussion navigates through the strategic deployment of QbD elements and tools. Amidst the evident advantages of QbD, challenges persist in its widespread adoption within the pharmaceutical sector and regulatory frameworks. This article sheds light on the regulatory landscape that currently governs the implementation of QbD in these crucial stages of pharmaceutical processes. For that reason, this review article aims to provide researchers, scientists, and industry professionals with a thorough introduction to QbD so they may adopt this methodical approach to developing and producing high-quality pharmaceutical products, always in compliance with the underlying regulations. Graphical Abstract

Guettarda uruguensis (Rubiaceae): antioxidant and anti-inflammatory plant with quercetin and esters of p-coumaric acid - Ana Flavia Schvabe Duarte; Daniela Maria Soares; Luciane Dalarmi; Mariana Saragiotto Krause; Fernanda Maria Marins Ocampos; Railson Henneber; Marilis Dallarmi Miguel; Deise Prehs Montrucchio; Obdulio Gomes Miguel (Natural Product Research, 2025)

Sow thistle (Sonchus oleraceus L.) propagation in vitro: wavelength, photon flux density and natural ventilation effects on its growth and chicoric acid content - Jeremias José Ferreira Leite; Rafael Marlon Alves de Assis; João Pedro Miranda Rocha; Melvis Celeste Vilanculos Cossa; Thainá de Oliveira; Adriane Duarte Coelho; Ana Caroline Batista da Silva; Simony Carvalho Mendonça; Suzan Kelly Vilela Bertolucci; José Eduardo Brasil Pereira Pinto (South African Journal of Botany, 2025)

Recent advances in kefiran polymer to produce nanofibers and films for food packaging applications - Josemar Gonçalves de Oliveira Filho; Larissa Graziele Rauber Duarte; Lúcio Belo; Tainá Francisca Cordeiro de Souza; Ana Helena Bitencourt; Samira Tosatti Yamim; Mariana Buranelo Egea (Food and Humanity, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Insights towards the impact of subinhibitory chlorhexidine on antimicrobial susceptibility and horizontal gene transfer in Enterococcus faecium - Ana P. Pereira; Ana C. Almeida-Santos; Bárbara Duarte; Patrícia Antunes; Luísa Peixe; Ana R. Freitas; Carla Novais (Science of The Total Environment, 2025)

Sustainability assessment of collagen extraction from fish skins: A comparative life cycle assessment of conventional and NADES-enhanced processes - Miguel P. Batista; Joana Ortigueira; Naiara Fernández; Frédéric B. Gaspar; Maria do Rosário Bronze; Ana Rita C. Duarte; Tiago F. Lopes (Journal of Environmental Chemical Engineering, 2025)

Optimizing bacterial nanocellulose production from eucalyptus bark: A circular approach to wastewater management and resource recovery - Ana Cristina Rodrigues; Daniela Martins; M. Salomé Duarte; Ricardo Silva-Carvalho; Susana Marques; Ana Júlia Cavaleiro; Miguel Gama; Fernando Dourado (Journal of Environmental Chemical Engineering, 2025)

New records on autogenic behavior among populations of Ornithodoros fonsecai (Labruna and Venzal, 2009) (Ixodida: Argasidae) from northeastern Brazil - Ana Carolina Castro-Santiago; Leidiane Lima-Duarte; Jaqueline Valeria Camargo; Simone Michaela Simons; Ricardo Bassini-Silva; Ana Cláudia Calchi; Glauber Meneses Barboza de Oliveira; Maurício Cláudio Horta; Sebastián Muñoz-Leal; Marcelo Bahia Labruna; Marcos Rogério André; Rosangela Zacarias Machado; et al. (Veterinary Research Communications, 2025)

Machine learning assessment of dredging impacts on the phytoplankton community on the Brazilian equatorial margin: A multivariate analysis - Marco Valério Jansen Cutrim; Ana Karoline Duarte dos Santos Sá; Quedyane Silva da Cruz; Andrea Christina Gomes de Azevedo-Cutrim; Ricardo Luvizotto Santos; Francisco José da Silva Dias; Marianna Basso Jorge; Lisana Furtado Cavalcanti-Lima (Environmental Pollution, 2025)

Phenotypic traits and genetic diversity of elephant grass for bioenergy purposes - Josefa Grasiela Silva Santana; Rogério Figueiredo Daher; Moisés Ambrósio; Cleudiane Lopes Leite; Ana Kesia Faria Vidal; Rafael Souza Freitas; Maxwel Rodrigues Nascimento; José Antonio Lamônica Netto; João Victor Bousquet Duarte; João Esdras Calaça Farias; Alexandre Gomes de Souza (Genetic Resources and Crop Evolution, 2025)

Assessing the vulnerability of urban tree species to climate change: The case study of Lisbon gardens - Ana Raquel Cunha; Ana Luísa Soares; Sílvia Catarino; Maria Cristina Duarte; Maria M. Romeiras (Urban Forestry & Urban Greening, 2025)

Paleoenvironmental reconstruction of the Neoproterozoic Mudador Marble, Passo Feio Complex, Dom Feliciano Belt, southern Brazil - Evandro Oliveira de Oliveira; Edinei Koester; Carla Cristine Porcher; Daniel Triboli Vieira; Rodrigo Chaves Ramos; André Sampaio Mexias; Ana Karina Scomazzon; Everton M. Bongiolo; André Abreu Martins; Vivianne Andrades Bastos; Leonardo Sacher Duarte; Iago Gunther Dubbon (Journal of South American Earth Sciences, 2025)

Glacial-interglacial changes in Antarctic Intermediate Water advection in the Southeast Pacific during the last 787 kyr - Karol O. Duarte; Igor M. Venancio; Rodrigo A. Nascimento; Ana Luiza S. Albuquerque; Thiago P. Santos; Stefano Crivellari; Cristiano M. Chiessi (Global and Planetary Change, 2025)

Facultative anaerobic bacteria enable syntrophic fatty acids degradation under micro-aerobic conditions - Carla Pereira Magalhães; M. Salomé Duarte; M. Alcina Pereira; Alfons J.M. Stams; Ana J. Cavaleiro (Bioresource Technology, 2025)

Assessing spatial and temporal trends over time in potential species richness using satellite time-series and ecological niche models - Nuno Garcia; João C. Campos; João Alírio; Lia B. Duarte; Salvador Arenas-Castro; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Biodiversity and Conservation, 2025)
Assessing biodiversity in protected areas is essential for effective conservation management. However, conventional methods for estimating species richness can lead to inaccurate assessments of biodiversity in these regions. To address this, we present a complementary approach to assess potential species richness at a 1 km resolution in the special conservation area of Montesinho/Nogueira (SAC-MN; Portugal), based on a spatial and temporal estimates of species richness trends over time (2001–2021). We compiled 10,190 species occurrence records from four taxonomic groups: amphibians, reptiles, birds, and mammals. We created correlative ecological niche models (MaxEnt) with a time series of satellite-remote sensing variables (SRS-ENMs) using Google Earth Engine (GEE). We calculated annual potential species richness (PSR) maps by stacking the SRS-ENMs and identified positive and negative trends with the Mann–Kendall test. Each species’ ecological niche model revealed unique patterns of habitat suitability within SAC-MN over time. The eastern and western boundaries of SAC-MN revealed an increase in PSR, while the central area indicated PSR declines. Each group displayed different trends in PSR: birds and mammals were more similar between them than amphibians and reptiles. This approach provides ecologists and conservationists with valuable tools to evaluate PSR and trends over time, offering crucial insights for decision-makers and stakeholders to support local biodiversity conservation efforts.

First report of Colletotrichum musicola causing anthracnose on Dioscorea alata - Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Anthony Carlos da Silva; Fernanda Oliveira da Silva; Willie Anderson dos Santos Vieira; Stephan Miller; Lisa A. Castlebury; Marcos Paz Saraiva Camara (Journal of Plant Pathology, 2025)

Grazing intensity for enhanced resource use efficiency in integrated crop-livestock systems: Balancing soil carbon storage and food security - Leonardo Dallabrida Mori; Vicente José Laamon Pinto Simões; Carolina dos Santos Cargnelutti; Lóren Pacheco Duarte; Gabriela Lima Leal; Ana Paula Schwede Doberstein; Taise Robinson Kunrath; Pedro Arthur de Albuquerque Nunes; Edicarlos Damascena de Souza; Cimélio Bayer; Paulo César de Faccio Carvalho (Journal of Environmental Management, 2025)

Evaluation of the antimicrobial effect of oregano essential oil (Origanum vulgare) on cooked mussels (Perna perna) experimentally contaminated with Escherichia coli and Salmonella Enteritidis - Laura Ribeiro Cerqueira de Oliveira; Ana Carolina Monteiro de Barros da Cruz Machado; Carlos Eduardo de Freitas Guimarães Filho; Erick Almeida Esmerino; Flávia Aline Andrade Calixto; Eliana de Fátima Marques de Mesquita; Maria Carmela Kasnowski Holanda Duarte (Food Control, 2025)

Application of a hybrid fuzzy inference system to map the susceptibility to fires - Miqueias Lima Duarte; Tatiana Acácio da Silva; Jocy Ana Paixão de Sousa; Amazonino Lemos de Castro; Roberto Wagner Lourenço (Natural Hazards, 2025)

Anthocyanins stabilization of Hibiscus sabdariffa extract with sepiolite: Analytical and reactive force fields approaches - Ana S. Márquez-Rodríguez; Arasay Carrión; Felipe Trejo; Hilda E. Esparza-Ponce; José M. Nápoles-Duarte; María L. Ballinas-Casarrubias; Luis E. Fuentes-Cobas; Erika Salas; Juan P. Palomares-Báez; María E. Fuentes-Montero (Sustainable Chemistry and Pharmacy, 2024)

Determination of mometasone furoate solubility, using deep eutectic systems, and topical formulation- experimental and computational studies - Rita Craveiro; Ângelo Rocha; Cláudio Fernandes; Ana Rita C. Duarte; Joana Marto; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2024)

Diverse genomic and epidemiological landscapes of redundant pbp5 genes in Enterococcus spp.: Insights into plasmid mobilization, ampicillin susceptibility, and environmental interactions - Paula Bierge; Miquel Sánchez-Osuna; Bárbara Duarte; Inmaculada Gómez-Sánchez; Mateu Espasa; Ana R. Freitas; Luisa Peixe; Oriol Gasch; Oscar Q. Pich; Carla Novais (Science of The Total Environment, 2024)

Impact of pre-fermentative maceration techniques on the chemical characteristics, phenolic composition, in vitro bioaccessibility, and biological activities of alcoholic and acetic fermented products from jaboticaba (Plinia trunciflora) - Bruna Rafaela da Silva Monteiro Wanderley; Natália Duarte de Lima; Carolina Turnes Pasini Deolindo; Aniela Pinto Kempka; Liziane Schittler Moroni; Victor Valentim Gomes; Luciano Valdemiro Gonzaga; Ana Carolina Oliveira Costa; Renata Dias de Mello Castanho Amboni; Ana Carolina Moura de Sena Aquino; Carlise Beddin Fritzen-Freire (Food Research International, 2024)

Neural networks in evaluating the post-harvest quality of strawberries fertilized with calcium and/or leaf silicon - Giulia Nayara Duarte; Hanna Elisia Araújo de Barros; Caio Vinicius Lima Natarelli; Jandeilson Pereira dos Santos; Lissa Izabel Ferreira de Andrade; Marcelo Henrique Avelar Mendes; Natalie Galhardo Ribeiro; Ana Beatriz Silva Araújo; Paulo César Ossani; Elisângela Elena Nunes Carvalho; Luciane Vilela Resende (Food and Humanity, 2024)

Trends in land cover and in pollen concentration of Quercus genus in Alentejo, Portugal: Effects of climate change and health impacts - Ana Galveias; Ediclê de Souza Fernandes Duarte; Mauro Raposo; Maria João Costa; Ana Rodrigues Costa; Célia M. Antunes (Environmental Pollution, 2024)

Eplingiella fruticosa leaf essential oil complexed with β-cyclodextrin exerts a neuroprotective effect in an Alzheimer’s disease animal model induced by Streptozotocin - Vanessa Alexandre-Silva; Beatriz Soares-Silva; Gabrielle Christine Pereira; Ana Claúdia Custódio-Silva; Patrícia Santos Carvalhinho-Lopes; Luciana Oliveira Taliano; Rafael Herling Lambertucci; Marcelo Duarte Cavalcante; Adriano Antunes de Souza Araújo; Lucindo Quintans-Júnior; José Ronaldo dos Santos; Alessandra Mussi Ribeiro (Metabolic Brain Disease, 2024)

Predicting health impacts of wildfire smoke in Amazonas basin, Brazil - Yara de Souza Tadano; Sanja Potgieter-Vermaak; Hugo Valadares Siqueira; Judith J. Hoelzemann; Ediclê S.F. Duarte; Thiago Antonini Alves; Fabio Valebona; Iuri Lenzi; Ana Flavia L. Godoi; Cybelli Barbosa; Igor O. Ribeiro; Rodrigo A.F. de Souza; et al. (Chemosphere, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Leptospirosis seroprevalence and associated risk factors in dairy goats in the Brazilian semi-arid region - Murilo Duarte de Oliveira; Davidianne de Andrade Morais; Ana Milena César Lima; Nathália Maria de Andrade Magalhães; Nathanael Natércio da Costa Barnabé; Raimundo Rizaldo Pinheiro; Francisco Selmo Fernandes Alves; Sérgio Santos de Azevedo; Clécio Henrique Limeira; Clebert José Alves (Research in Veterinary Science, 2024)

A pilot-scale evaluation of residual sludge quality in a worm-sludge treatment reed bed in the Mediterranean region - Amir Gholipour; Rita Fragoso; Ana Galvão; Elizabeth Duarte (Journal of Environmental Management, 2024)

Edible insects: Understanding benzo(a)pyrene toxicokinetics in yellow mealworms for safe and sustainable consumption - Diogo N. Cardoso; Regina M.B.O. Duarte; Ana Rita R. Silva; Marija Prodana; Ana Góis; Patricia V. Silva; Amid Mostafaie; José Pinto; Pedro F. Brandão; Ivã G. Lopes; Bryan W. Brooks; Susana Loureiro (Science of The Total Environment, 2024)

Exploring the biological properties and bioaccessibility of orange peel extracts using deep eutectic systems - Adriana Viñas-Ospino; Isabel Sá-Nogueira; Ana Rita Duarte; Daniel López-Malo; María José Esteve; Ana Frígola; Jesús Blesa; Alexandre Paiva (Food Bioscience, 2024)

Ultrasound and microwaves reduce stress in probiotics during avocado drying: Impact on mass transfer and cell viability - Newton Carlos Santos; Raphael Lucas Jacinto Almeida; Shênia Santos Monteiro; Virgínia Mirtes de Alcântara Silva; Thalis Leandro Bezerra de Lima; Maria Monique Tavares Saraiva; Rebeca Morais Silva Santos; Ana Nery Alves Martins; Yaroslávia Ferreira Paiva; Jefferson Soares de Lima; Maria Eduarda Martins Duarte da Costa; Matheus Augusto de Bittencourt Pasquali; et al. (Food Bioscience, 2024)

Spatial heterogeneity of zooplankton community in an eutrophicated tropical estuary - Rayane Serra Rosas; Andrea Christina Gomes Azevedo-Cutrim; Marco Valério Jansen Cutrim; Quedyane Silva da Cruz; Danielle Stephane Campos Souza; Ana Karoline Duarte dos Santos Sá; Ana Virginia Gomes Oliveira; Taíza Pimentel Santos (Aquatic Sciences, 2024)

Assessment of oxidative stress biomarkers in Palaemon varians exposed to deep eutectic systems - Mª Pilar Garralaga; Ines Ferreira; Laura Lomba; Elisabet Pires; Sara Gracia-Barberán; Ana Rita C. Duarte; Mário Diniz (Environmental Science and Pollution Research, 2024)
In recent years, there has been extensive research within the scientific community on deep eutectic systems due to their remarkable versatility in solubilizing diverse substances and serving as effective solvents in catalytic processes. While initially regarded as non-toxic, a comprehensive toxicological assessment is essential to comprehend their behavior within organisms. In this study, seven distinct systems, composed of N,N,N -triethyl- N -(2,3-dihydroxypropyl)ammonium chloride (N00Cl) and glycerol-derived ethers with alkyl chains of varying lengths (100, 200, 3F00, 300, 3i00, and 400), in a 1:2 molar ratio were investigated for their aquatic toxicity in shrimp ( Palaemon varians ). The assessment involved analyzing oxidative stress biomarkers such as glutathione S-transferase, glutathione peroxidase, catalase, superoxide dismutase, total antioxidant capacity (TAC), and lipoperoxidation (MDA content). Results show an odd–even effect for LC 50 values being N00Cl-300 , the system showing higher values. Regarding oxidative stress, an imbalance between reactive oxygen species (ROS) and antioxidant capacity in the organisms has been observed, suggesting significant toxicity to shrimps due to the changes in oxidative stress biomarkers at high concentrations. However, at 100 mg/l all systems can be considered environmentally safe, and no negative impacts are expected on aquatic ecosystems.

Comprehensive DNA metabarcoding-based detection of non-indigenous invertebrates in recreational marinas through a multi-substrate approach - Ana S. Lavrador; Fábio G. Amaral; Jorge Moutinho; Pedro E. Vieira; Filipe O. Costa; Sofia Duarte (Marine Environmental Research, 2024)

Green extraction of phenolic compounds from the by-product of purple araçá (Psidium myrtoides) with natural deep eutectic solvents assisted by ultrasound: Optimization, comparison, and bioactivity - Natália Duarte de Lima; Bruna Rafaela da Silva Monteiro Wanderley; Ana Letícia Andrade Ferreira; Marina Pereira-Coelho; Isabel Cristina da Silva Haas; Luciano Vitali; Luiz Augusto dos Santos Madureira; José Miguel Müller; Carlise Beddin Fritzen-Freire; Renata Dias de Mello Castanho Amboni (Food Research International, 2024)

The virome of bubaline (Bubalus bubalis) tonsils reveals an unreported bubaline polyomavirus - Francine C. B. Timm; Fabrício Souza Campos; Luis Janssen; Raíssa Nunes dos Santos; Bruna Paredes-Galarza; Nicole Vieira Stone; Martha Trindade Oliveira; Raíssa Gasparetto; Nicolas Felipe Drum Müller; Alanis da Silva Melgarejo; Miguel Leonetti Corrêa; Lina Marcela Violet Lozano; et al. (Brazilian Journal of Microbiology, 2024)

First report of Schlumbergera virus X infecting dragon fruit (Selenicereus spp.) in Portugal - Natália Tomás Marques; Ana Rita Trindade; Amílcar Duarte (Journal of Plant Pathology, 2024)

A comparative study of worm-sludge treatment reed bed planted with Phragmites australis and Arundo donax in the Mediterranean region - Amir Gholipour; Rita Fragoso; Ana Galvão; Elizabeth Duarte (Environmental Science and Pollution Research, 2024)
Sludge treatment reed bed planted (STRB) with Phragmites australis ( P.australis ) and Arundo donax ( A.donax ) was assessed in the presence of Eisenia fetida under control condition during the dry season. Worm-planted units were fed with mixed sewage sludge (dry and volatile solids of 29.44 g DS.L −1 and 24.23 g VS.L −1 ). Sludge loading rates (SLR) of 50, 60, and 70 kg DS m −2 year −1 were examined to assess dewatering efficiency. Surface layers in units with P.australis and A.donax achieved DS of 80 and 81% at a loading rate of 50 kg DS m −2 year −1 , while their subsurface DS were 41 and 25%, respectively. Units with A.donax experienced plant loss when subjected to SLR exceeding 60 kg DS m −2 year −1 . More than 10 cm of residual sludge accumulated on the top of units after a 2-month final rest. Evapotranspiration was greater in the unit with P.australis (5.23 mm day −1 ) compared to the unit with A.donax (4.24 mm day −1 ) while both were fed with 70 kg DS m −2 year −1 . Water loss contributions from residual sludge layer, drained water, and evapotranspiration were 3, 46, and 51%, respectively. Units with P.australis indicated 20% higher water loss compared to units with A.donax . Although the drained water quality improved over time, it did not meet standard limits. The residual sludge layer contained macro and micronutrients, and heavy metals with a significant elemental order of N > Ca > P > S > mg > K (N:P:K = 31:8:1), Fe > Na > B > Mn > Mo and Zn > Cr > Cu > Pb > Ni > Cd. Overall, STRB could be a sustainable alternative technology to conventional sewage sludge management techniques. Graphical Abstract

Dynamic shifts of functional diversity through climate-resilient strategies and farmland restoration in a mountain protected area - João C. Campos; João Alírio; Salvador Arenas-Castro; Lia Duarte; Nuno Garcia; Adrián Regos; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Journal of Environmental Management, 2024)

Magnetic refrigeration enhanced by magnetically-activated thermal switch: An experimental proof-of-concept - Vivian M. Andrade; Cláudia R. Fernandes; Daniel J. Silva; Joana S. Teixeira; Clara R. Pereira; Rita Duarte; Ana L. Pires; João Ventura; Joana Oliveira (International Journal of Refrigeration, 2024)

Bacterial diversity of mineral well water from ten sources belonging to the Guarani aquifer system: Assessment by cultivation-dependent and cultivation-independent methods and their correlation with water physicochemical properties - Danilo Moreira Vilas Boas; Héctor Sierra; Larissa Pereira Margalho; Ana Carolina H. Ramos; Giancarlo P. Saraiva; Wilson Jose F.L. Junior; Vinícius da Silva Duarte; Anderson S. Sant’Ana (Groundwater for Sustainable Development, 2024)

Herpesviruses in migrating procellariforms, northeastern Brazil - Carlos Sacristán; Aricia Duarte-Benvenuto; Pedro Enrique Navas-Suárez; Roberta Zamana-Ramblas; Laura Baes; Barbara Sophia Codeas; Larissa Pavanelli; Joana Ikeda; José Luiz Catão-Dias; Ana Carolina Ewbank (Veterinary Research Communications, 2024)
Seabirds are one of the most threatened avian groups. Viruses, including herpesvirus, represent considerable threats to marine avifauna. Herein, our goal was to survey herpesvirus in Procellariiformes that stranded in Brazil between June and July 2021. We analyzed 12 Cory's shearwaters ( Calonectris borealis ), two Great Shearwaters ( Ardenna gravis , syn. Puffinus gravis ) and one Yellow-nosed Albatross ( Thalassarche chlororynchos ) found in an unusual mortality event in Bahía state, northeastern Brazil. After necropsy, selected tissue samples were tested for herpesvirus using a broad-range nested PCR. Overall, 20% (3/15) of the birds were herpesvirus-positive, i.e., two Cory's Shearwaters and one Great Shearwater. One alphaherpesvirus sequence type was identified in each shearwater species, classified into the genus Mardivirus . This study describes two likely novel herpesviruses in shearwaters, contributing to the currently very scarce data regarding infectious agents in Procellariiformes. Further studies are necessary to evaluate the presence and characteristics of herpesvirus in Procellariiformes, and the presence (or not) of related disease in order to understand the epidemiology of this infectious agent and eventually contribute to the conservation of this endangered seabird group.

Long-term administration of omeprazole in mice: a study of behavior, inflammatory, and oxidative stress alterations with focus on central nervous system - Dulce Maria Nascimento Coelho; Dilailson Carlos Costa Júnior; Daniel Moreira Alves da Silva; Ana Carolina Benício Alves; Raquell de Castro Chaves; Manoela de Oliveira Rebouças; José Tiago Valentim; Andressa Alexandre de Oliveira; Iardja Stefane Lopes Sales; Lucas Antonio Duarte Nicolau; Francisca Cléa Florenço de Sousa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Toxicity of the emerging pollutants propylparaben and dichloropropylparaben to terrestrial plants - Caio Okon; Mylena Bathke Rocha; Lizandra de Souza Ratuchinski; Diego Espirito Santo; Charla Chaionara Schults Duarte; Lidiane de Lima Feitoza; Osvaldo Valarini Junior; Paulo Michel Pinheiro Ferreira; Edson Araújo de Almeida; Maria Cristina Oliveira Halmemam; Danielle Cristina dade SilvaOliveira; Regiane da Silva Gonzalez; et al. (Environmental Science and Pollution Research, 2024)

Alkaloids (emetine and cephalin) production – affected by full sunlight stress in Carapichea ipecacuanha - Cristina Moll Hüther; Vitor Francisco Ferreira; Fernando de Carvalho da Silva; Wilson da Costa Santos; Junior Borella; Ramonn Diego Barros de Almeida; Daniela Marques Correia; Glauce Christian Alves Duarte; Ana Claudia Langaro; Julia Ramos de Oliveira; Jóice Azeredo Silva; Thelma de Barros Machado; et al. (Natural Product Research, 2024)

Biodegradation of e-waste microplastics by Penicillium brevicompactum - Diogo A. Ferreira-Filipe; Leila Oliveira; Ana Paço; António J.S. Fernandes; Florinda M. Costa; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Science of The Total Environment, 2024)

Bilateral testicular myxosarcoma in a cryptorchid dog - Tábatta Arrivabene Neves; Wanderson Lucas Alves dos Santos; Marlos Melo Duarte; Camila Arrivabene Neves; Jael Soraes Batista; Tiago da Silva Teófilo; Lucas dos Santos Rebouças; Ana Kelen Felipe Lima; Francisca Elda Ferreira Dias; Mônica Arrivabene; Tânia Vasconcelos Cavalcante (Research in Veterinary Science, 2024)

Geochemical associations between the lateritic crusts and carbonatitic rocks of the Carbonatitic Complex at Morro dos Seis Lagos, AM, Brazil - Ana Carolina de Faria Duarte; Claudio Gerheim Porto; Artur Cezar Bastos Neto; Reiner Neumann; Lucy Takehara; João Pedro Proença Bento (Journal of Geochemical Exploration, 2024)

Laetia procera (Poepp.) Eichler can be included in polycyclic management programs for timber production, replacing species intensively harvested in the Amazon forest - Ana Paula Souza Ferreira; João Olegário Pereira de Carvalho; Cassio Rafael Costa dos Santos; Washington Duarte Silva da Silva; Tatiana da Cunha Castro; Afonso Figueiredo Filho; Ademir Roberto Ruschel (Forest Ecology and Management, 2024)

Protection of cowpea seeds and toxicity against cowpea weevils by the essential oils from Lippia alba (verbenaceae) and Schinus terebinthifolius (anacardiaceae) - Rafael Torre; Elisabeth Alves Duarte Pereira de Medeiros; Camila da Silva Barbosa Pereira; Ana Clara Ramos Menezes; Igor Sampaio Fontes; Larissa Vitória Ribeiro Pereira; Diego Henrique Fernandes Paiva; André Marques dos Santos; Pedro Corrêa Damasceno Junior; Marco Andre Alves de Souza (Crop Protection, 2024)

Evaluating drained water quality in a pilot worm-sludge treatment reed bed planted with Arundo donnas in the Mediterranean climate - Amir Gholipour; Rita Fragoso; Ana Galvão; Elizabeth Duarte (Science of The Total Environment, 2024)

How temperature modulates the expression of pathogenesis-related molecules of the cross-kingdom pathogen Lasiodiplodia hormozganensis - Carina Félix; Rodrigo Meneses; Micael F.M. Gonçalves; Ana S. Duarte; Jesus V. Jorrín-Novo; Yves van de Peer; Dieter Deforce; Filip Van Nieuwerburgh; Artur Alves; Ana C. Esteves (Science of The Total Environment, 2024)

Lactobacillus delbrueckii CIDCA 133 fermented milk modulates inflammation and gut microbiota to alleviate acute colitis - Luís Cláudio Lima de Jesus; Andria dos Santos Freitas; Joyce da Cruz Ferraz Dutra; Gabriela Munis Campos; Monique Ferrary Américo; Juliana Guimarães Laguna; Evandro Gonçalves Dornelas; Rodrigo Dias de Oliveira Carvalho; Kátia Duarte Vital; Simone Odília Antunes Fernandes; Valbert Nascimento Cardoso; Jamil Silvano de Oliveira; et al. (Food Research International, 2024)

Application of the galactomannan gel from Cassia grandis seeds for biomedical purposes: Study of the incorporation of collagenases and their release profile - Carolina de Albuquerque Lima Duarte; Mateus Gonçalves da Silva; Ana Lúcia Figueiredo Porto; Maria Carolina de Albuquerque Wanderley; Sabrina Swan Souza da Silva; Alexsandra Frazão de Andrade; Raquel Pedrosa Bezerra; Attilio Converti; Diego Gomes Ramos; Daniela de Araújo Viana Marques; Priscilla Barbosa Sales de Albuquerque (Carbohydrate Polymers, 2024)

Production of carotenoids by Rhodotorula mucilaginosa using glucose and cassava wastewater and a comparison between ethanol, methanol and DMSO in their extraction - Carolina Sangalli Dardani; Whallans Raphael Couto Machado; Ana Lúcia Ferrarezi Duarte; Giovana da Costa Oliveira; Maurício Bonatto Machado de Castilhos; Vanildo Luiz Del Bianchi (Biocatalysis and Agricultural Biotechnology, 2024)

Antarctic fungi produce pigment with antimicrobial and antiparasitic activities - Sabrina Barros Cavalcante; André Felipe da Silva; Lucas Pradi; Jhuly Wellen Ferreira Lacerda; Tiago Tizziani; Louis Pergaud Sandjo; Lenon Romano Modesto; Ana Claudia Oliveira de Freitas; Mario Steindel; Patricia Hermes Stoco; Rubens Tadeu Delgado Duarte; Diogo Robl (Brazilian Journal of Microbiology, 2024)

Endophytic species of Colletotrichum associated with cashew tree in northeastern Brazil - Diana Gissell Barreto Ramos; Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Anthony Carlos da Silva; Willie Anderson dos Santos Vieira; Lisa A. Castlebury; Marcos Paz Saraiva Câmara (Fungal Biology, 2024)

Thiazolyl-isatin derivatives: Synthesis, in silico studies, in vitro biological profile against breast cancer cells, mRNA expression, P-gp modulation, and interactions of Akt2 and VIM proteins - Luiz Alberto Barros Freitas; Carolina Sousa; Beatriz Silva Lima; Denise Duarte; Paulo André Teixeira de Moraes Gomes; Camila Gabriela Costa Ramos; Valécia de Cássia Mendonça Costa; Maira Galdino da Rocha Pitta; Moacyr Jesus Barreto de Melo Rêgo; Carlos Alberto de Simone; Mafalda Videira; Ana Cristina Lima Leite (Chemico-Biological Interactions, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Organic contamination and multi-biomarker assessment in watersheds of the southern Brazil: an integrated approach using fish from the Astyanax genus - Yuri Dornelles Zebral; Bruna Duarte Pereira Righi; Iuri Salim Abou Anni; Ana Laura Venquiaruti Escarrone; Tainá Guillante; Carlos Eduardo Delfino Vieira; Patrícia Gomes Costa; Adalto Bianchini (Environmental Science and Pollution Research, 2024)

The impact of chronic and acute problems on sea turtles: The consequences of the oil spill and ingestion of anthropogenic debris on the tropical semi-arid coast of Ceará, Brazil - Alice F. Feitosa; Ícaro B.H.M.P. Menezes; Oscar S. Duarte; Carminda S．B． Salmito-Vanderley; Pedro B.M. Carneiro; Rufino N.A. Azevedo; André H.B. Oliveira; Ana C.S. Luz; Adriana P. Nascimento; Ronaldo F. Nascimento; Laercio L. Martins; Rivelino M. Cavalcante; et al. (Aquatic Toxicology, 2024)

Chronic exposure to 2,2′-azobis-2-amidinopropane that induces intestinal damage and oxidative stress in larvae of Drosophila melanogaster - Rener Mateus Francisco Duarte; Serena Mares Malta; Fernanda Naves Araújo do Prado Mascarenhas; Vinicius Prado Bittar; Ana Luiza Borges; Renata Roland Teixeira; Renata Graciele Zanon; Carlos Ueira Vieira; Foued Salmen Espindola (Environmental Toxicology and Pharmacology, 2024)

Seroprevalence of hepatitis E virus in patients with chronic liver disease - Lílian Rose Maia Gomes de Araújo; Andrea Dória Batista; Maria Rosângela Cunha Duarte Côelho; Joelma Carvalho Santos; Gabriel Galindo Cunha; Gabriela Rodrigues Aguiar Leal; João Renato Rebello Pinho; Ana Lúcia Coutinho Domingues; Edmundo Pessoa Lopes (Brazilian Journal of Microbiology, 2024)

Water balance analysis in a novel pilot-scale of the Worm-sludge treatment reed bed (W-STRB) planted with Arundo donax - Amir Gholipour; Rita Fragoso; Ana Galvão; Elizabeth Duarte (Water Research, 2024)

Microplastics from agricultural mulch films: Biodegradation and ecotoxicity in freshwater systems - Diogo A. Ferreira-Filipe; Ana Paço; Bruna Pinho; Rafael Silva; Sara A.M. Silva; Fátima Jesus; Joana L. Pereira; Armando C. Duarte; Teresa A.P. Rocha-Santos; Ana L. Patrício-Silva (Science of The Total Environment, 2024)

Stored products insects in Portugal – New data and overview - Sónia Duarte; Ana Magro; Graça Barros; Maria Otilia Carvalho (Journal of Stored Products Research, 2024)

Comparative responses and effects of exposure to metallic and nanoparticle zinc in the mussel Mytilus galloprovincialis - Joana Roma; Madalena Missionário; Carolina Madeira; Ana Rita Matos; Catarina Vinagre; Pedro M. Costa; Bernardo Duarte (Estuarine, Coastal and Shelf Science, 2024)

Evidence of Mycobacterium avium subsp. paratuberculosis binding to albumin: technical and biological implications - Ana Jolly; María Laura Barnech; Juan José Duarte; Jorge Suhevic; Ana María Jar; Silvia Leonor Mundo (Veterinary Research Communications, 2024)

New approaches for modulation of alginate-chitosan delivery properties - Ludmilla Meskelis; Raquel F. Agondi; Larissa G.R. Duarte; Matheus D. de Carvalho; Ana Carla K. Sato; Carolina S.F. Picone (Food Research International, 2024)

A Stochastic Model of an Early Warning System for Detecting Anomalous Incidence Values of COVID-19 - Ana Filipa Duarte; Amílcar Soares; Maria João Pereira; André Peralta-Santos; Pedro Pinto Leite; Leonardo Azevedo (Mathematical Geosciences, 2024)
The ability to identify and predict outbreaks during epidemic and pandemic events is critical to the development and implementation of effective mitigation measures by the relevant health and political authorities. However, the spatiotemporal prediction of such diseases is not straightforward due to the highly non-linear behaviour of its evolution in both space and time. The methodology proposed herein is the basis of an early warning system to predict short-term anomalous values (i.e., high and low values) of the incidence of COVID-19 at the municipality level for mainland Portugal. The proposed modelling tool combines stochastic sequential simulation and machine learning, namely symbolic regression, to model the spatiotemporal evolution of the disease. The machine learning component is used to model the 14-day incidence rate curves of COVID-19, as provided by the Portuguese Directorate-General for Health, while the geostatistical simulation component models the spatial distribution of these predictions, for a simulation grid comprising the metropolitan area of Lisbon, following a pre-defined spatial continuity pattern. The method is illustrated for a period of 5 months during 2021, and considering the entire set of 19 municipalities belonging to the metropolitan area of Lisbon, Portugal. The results show the ability of the early warning system to predict and detect anomalous high and low incidence rate values for different periods of the pandemic event during this period.

Sulfated iota-carrageenan from marine alga Agardhiella ramosissima prevents gastric injury in rodents via its antioxidant properties - João Lucas Silva Pinheiro; Lucas Henrique Marques Rodrigues; Lorena Duarte da Silva; Victória Martins Rodrigues dos Santos; Dayane Aparecida Gomes; Francisco Diego da Silva Chagas; Luciano de Sousa Chaves; Márcia Rúbia Silva Melo; Ana Lúcia Ponte Freitas; Marcellus Henrique Loiola Ponte Souza; Jand-Venes Rolim Medeiros; Renan Oliveira Silva Damasceno (Algal Research, 2024)

Facemasks: An insight into their abundance in wetlands, degradation, and potential ecotoxicity - Ana Paço; Ana M. Oliveira; Diogo A. Ferreira-Filipe; Andreia C.M. Rodrigues; Rui J.M. Rocha; Amadeu M.V.M. Soares; Armando C. Duarte; Ana L. Patrício Silva; Teresa Rocha-Santos (Science of The Total Environment, 2023)

Quantitative microbiological risk assessment for the occurrence of listeriosis in Brazil due to the consumption of milk processed by pasteurization or thermosonication - Gustavo Luis P.A. Ramos; Maria Carmela K.H. Duarte; Janaína S. Nascimento; Adriano G. Cruz; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2023)

Adverse Effects of Octocrylene on Cultivated and Spontaneous Plants and in Soil Animal - Gabrielle Cristina dos Santos Gonçalves Nascimento; Daniela Giovana da Cunha Barros; Lizandra Souza Ratuchinski; Caio Okon; Patricia Aline Bressiani; Diego Espirito Santo; Charla Chaionara Schults Duarte; Paulo Michel Pinheiro Ferreira; Osvaldo Valarini Junior; Juan Carlos Pokrywiecki; Elisângela Dusman; Regiane da Silva Gonzalez; et al. (Water, Air, & Soil Pollution, 2023)

Plasmacytoid Dendritic Cells, the Expression of the Stimulator of Interferon Genes Protein (STING) and a Possible Role of Th17 Immune Response in Cervical Lesions Mediated by Human Papillomavirus - Ana Carolina Caetano Jesus; Maria Cristina Gonçalves Meniconi; Luciane Kanashiro Galo; Maria Irma Seixas Duarte; Mirian Nacagami Sotto; Carla Pagliari (Indian Journal of Microbiology, 2023)

Dog in sheep’s clothing: livestock depredation by free-ranging dogs may pose new challenges to wolf conservation - Sofia Lino; Mariana Rossa; Joana M. Fernandes; Tânia Barros; Ana Lino; Dário Hipólito; Eduardo Ferreira; Sara C. Aliácar; Duarte Cadete; Carlos Fonseca; Rita T. Torres; Luís M. Rosalino; et al. (European Journal of Wildlife Research, 2023)
Livestock depredation is a common cause of human-carnivore conflicts. In Portugal, free-ranging dogs are increasingly abundant and overlap endangered Iberian wolf territories, with reports of livestock depredation. However, the lack of awareness about dogs’ possible role as predators leads to bias against wolves in cases of damages. Our goal was to assess and compare wolf and free-ranging dog’s diet composition at southern wolf range in Portugal, to offer insights on dogs’ predatory role on livestock and its implications for the conservation of an endangered wolf subpopulation. We assessed diet composition from 107 to 95 genetically confirmed wolf and dog scats, respectively, and complemented the analysis with data from 40 attacks on livestock with successful genetic predator assignment. Scat analysis highlighted goats as the most consumed dog prey in all analysed regions, with lagomorphs, small mammals, and wild boars as second most consumed in each region, respectively. Wolves mainly relied on goats and wild boars in the west, whereas in the central region they mostly fed on birds. The dietary overlap between both canids was very high (Pianka’s index O = 0.93), showing potential for competition. Additionally, we found that dogs were the sole predators detected in most attacks (62%). Our findings highlight dogs’ role as predators of livestock, and possibly also wild species, posing a further challenge to wolf conservation. Alongside adequate husbandry practices, we emphasise the need for a stronger enforcement of the legislation on dog ownership and an effective management of the stray population to reduce human-wolf conflict.

Production of Oligosaccharides from Pine Nut Shells by Autohydrolysis - Ivone Torrado; Ana Dionísio; Maria C. Fernandes; Luísa Bivar Roseiro; Florbela Carvalheiro; Helena Pereira; Luís C. Duarte (BioEnergy Research, 2023)
Pinus pinea nuts are commercial relevant Mediterranean edible forest nuts, with an increasing production and market value, whose industrial processing yields a lignocellulosic by-product, the pine nut shells, currently only used for combustion. Little research has been done on pine nut shells that could support a value-added application for this residue. This work studies for the first time the production of oligosaccharides by autohydrosis, and aims at an integrated upgrade within the biorefinery framework. Autohydrolysis was explored in the temperature range between 150 and 230 °C (corresponding to severity factors 2.13–4.63). Oligosaccharides, mainly xylo-oligosaccharides (95% of the total), were the key soluble products, reaching 28.7 g/100 g of xylan of the feedstock at the optimal conditions (log R 0 4.01). Other products were monosaccharides and phenolic compounds that reached 7.8 and 4.7 g/L, respectively, under the most severe conditions. The stability of the oligosaccharides at different temperatures (room, 37 °C and 100 °C) and pH (between 1 and 11) grant them significant market potential in the food and pharma sectors. The pre-treated pine nut shells by autohydrolysis presented an improved, although low, enzymatic digestibility (14%), and an improved high-heating value, therefore advising their further valorization by thermochemical pathways.

The role of inflammation and antioxidant defenses in the cardiotoxicity of doxorubicin in elderly CD-1 male mice - Ana Reis-Mendes; Mariana Ferreira; José Alberto Duarte; Margarida Duarte-Araújo; Fernando Remião; Félix Carvalho; Emília Sousa; Maria Lourdes Bastos; Vera Marisa Costa (Archives of Toxicology, 2023)
Doxorubicin (DOX) is a potent chemotherapeutic agent used against several cancer types. However, due to its cardiotoxic adverse effects, the use of this drug may be also life-threatening. Although most cancer patients are elderly, they are poorly represented and evaluated in pre-clinical and clinical studies. Considering this, the present work aims to evaluate inflammation and oxidative stress as the main mechanisms of DOX-induced cardiotoxicity, in an innovative approach using an experimental model constituted of elderly animals treated with a clinically relevant human cumulative dose of DOX. Elderly (18–20 months) CD-1 male mice received biweekly DOX administrations, for 3 weeks, to reach a cumulative dose of 9.0 mg/kg. One week (1W) or two months (2 M) after the last DOX administration, the heart was collected to determine both drug’s short and longer cardiac adverse effects. The obtained results showed that DOX causes cardiac histological damage and fibrosis at both time points. In the 1W-DOX group, the number of nuclear factor kappa B (NF-κB) p65 immunopositive cells increased and a trend toward increased NF-κB p65 expression was seen. An increase of inducible nitric oxide synthase (iNOS) and interleukin (IL)-33 and a trend toward increased IL-6 and B-cell lymphoma-2-associated X (Bax) expression were seen after DOX. In the same group, a decrease in IL-1β, p62, and microtubule-associated protein 1A/1B-light chain 3 (LC3)-I, p38 mitogen-activated protein kinase (MAPK) expression was observed. Contrariwise, the animals sacrificed 2 M after DOX showed a significant increase in glutathione peroxidase 1 and Bax expression with persistent cardiac damage and fibrosis, while carbonylated proteins, erythroid-2-related factor 2 (Nrf2), NF-κB p65, myeloperoxidase, LC3-I, and LC3-II expression decreased. In conclusion, our study demonstrated that in an elderly mouse population, DOX induces cardiac inflammation, autophagy, and apoptosis in the heart in the short term. When kept for a longer period, oxidative-stress-linked pathways remained altered, as well as autophagy markers and tissue damage after DOX treatment, emphasizing the need for continuous post-treatment cardiac monitoring.

Trust-based health decision-making recruits the neural interoceptive saliency network which relates to temporal trajectories of Hemoglobin A1C in Diabetes Type 1 - Helena Jorge; Isabel C. Duarte; Miguel Melo; Ana Paula Relvas; Miguel Castelo-Branco (Brain Imaging and Behavior, 2023)
Experimental approaches in neuroeconomics generally involve monetary utility. Utility in the health domain is relevant in diabetes because constant daily life decisions are critical for self-consequential long-term outcomes. We used fMRI to investigate self-consequent decision-making in the health and economic domains in Type 1 Diabetes Mellitus and controls ( N = 50). We focused on two critical phases of decision-making: Investment and Feedback (Positive or Negative). Patients showed larger BOLD activation of limbic, and reward/dopaminergic regions in particular in the health trust game. Importantly, the worse the trajectory of metabolic control (increasing HbA1C), the higher the BOLD activity in regions of the interoceptive saliency network. This was manifested by positive correlations between brain activity during investment in anterior cingulate cortex and insula and HbA1c blood level progression. We conclude that the neural correlates of health-consequent decision-making domain involve limbic and reward related dopaminergic regions in Type 1 Diabetes Mellitus. Furthermore, the temporal trajectory of HbA1C blood levels is correlated with neural risk processing in the saliency network. Evidence for differential risk processing in the health versus the neuroeconomic context, and the discovery of a role for the saliency interoceptive network in metabolic control trajectories suggests a new perspective on the development of personalized interventions.

Uncovering the effects of copper feed supplementation on the selection of copper-tolerant and antibiotic-resistant Enterococcus in poultry production for sustainable environmental practices - Andreia Rebelo; Bárbara Duarte; Ana R. Freitas; Agostinho Almeida; Rui Azevedo; Edgar Pinto; Luísa Peixe; Patrícia Antunes; Carla Novais (Science of The Total Environment, 2023)

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Bento Almeida d’Eça: Hydraulic Agriculture under the umbrella of Engineers in Nineteenth Century Portugal - Ana Duarte Rodrigues; Pier Luigi Pireddu; Patricia Trindade Monteiro (Sustainable Water Resources Management, 2023)
In mid-nineteenth century Portugal, the practice of irrigation was deemed to be completely backwards in comparison with the prevailing European standards. Distant were the times of Al-Andalus, when a so-called green revolution occurred on the Iberian Peninsula. Within this context, Agricultural Hydraulics gained momentum as a scientific field. Although water governance had a long run, the ‘politicisation’ of water issues clearly intensified in the Regeneration political regime. From 1851 onwards, the stability required for national material progress was ensured. The country had been struggling to build roads, railways, telegraphs, ports and, therefore, the Ministry of Public Works was established in 1852 to undertake these architectural and engineering projects. This paper argues that not only due to rivers’ manipulation for agriculture, but also to the rising status of engineers, Agricultural Hydraulics was under the Ministry of Public Works and, consequently, on the sphere of engineers rather than agronomists. Focusing on the making of a military engineer as an expert on Agricultural Hydraulics by sending him abroad and fostering his literary education, this paper reveals how this knowledge was appropriated and transformed into new projects for the Tagus River. Moreover, contrary to recent review that Hydraulic Services were launched in Portugal by 1884, based on the “Plan for Organization of Hydrographic Services on the mainland of Portugal”, this paper highlights the crucial role played by the Portuguese engineer Bento Fortunato Almeida d’Eça through his work as Superintendent of the Tagus River and its Tributaries, twenty years earlier.

Impact of inbreeding and genetic parameter estimates for seminal traits in Lusitano horses - Ana Rita Gonçalves; Luis Telo da Gama; Luis Antunes; Helena Guimarães; Miguel Bliebernicht; José Carlos Duarte; Cristina Cosinha; Bruno Duarte Rego; Pedro Ferro da Costa; Tiago Guimarães; António Rocha; Elisa Bettencourt (Theriogenology, 2023)

Threats to sustainability in face of post-pandemic scenarios and the war in Ukraine - João Pinto da Costa; Ana Luísa Silva; Damià Barcelò; Teresa Rocha-Santos; Armando Duarte (Science of The Total Environment, 2023)

Potential of bioactive molecules from photosynthetic microorganisms on Leishmania spp.: A review - Sabrina Swan Souza da Silva; Alexsandra Frazão de Andrade; Milena de Paiva-Cavalcanti; João Carlos Monteiro de Carvalho; Daniela de Araújo Viana-Marques; Carolina de Albuquerque Lima Duarte; Ana Lúcia Figueiredo Porto; Raquel Pedrosa Bezerra (Algal Research, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Acetaminophen induced antioxidant and detoxification responses in a stygobitic crustacean - Cláudia Duarte; Carlos Gravato; Tiziana Di Lorenzo; Ana Sofia P.S. Reboleira (Environmental Pollution, 2023)

Shading effect and forage production of tropical grasses in Brazilian semi-arid silvopastoral systems - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Ana Clara Rodrigues Cavalcante; Vitor Hugo Maues Macedo; Magno José Duarte Cândido (Agroforestry Systems, 2023)

Streams in the Mediterranean Region are not for mussels: Predicting extinctions and range contractions under future climate change - Janine P. da Silva; Ronaldo Sousa; Duarte Vasconcelos Gonçalves; Rafael Miranda; Joaquim Reis; Amílcar Teixeira; Simone Varandas; Manuel Lopes-Lima; Ana Filipa Filipe (Science of The Total Environment, 2023)

High accumulation of lipofuscin is observed in preantral follicles of adult goat ovaries: Is it a senescence sign? - Marília Lima; Naíza Arcângela Ribeiro de Sá; Marco Aurélio Schiavo Novaes; Gaby Judith Quispe Palomino; Gildas Mbemya Tetaping; César Carneiro Linhares Fernandes; Drielle Neske Garcia; Davide Rondina; Augusto Schneider; José Ricardo Figueiredo; Ana Beatriz Graça Duarte; Ana Paula Ribeiro Rodrigues (Small Ruminant Research, 2023)

Partial characterization of Loxosceles anomala (Mello-Leitão, 1917) venom: A brown spider of potential medical concern - Pamella Peres-Damásio; Rafaela Silva-Magalhães; Ana Luiza Silva-Araújo; Elaine Henriques Teixeira Pereira; Adriano Lima Silveira; Luana Silveira da Rocha Nowicki Varella; Márcia Helena Borges; Carlos Chavez-Olórtegui; Ana Luiza Bittencourt Paiva; Clara Guerra-Duarte (Toxicon, 2023)

Evaluation of the volatiles’ chemical profile and antibacterial activity of Lavandula stoechas L. extracts obtained by supercritical carbon dioxide - Jelena Vladić; Igor Jerković; Sandra Svilović; Valentina Pavić; Kristian Pastor; Alexandre Paiva; Stela Jokić; Silvia Rebocho; Ana Rita Duarte (Sustainable Chemistry and Pharmacy, 2023)

Environmental field conditions and sampling effort affect the molecular identification success of livestock predators - Sofia Lino; Ana Lino; Joana M. Fernandes; Eduardo Ferreira; Carlos Fonseca; Sara Aliácar; Duarte Cadete; Luís M. Rosalino; João Carvalho (Mammalian Biology, 2023)

Endothelial progenitor cell response to a multicomponent exercise training program in adults with cardiovascular risk factors - Suiane Cavalcante; Manuel Teixeira; Marisol Gouveia; Ana Duarte; Miriam Ferreira; Maria I. Simões; Maria Conceição; Mariana Costa; Ilda P. Ribeiro; Ana Cristina Gonçalves; José Oliveira; Fernando Ribeiro (German Journal of Exercise and Sport Research, 2023)

Neutralizing antibodies to bovine and bubaline alphaherpesviruses in water buffaloes (Bubalus bubalis) - Camila Mengue Scheffer; Ana Paula Muterle Varela; Thais Fumaco Teixeira; Candice Schmidt; Samuel Paulo Cibulski; Helton Fernandes dos Santos; Phelipe Magalhães Duarte; Fabricio Souza Campos; Ana Cláudia Franco; Paulo Michel Roehe (Brazilian Journal of Microbiology, 2023)

Internuclear ophthalmoplegia, skew deviation and nystagmus from facial colliculus infarction: small lesion big trouble - Diana Vilares Valente; Tomás Duarte de Almeida; Inês Gil; Hipólito Nzwalo; Ana Catarina Félix (Acta Neurologica Belgica, 2023)

Lifelong exercise training promotes the remodelling of the immune system and prostate signalome in a rat model of prostate carcinogenesis - Elisabete Nascimento-Gonçalves; Fernanda Seixas; Carlos Palmeira; Gabriela Martins; Carolina Fonseca; José Alberto Duarte; Ana I. Faustino-Rocha; Bruno Colaço; Maria João Pires; Maria João Neuparth; Daniel Moreira-Gonçalves; Margarida Fardilha; et al. (GeroScience, 2023)
This work aimed to understand how lifelong exercise training promotes the remodelling of the immune system and prostate signalome in a rat model of PCa. Fifty-five male Wistar rats were divided into four groups: control sedentary, control exercised, induced PCa sedentary and induced PCa exercised. Exercised animals were trained in a treadmill for 53 weeks. Pca induction consisted on the sequential administration of flutamide, N-methyl-N-nitrosourea and testosterone propionate implants. Serum concentrations of C-reactive protein (CRP) and tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) were not different among groups. Peripheral levels of γδ T cells were higher in Pca exercised group than in the PCa sedentary group ( p < 0.05). Exercise training also induced Oestrogen Receptor (ESR1) upregulation and Mitogen-activated Protein Kinase 13 (MAPK13) downregulation, changed the content of the phosphorylated (at Ser-104) form of this receptor (coded by the gene ESR1) and seemed to increase Erα phosphorylation and activity in exercised PCa rats when compared with sedentary PCa rats. Our data highlight the exercise-induced remodelling of peripheral lymphocyte subpopulations and lymphocyte infiltration in prostate tissue. Moreover, exercise training promotes the remodelling prostate signalome in this rat model of prostate carcinogenesis.

Effects of using waste high-density polyethylene on the rheological, mechanical, and thermal performance of asphalt materials - Amanda Jessica Rodrigues da Silva; Adriano Elísio de Figueiredo Lopes Lucena; Osires de Medeiros Melo Neto; Ana Maria Gonçalves Duarte Mendonça; Daniel Beserra Costa; Robson Kel Batista de Lima (Environment, Development and Sustainability, 2023)

Environmental heterogeneity of a tropical river-to-sea continuum and its relationship with structure and phytoplankton dynamics – Lençóis Maranhenses National Park - Quedyane Silva da Cruz; Marco Valério Jansen Cutrim; Taiza Pimentel Santos; Ana Karoline Duarte dos Santos Sá; Lisana Furtado Cavalcanti-Lima (Marine Environmental Research, 2023)

Biological effects of sewage sludge – does its incorporation into agricultural soils in the state of Paraná, Brazil, represent an environmental risk? - Ádila Cristina Krukoski Filipi; Gabrielle Cristina dos Santos Gonçalves Nascimento; Patricia Aline Bressani; Anna Karolina Gomes Oliveira; Diego Espirito Santo; Charla Chaionara Schultz Duarte; Eduardo Michel Vieira Gomes; Paulo Michel Pinheiro Ferreira; Juan Carlos Pokrywiecki; Regiane da Silva Gonzalez; Fernanda Batista de Souza; Elisângela Dusman; et al. (Water, Air, & Soil Pollution, 2023)

A glimpse at an early stage of microbe domestication revealed in the variable genome of Torulaspora delbrueckii , an emergent industrial yeast - Margarida Silva; Ana Pontes; Ricardo Franco‐Duarte; Pedro Soares; José Paulo Sampaio; Maria João Sousa; Patrícia H. Brito (Molecular Ecology, 2023)
Microbe domestication has a major applied relevance but is still poorly understood from an evolutionary perspective. The yeast Torulaspora delbrueckii is gaining importance for biotechnology but little is known about its population structure, variation in gene content or possible domestication routes. Here, we show that T. delbrueckii is composed of five major clades. Among the three European clades, a lineage associated with the wild arboreal niche is sister to the two other lineages that are linked to anthropic environments, one to wine fermentations and the other to diverse sources including dairy products and bread dough (Mix‐Anthropic clade). Using 64 genomes we assembled the pangenome and the variable genome of T. delbrueckii . A comparison with Saccharomyces cerevisiae indicated that the weight of the variable genome in the pangenome of T. delbrueckii is considerably smaller. An association of gene content and ecology supported the hypothesis that the Mix‐Anthropic clade has the most specialized genome and indicated that some of the exclusive genes were implicated in galactose and maltose utilization. More detailed analyses traced the acquisition of a cluster of GAL genes in strains associated with dairy products and the expansion and functional diversification of MAL genes in strains isolated from bread dough. In contrast to S. cerevisiae , domestication in T. delbrueckii is not primarily driven by alcoholic fermentation but rather by adaptation to dairy and bread‐production niches. This study expands our views on the processes of microbe domestication and on the trajectories leading to adaptation to anthropic niches.

Mechanical wounding impacts the growth versus defense balance in tomato (Solanum lycopersicum) - Ana Flavia Aparecida Cunha; Pedro Henrique Duarte Rodrigues; Ana Clara Anghinoni; Vinicius Juliani de Paiva; Daniel Gonçalves da Silva Pinheiro; Marcelo Lattarulo Campos (Plant Science, 2023)

Current knowledge on the presence, biodegradation, and toxicity of discarded face masks in the environment - Ana M. Oliveira; Ana L. Patrício Silva; Amadeu M.V.M. Soares; Damià Barceló; Armando C. Duarte; Teresa Rocha-Santos (Journal of Environmental Chemical Engineering, 2023)

Evaluating the in vitro digestion of lipids rich in medium-chain fatty acids (MCFAs) using dynamic and static protocols - Ericsem Pereira; Jean-Michel Fernandes; Raquel Gonçalves; Ana C. Pinheiro; M. Salomé Duarte; M. Madalena Alves; Antonio J.A. Meirelles; Guilherme J. Maximo; Antonio A. Vicente (Food Chemistry, 2023)

Cryopreservation of mature zygotic embryos, shoot bud regeneration, and field establishment of Pinus elliottii var. elliottii x Pinus caribaea var. hondurensis in vitro-derived plants - Lilian P. E. Ayala; Claudia V. Luna; Elsa A. Brugnoli; Fabiana D. Espasandin; María J. Duarte; Ana M. González; María E. Gauchat; Paloma Moncaleán Guillén; Pedro A. Sansberro (Trees, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Joint species distribution models unveil co‐occurrences between freshwater mussels and their fish hosts - Janine P. da Silva; Duarte Vasconcelos Gonçalves; Aina Garcia‐Raventós; Manuel Lopes‐Lima; Simone Varandas; Elsa Froufe; Amílcar Teixeira; Francis K. C. Hui; Ana Filipa Filipe; Ronaldo Sousa (Journal of Biogeography, 2023)
Aim Freshwater mussels are among the most threatened taxa in the world, partially due to the dependence on fish hosts to complete their life cycle. Knowledge about the role of environmental and biotic drivers in determining mussels' distribution is currently lacking. We aimed to assess the role of environmental and biotic drivers in determining the distribution of mussels and their fish hosts and to test if co‐occurrence patterns were able to identify mussel‐host interactions. Location Douro River basin (Iberian Peninsula). Taxon Four freshwater mussels and ten fish hosts. Methods Joint species distribution models (JSDMs) were fitted to presence‐absence records for mussel and fish assemblages. Variance partitioning among environmental variables and latent variables was conducted to determine the environmental versus biotic drivers of species distributions. Resulting matrices of pairwise species co‐occurrences were used to identify co‐occurrence patterns. Results The distribution of host generalist mussel species was mainly explained by environmental variables related to climate and topography. The distribution of the host specialist Margaritifera margaritifera was mainly explained by land use. Strong positive correlations between mussels and the most relevant fish hosts were consistently captured by JSDMs. Co‐occurrence patterns were mainly explained by residual factors, indicating the potential role of biotic interactions. Main Conclusions Biotic interactions were expected to play an important role in explaining mussels' distribution, but the contribution of this factor was only meaningful for the host specialist M. margaritifera . Correlations between mussels and suitable hosts allowed to infer important fish hosts for freshwater mussels in the Douro River basin from distributional data alone. By finding similarities between the ecological requirements of co‐occurring species, conservation measures can be oriented towards several species, which brings a more holistic perspective to the protection of biodiversity.

Identifying freshwater priority areas for cross-taxa interactions - Joana Garrido Nogueira; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe; Elsa Froufe; Duarte V. Gonçalves; Janine P. da Silva; Ronaldo Sousa; Amílcar Teixeira; Simone Varandas; Virgilio Hermoso (Science of The Total Environment, 2023)

First assessment of leaf lipids and fatty acids as biomarkers of grapevine tolerance/susceptibility to Plasmopara viticola - Ana Rita Cavaco; Gonçalo Laureano; Bernardo Duarte; Jorge Marques da Silva; Carla Gameiro; Jorge Cunha; José Eiras Dias; Ana Rita Matos; Andreia Figueiredo (Physiological and Molecular Plant Pathology, 2023)

Anthocyanin bioaccessibility and anti-inflammatory activity of a grape-based 3D printed food for dysphagia - Alan Giovanini de Oliveira Sartori; Ana Sofia Martelli Chaib Saliba; Bruna Sousa Bitencourt; Jaqueline Souza Guedes; Larissa Catelli Rocha Torres; Severino Matias de Alencar; Pedro Esteves Duarte Augusto (Innovative Food Science & Emerging Technologies, 2023)

Maternal dietary exposure to mycotoxin aflatoxin B1 promotes intestinal immune alterations and microbiota modifications increasing infection susceptibility in mouse offspring - Patricia Bastos-Amador; Elsa Leclerc Duarte; Júlio Torres; Ana Teresa Caldeira; Inês Silva; Cátia Salvador; Ricardo Assunção; Paula Alvito; Manuela Ferreira (Food and Chemical Toxicology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Effects of the addition of fatty acid from soybean oil sludge in recycled asphalt mixtures - Osires de Medeiros Melo Neto; Leda Christiane de Figueiredo Lopes Lucena; Ingridy Minervina Silva; Luciana de Figueiredo Lopes Lucena; Ana Maria Gonçalves Duarte Mendonça; Albaniza Maria da Silva Lopes; Flavia Maria Mendes da Silva; Alex Guedes de Amorim; Hugo Ribeiro de Oliveira Neto (Environmental Science and Pollution Research, 2023)

PM2.5 chemical composition and health risks by inhalation near a chemical complex - Célia Alves; Margarita Evtyugina; Estela Vicente; Ana Vicente; Ismael Casotti Rienda; Ana Sánchez de la Campa; Mário Tomé; Iola Duarte (Journal of Environmental Sciences, 2023)

Assessment of metabolic, mineral, and cytotoxic profile in pineapple leaves of different commercial varieties: A new eco-friendly and inexpensive source of bioactive compounds - Tamyris de Aquino Gondim; Jhonyson Arruda Carvalho Guedes; Maria Francilene Souza Silva; Adenilton Camilo da Silva; Ana Paula Dionísio; Fernanda Vidigal Duarte Souza; Claudia do Ó Pessoa; Gisele Simone Lopes; Guilherme Julião Zocolo (Food Research International, 2023)

Melissa officinalis essential oil as an antimicrobial agent against Listeria monocytogenes in watermelon juice - Filomena Carvalho; Alexandra T. Coimbra; Lúcia Silva; Ana P. Duarte; Susana Ferreira (Food Microbiology, 2023)

Current developments and future perspectives on biotechnology applications of natural deep eutectic systems - Ana Rita Jesus; Alexandre Paiva; Ana Rita C. Duarte (Current Opinion in Green and Sustainable Chemistry, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Uncovering biodegradability and biocompatibility of betaine-based deep eutectic systems - Inês João Ferreira; Alexandre Paiva; Mário Diniz; Ana Rita Duarte (Environmental Science and Pollution Research, 2023)
Deep eutectic systems (DES) have shown increasing popularity in last decade; however, the number of studies on the potential toxicity towards living organisms remains scarce. These studies are of the utmost importance to infer on the claimed non-toxicity and biocompatibility of DES. Most articles published, at this moment, only evaluate the toxicity towards a cell model or in different strains of bacteria. For this purpose, in this work, the effect of two DES (betaine:sorbitol:water 1:1:3 and betaine:glycerol 1:2) and their individual components were evaluated at different concentrations after administered via intraperitoneal injection in zebrafish ( Danio rerio ). The total antioxidant capacity, lipoperoxidation, and the activity of various enzymes that work in different antioxidant pathways (superoxide dismutase, glutathione peroxidase, catalase, and glutathione S-transferase) were assessed. The results show no significant toxicity within the tested concentrations: up to 5000 µM and 3000 µM, for the assays using the system betaine:sorbitol:water 1:1:3 and for betaine:glycerol 1:2, respectively. The toxicity of individual components was studied up to 1000 µM. Based on the encouraging results that have been obtained, it is safe to conclude that these two deep eutectic systems can be used as the new class of environmentally friendly solvents. Graphical Abstract

Colletotrichum karsti causing anthracnose on Dioscorea cayennensis in Brazil - Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Willie Anderson dos Santos Vieira; Ailton Reis; Lisa A. Castlebury; Marcos P. S. Câmara (Journal of Plant Pathology, 2023)

Removing chemical and biological pollutants from swine wastewater through constructed wetlands aiming reclaimed water reuse - Maria L. Bôto; Sofia M. Dias; Rute Duarte Crespo; Ana P. Mucha; C. Marisa R. Almeida (Journal of Environmental Management, 2023)

Wall and roof solutions for a retail building considering cost investment and life cycle approach: A case study in Portugal - Ana Ferreira; Manuel Duarte Pinheiro; Jorge de Brito; Ricardo Mateus; Rita Mendonça (Journal of Cleaner Production, 2023)

Enterococcus spp. from chicken meat collected 20 years apart overcome multiple stresses occurring in the poultry production chain: Antibiotics, copper and acids - Andreia Rebelo; Bárbara Duarte; Carolina Ferreira; Joana Mourão; Sofia Ribeiro; Ana R. Freitas; Teresa M. Coque; Rob Willems; Jukka Corander; Luísa Peixe; Patrícia Antunes; Carla Novais (International Journal of Food Microbiology, 2023)

Characterising the fruit and vegetables consumer ethnocentrism in a southern European Country: An assessment of the reliability and validity of the “CETSCALE” in Portugal - Luis Pedro Miguel; Susana Henriques Marques; Ana Patricia Duarte (Food Quality and Preference, 2023)

Water Intensity Indicators in the Global Retail Sector - Ana Ferreira; Manuel Duarte Pinheiro; Jorge de Brito; Ricardo Mateus; Vitor Sousa (Water Resources Management, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

In silico design and in vitro assessment of anti-Helicobacter pylori compounds as potential small-molecule arginase inhibitors - Ana Thereza Fiori-Duarte; João Paulo de Oliveira Guarnieri; Jessica Rodrigues Pereira de Oliveira Borlot; Marcelo Lancellotti; Ricardo Pereira Rodrigues; Rodrigo Rezende Kitagawa; Daniel Fábio Kawano (Molecular Diversity, 2022)

Analysis of seroprevalence and risk factors for hepatitis E virus (HEV) in donation candidates and blood donors in Northeast Brazil - Gabriel Galindo Cunha; Luan Araújo Bezerra; José Valter Joaquim Silva Júnior; Juliana Prado Gonçales; Ana Cristina Bezerra Montreuil; Maria Rosângela Cunha Duarte Côelho (Brazilian Journal of Microbiology, 2022)

Erysipelas in a stranded common bottlenose dolphin: first report in a South American odontocete - Carlos Sacristán; Ana Carolina Ewbank; Angélica María Sánchez-Sarmiento; Aricia Duarte-Benvenuto; João Carlos Gomes Borges; Vanessa Araújo Rebelo; Josué Díaz-Delgado; Lara Borges Keid; José Luiz Catão-Dias (Brazilian Journal of Microbiology, 2022)

Macronutrients and dissolved iron in a land-ocean approach: Influences of contamination by ore tailings in Southeastern Brazil - Renata Caiado Cagnin; Cybelle Menolli Longhini; Eduardo Schettini Costa; Cesar Alexandro da Silva; Stéfano Zorzal-Almeida; Danniel Mendes; Vânya Márcia Duarte Pasa; Paulo Jorge Sanches Barbeira; Alessandra Delazari-Barroso; Björn Gücker; Iola Gonçalves Boëchat; Ana Teresa Lima; et al. (Frontiers in Marine Science, 2022)
Recently, many dam rupture disasters related to the mining industry have caused significant disruption to ecosystems globally. Contaminants, including nutrients in excess, can be transported from the river watersheds to the ocean in great quantities. In 2015, millions of m 3 of iron ore tailings were released in the Doce River in southeastern Brazil, leading to several damaging effects to the river and marine ecosystem. So far, few studies have integrated the impact of these tailings on the river and the sea simultaneously. This research aims to provide a perspective on the macronutrients and iron concentrations and balance in the Doce River and the adjacent continental shelf, the related abiotic factors and the phytoplankton response under a new steady state of iron enrichment environment. The iron ore tailings increased the concentrations of nutrients in the river and on the continental shelf, especially for dissolved silica and iron. There was also a long-term indirect phosphorus enrichment associated to adsorption/desorption onto Fe-oxides and a nitrogen increase possibly due to N-fixing enhanced by iron. N fixation/remineralization predominates in the river watershed, while in the sea, the hydrodynamics provides nutrients supplied by the river and recycling from sediment resuspension. Nutrient ratios show DIP limitation in the river, while the complex marine environment brings both limitations on DIN, DIP, and DSi, as well as a stoichiometric equilibrium to the dataset. The phytoplankton response to the abiotic factors was more representative in the river watershed than on the continental shelf. This work emphasizes the importance of reporting local data for understanding global land-ocean nutrient fluxes and their potential influence on primary productivity and trophic chain balance.

Forest fire risk indicator (FFRI) based on geoprocessing and multicriteria analysis - Jocy Ana Paixão de Sousa; Elfany Reis do Nascimento Lopes; Miqueias Lima Duarte; Henrique Ewbank; Roberto Wagner Lourenço (Natural Hazards, 2022)

Dietary exposure to low-calorie sweeteners in a sample of Brazilian pregnant women - Larissa Marinho Duarte; Sila Mary Rodrigues Ferreira; Claudia Choma Bettega Almeida; Ana Clara da Fonseca Leitão Duran; Mariana Fagundes Grilo; Mariana de Souza Macedo; Sylvia do Carmo Castro Franceschini; Sandra Patricia Crispim (Food Additives & Contaminants: Part A, 2022)

Castor bean cake for the control of parasites in pasture-finished sheep - Abner José Girão Meneses; Roberto Cláudio Fernandes Franco Pompeu; Hévila Oliveira Salles; Luiz da Silva Vieira; Marcel Teixeira; Marcos Cláudio Pinheiro Rogério; Ana Márjory Paiva Sousa; Patrício Leandro Pereira; Magno José Duarte Cândido (Tropical Animal Health and Production, 2022)

Growth Response, Gas Exchange, and Leaf Anatomy of Handroanthus spp. Seedlings in Mine Tailings Enriched with Nutrient Solution - Ana Lívia Martins Scarpa; Yasmini da Cunha Cruz; Vinícius Politi Duarte; Evaristo Mauro de Castro; Moacir Pasqual; Jean Paulo Vitor de Oliveira; Fabricio José Pereira (Journal of Soil Science and Plant Nutrition, 2022)

Global estimates of the extent and production of macroalgal forests - Carlos M. Duarte; Jean‐Pierre Gattuso; Kasper Hancke; Hege Gundersen; Karen Filbee‐Dexter; Morten F. Pedersen; Jack J. Middelburg; Michael T. Burrows; Kira A. Krumhansl; Thomas Wernberg; Pippa Moore; Albert Pessarrodona; et al. (Global Ecology and Biogeography, 2022)
Aim Macroalgal habitats are believed to be the most extensive and productive of all coastal vegetated ecosystems. In stark contrast to the growing attention on their contribution to carbon export and sequestration, understanding of their global extent and production is limited and these have remained poorly assessed for decades. Here we report a first data‐driven assessment of the global extent and production of macroalgal habitats based on modelled and observed distributions and net primary production (NPP) across habitat types. Location Global coastal ocean. Time period Contemporary. Major taxa studied Macroalgae. Methods Here we apply a comprehensive niche model to generate an improved global map of potential macroalgal distribution, constrained by incident light on the seafloor and substrate type. We compiled areal net primary production (NPP) rates across macroalgal habitats from the literature and combined this with our estimates of the global extent of these habitats to calculate global macroalgal NPP. Results We show that macroalgal forests are a major biome with a global area of 6.06–7.22 million km 2 , dominated by red algae, and NPP of 1.32 Pg C/year, dominated by brown algae. Main conclusions The global macroalgal biome is comparable, in area and NPP, to the Amazon forest, but is globally distributed as a thin strip around shorelines. Macroalgae are expanding in polar, subpolar and tropical areas, where their potential extent is also largest, likely increasing the overall contribution of algal forests to global carbon sequestration.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

REE Anomalies Changes in Bottom Sediments Applied in the Western Equatorial Atlantic Since the Last Interglacial - Thiago A. Sousa; Igor Martins Venancio; Eduardo Duarte Marques; Thiago S. Figueiredo; Rodrigo Azevedo Nascimento; Joseph M. Smoak; Ana Luiza S. Albuquerque; Claudio Morisson Valeriano; Emmanoel Vieira Silva-Filho (Frontiers in Marine Science, 2022)
We reconstruct paleoredox conditions in the Western Equatorial Atlantic (WEA) over the glacial-interglacial cycle (~130 ka) by using new high-resolution REEs data and their anomalies from a marine sediment core (GL-1248) collected from the equatorial margin off the continental shelf of NE Brazil. This approach aims to improve the understanding of the dynamics of paleoclimatic and sedimentary inputs on the coast of northeastern Brazil. Marine sediments were analyzed via Mass Spectrometry (ICP-MS) after total digestion with HF/HNO 3 . REEs proxies are a useful tool in understanding the transport and origin of sediments due to their physicochemical properties. Our data showed the Parnaíba River was the main source of REEs content in the western South Atlantic. Fe minerals (Fe-oxyhydroxides) produced via weathering of continental and tropical soils were the principal REE-carrier phase during transportation and ultimate deposition at core site GL-1248. Several regional climatic factors mainly rainfall changes contributed significantly to continental-REEs erosion of sedimentary layers of the Parnaíba Basin, and transport and deposition of the mobilized REEs from the continent to the study site. Furthermore, changes in the negative Ce-anomaly showed low variation along the core indicating a reduction in deep ocean oxygenation during the interglacial relative to the last glacial period. That variation, probably, was associated with glacial-interglacial variations in sea level with the exposure of the continental shelf. The origin of positive Eu anomalies in siliciclastic sediment, also observed in the core, was explained by preferential retention by feldspars such as plagioclases and potassium feldspars mostly from the assimilation of felspar during fractionation crystallization of felsic magma in the Parnaíba basin since the Last Interglacial.

Sunlight Irradiated Pyrite-Fenton System for Advanced Oxidative Treatment of Textile Dyes Mixture - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Sérgio Gonzaga dos Santos Júnior; Rayssa Kelen de Mendonça Gomes; Alex Leandro Andrade de Lucena; Graziele Elisandra do Nascimento; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Giovanna Machado; Ana Maria Mendonça de Albuquerque Melo; Marta Maria Menezes Bezerra Duarte (Water, Air, & Soil Pollution, 2022)

Optimizing EEG Source Reconstruction with Concurrent fMRI-Derived Spatial Priors - Rodolfo Abreu; Júlia F. Soares; Ana Cláudia Lima; Lívia Sousa; Sónia Batista; Miguel Castelo-Branco; João Valente Duarte (Brain Topography, 2022)
Reconstructing EEG sources involves a complex pipeline, with the inverse problem being the most challenging. Multiple inversion algorithms are being continuously developed, aiming to tackle the non-uniqueness of this problem, which has been shown to be partially circumvented by including prior information in the inverse models. Despite a few efforts, there are still current and persistent controversies regarding the inversion algorithm of choice and the optimal set of spatial priors to be included in the inversion models. The use of simultaneous EEG-fMRI data is one approach to tackle this problem. The spatial resolution of fMRI makes fMRI derived spatial priors very convenient for EEG reconstruction, however, only task activation maps and resting-state networks (RSNs) have been explored so far, overlooking the recent, but already accepted, notion that brain networks exhibit dynamic functional connectivity fluctuations. The lack of a systematic comparison between different source reconstruction algorithms, considering potentially more brain-informative priors such as fMRI, motivates the search for better reconstruction models. Using simultaneous EEG-fMRI data, here we compared four different inversion algorithms (minimum norm, MN; low resolution electromagnetic tomography, LORETA; empirical Bayes beamformer, EBB; and multiple sparse priors, MSP) under a Bayesian framework (as implemented in SPM), each with three different sets of priors consisting of: (1) those specific to the algorithm; (2) those specific to the algorithm plus fMRI task activation maps and RSNs; and (3) those specific to the algorithm plus fMRI task activation maps and RSNs and network modules of task-related dFC states estimated from the dFC fluctuations. The quality of the reconstructed EEG sources was quantified in terms of model-based metrics, namely the expectation of the posterior probability P (model|data) and variance explained of the inversion models, and the overlap/proportion of brain regions known to be involved in the visual perception tasks that the participants were submitted to, and RSN templates, with/within EEG source components. Model-based metrics suggested that model parsimony is preferred, with the combination MSP and priors specific to this algorithm exhibiting the best performance. However, optimal overlap/proportion values were found using EBB and priors specific to this algorithm and fMRI task activation maps and RSNs or MSP and considering all the priors (algorithm priors, fMRI task activation maps and RSNs and dFC state modules), respectively, indicating that fMRI spatial priors, including dFC state modules, might contain useful information to recover EEG source components reflecting neuronal activity of interest. Our main results show that providing fMRI spatial derived priors that reflect the dynamics of the brain might be useful to map neuronal activity more accurately from EEG-fMRI. Furthermore, this work paves the way towards a more informative selection of the optimal EEG source reconstruction approach, which may be critical in future studies.

Trade-Offs and Synergies Between Seagrass Ecosystems and Fishing Activities: A Global Literature Review - Mariana Herrera; Ana Tubío; Pablo Pita; Elsa Vázquez; Celia Olabarria; Carlos M. Duarte; Sebastián Villasante (Frontiers in Marine Science, 2022)
Seagrass ecosystems support human well-being by delivering a wide range of ecosystem services. Particularly important is the significant role they play in food provisioning by supporting fisheries worldwide. Despite their socio-economic importance, it is only recently when they have been considered as important social-ecological systems worldwide. Research focused on the interactions between seagrasses and human activities have been understudied and never addressed from a global approach, even though this knowledge is essential to create relevant policy and management plans, and to promote governance systems, which consider fishers’ needs and rights. Thus, we carried out a global systematic review on trade-offs and/or synergies between seagrasses and fishing activities, aiming to analyse the current state of the art on these interactions, to identify potential gaps in knowledge, and to pinpoint key research priorities. We found a total of 94 publications assessing the relationship between seagrass ecosystems and fisheries, which have tripled between 2001-2021, being most of them empirical studies (90%) with ecological scope (a total of 68). Socioeconomic studies (3%) on the subject were identified as a knowledge gap. Most studies (72%) were carried out in northern hemisphere countries, with an underrepresentation of studies in tropical regions. The studies reporting trade-off (a total of 69) interactions almost tripled those reporting synergies (a total of 31) between seagrass ecosystems and fisheries. Mechanical damage to seagrasses by fishing gear is the main source (51%) of trade-offs, followed by overfishing (28%), while aquaculture cages’ emissions (20%) are also a relevant source of trade-offs. Seafood market demand and conflicts of use were the main drivers for trade-offs. When assessing synergistic interactions, most studies (27 out of 31) reported a larger abundance or recruitment of species with commercial interest mediated by seagrass habitat provision. Globally, seagrass ecosystems are mainly affected by industrial and small-scale fisheries, including aquaculture and shellfisheries, and to a lesser extent, by recreational fisheries. Fisheries management system is not specified in more than half (53) of the reviewed publications, which represents a key knowledge gap with implications for sustainable management. Nevertheless, we document a fast increase in studies covering fishery-seagrass interactions, which, if accompanied by better reporting of the nature of the interactions and the socio-economic context of the fishery, would help improve the sustainable management of both systems.

Posterior reversible encephalopathy syndrome: characteristics, diagnostic accuracy, prognostic factors and long-term outcome in a paediatric population - Catarina Marques Duarte; Ana Sofia Vilardouro; Duarte Rebelo; Sofia Quintas; Francisco Abecasis (Acta Neurologica Belgica, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Modelling Fish Growth with Imperfect Data: The Case of Trachurus picturatus - Ana Neves; Ana Rita Vieira; Vera Sequeira; Elisabete Silva; Frederica Silva; Ana Marta Duarte; Susana Mendes; Rui Ganhão; Carlos Assis; Rui Rebelo; Maria Filomena Magalhães; Maria Manuel Gil; et al. (Fishes, 2022)
Growth modelling is essential to inform fisheries management but is often hampered by sampling biases and imperfect data. Additional methods such as interpolating data through back-calculation may be used to account for sampling bias but are often complex and time-consuming. Here, we present an approach to improve plausibility in growth estimates when small individuals are under-sampled, based on Bayesian fitting growth models using Markov Chain Monte Carlo (MCMC) with informative priors on growth parameters. Focusing on the blue jack mackerel, Trachurus picturatus, which is an important commercial fish in the southern northeast Atlantic, this Bayesian approach was evaluated in relation to standard growth model fitting methods, using both direct readings and back-calculation data. Matched growth parameter estimates were obtained with the von Bertalanffy growth function applied to back-calculated length at age and the Bayesian fitting, using MCMC to direct age readings, with both outperforming all other methods assessed. These results indicate that Bayesian inference may be a powerful addition in growth modelling using imperfect data and should be considered further in age and growth studies, provided relevant biological information can be gathered and included in the analyses.

Cardiotoxicity of cyclophosphamide’s metabolites: an in vitro metabolomics approach in AC16 human cardiomyocytes - Flávio Dionísio; Ana Margarida Araújo; Margarida Duarte-Araújo; Maria de Lourdes Bastos; Paula Guedes de Pinho; Félix Carvalho; Vera Marisa Costa (Archives of Toxicology, 2022)

Constructed Wetlands in the Production of Crimson Fountain Grass Flower Stems - Iracema Clara Alves Luz; Antonio Rodrigues da Cunha Neto; Ana Flávia Santos Rabelo de Melo; Michele Valquíria dos Reis; Fátima Resende Luiz Fia; Mateus Pimentel de Matos; Patrícia Duarte de Oliveira Paiva (Water, Air, & Soil Pollution, 2022)

Transposable elements expression in Rhinella marina (cane toad) specimens submitted to immune and stress challenge - Adriana Ludwig; Michelle Orane Schemberger; Camilla Borges Gazolla; Joana de Moura Gama; Iraine Duarte; Ana Luisa Kalb Lopes; Carolina Mathias; Desirrê Alexia Lourenço Petters-Vandresen; Michelle Louise Zattera; Daniel Pacheco Bruschi (Genetica, 2021)

Self-shading effect in the growth, photosynthesis and anatomy of Typha domingensis Pers. - Ana Lívia Martins Scarpa; Yasmini da Cunha Cruz; Marcio Paulo Pereira; Evaristo Mauro de Castro; Marcelo Polo; Vinícius Politi Duarte; Fabricio José Pereira (Brazilian Journal of Botany, 2021)

Novel alphaherpesvirus in a wild South American sea lion (Otaria byronia) with pulmonary tuberculosis - Carlos Sacristán; Samira Costa-Silva; Laura Reisfeld; Pedro Enrique Navas-Suárez; Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Natália Coelho Couto de Azevedo Fernandes; Rodrigo Albergaria Ressio; Marzia Antonelli; Janaina Rocha Lorenço; Cíntia Maria Favero; Juliana Marigo; et al. (Brazilian Journal of Microbiology, 2021)

Pursuing Multiple Biomarkers for Early Idiopathic Parkinson’s Disease Diagnosis - Yareth Gopar-Cuevas; Ana P. Duarte-Jurado; Rosa N. Diaz-Perez; Odila Saucedo-Cardenas; Maria J. Loera-Arias; Roberto Montes-de-Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2021)

Pollen morphology of Senegalia Raf. species and related genera (Leguminosae: Caesalpinioideae: mimosoid clade) - Ana Flávia Trabuco Duarte; Pétala Gomes Ribeiro; André Luiz da Costa Moreira; Luciano Paganucci de Queiroz; Francisco de Assis Ribeiro dos Santos (Palynology, 2021)

Enhancing knowledge on low‐value fishing species: the distinct reproductive strategy of two gurnard species - Ana Neves; Inês Sousa; Vera Sequeira; Ana Rita Vieira; Elisabete Silva; Frederica Silva; Ana Marta Duarte; Susana Mendes; Rui Ganhão; Carlos Assis; Rui Rebelo; Maria Filomena Magalhães; et al. (Journal of Fish Biology, 2021)
The depletion and overexploitation of several fish stock demands for a valorisation of non‐target and discarded species. Nonetheless, such species are often poorly studied, and information on their biological parameters must be gathered for effective population management. For 1 year, the reproductive strategy of the piper gurnard Trigla lyra and the red gurnard Chelidonichthys cuculus was studied by monthly samples obtained from commercial boats operating on western Portuguese coast. Both species showed a biased sex ratio towards females, especially for larger length classes. Length at first maturity could be estimated only for red gurnard (22.1 and 19.9 cm for females and males, respectively) because all piper gurnard individuals caught were mature. Piper gurnard showed determinate fecundity and a short spawning season, from November to February with a peak in January, whereas red gurnard showed indeterminate fecundity and a wide spawning season, from late December to May. The relative annual fecundity estimated for red gurnard (1893 ± 728 oocytes × g −1 eviscerated weight [EW]) was higher than the one estimated for piper gurnard (1018 ± 250 oocytes×g −1 EW). Although important information for understanding the species dynamics is presented in this study, additional information on other life‐history parameters and of species landings is required.

Preparation of Activated Carbon from Sugarcane Bagasse and Removal of Color and Organic Matter from Real Textile Wastewater - Wiviane Kássia Oliveira Correia da Costa; Sávia Gavazza; Marta Maria Menezes Bezerra Duarte; Sueny Kêlia Barbosa Freitas; Nattany Tayany Gomes de Paula; Ana Paula Silveira Paim (Water, Air, & Soil Pollution, 2021)

The role of renin angiotensin system in the pathophysiology of rheumatoid arthritis - Fernanda Rocha Chaves Moreira; Tiago Almeida de Oliveira; Nádia Eliza Ramos; Maria Augusta Duarte Abreu; Ana Cristina Simões e Silva (Molecular Biology Reports, 2021)

Facies types and depositional cyclicity of a Toarcian–Aalenian(?) carbonate-siliciclastic mixed succession (Cabo Carvoeiro Formation) in the Lusitanian Basin, Portugal - João Barata; Luís V. Duarte; Ana C. Azerêdo (Journal of Iberian Geology, 2021)

Plant growth–promoting traits of yeasts isolated from the tank bromeliad Vriesea minarum L.B. Smith and the effectiveness of Carlosrosaea vrieseae for promoting bromeliad growth - Andréa R. Marques; Alessandra A. Resende; Fátima C. O. Gomes; Ana Raquel O. Santos; Carlos A. Rosa; Alexandre A. Duarte; José Pires de Lemos-Filho; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2021)

Ecoengineering Solutions for the Impairment of Spreading and Growth of Invasive Spartina patens in Mediterranean Salt Marshes - Ricardo Cruz de Carvalho; Eduardo Feijão; Irina Duarte; Vanessa Pinto; Marisa Silva; Ana Rita Matos; Anabela Bernardes da Silva; Isabel Caçador; Patrick Reis-Santos; Vanessa F. Fonseca; Bernardo Duarte (Frontiers in Marine Science, 2021)
The invasion of natural communities by non-indigenous species represents one of the most serious threats to biodiversity. Understanding the ecophysiology of invasive species can provide insights into potential physiological handicaps relative to native species. By doing so, we can leverage the development of ecoengineering solutions for the removal of non-indigenous species, preferably using non-chemical methods. Spartina patens is a known invasive species of cordgrass aggressively proliferating in Mediterranean salt marshes, producing impenetrable monospecific stands. As its occurrence is delimited by the upper high tide water level, we hypothesized that S. patens is intolerant to waterlogging. Therefore, we developed a field experiment where strands of S. patens were kept waterlogged over the entire tidal cycle for 30 days. At the end of the experimental period, plants in the trial plots exhibited severe stress symptoms at different physiological levels compared with control plots (no intervention). At the photobiological level, intervened plants exhibited lower efficiency in producing chemical energy from light, whilst at the biochemical level waterlogging impaired the antioxidant system and increased lipid peroxidation products. Furthermore, the application of chlorophyll a pulse amplitude modulated (PAM) fluorometry, a non-invasive technique, allowed us to evaluate the effectiveness of the implemented measures, being the tool that provided the best separation between the control and intervened population. Considering the physiological traits observed here, ecoengineering solutions based on increased waterlogging of S. patens stands, can be a low-cost and efficient measure to reduce the spreading and growth of this invasive species in the Mediterranean and other salt marshes worldwide with little disturbance.

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Characterization of Sweet Sorghum Genotypes Based on Agro-industrial Performance and Fermentation Potential - Talieisse Gomes Fagundes; Gabrielle Maria Romeiro Lombardi; Ana Cláudia Alencar Lopes; Cláudio Carlos Fernandes Filho; Lucas Silveira Lopes; Rafael Augusto da Costa Parrella; Whasley Ferreira Duarte; José Airton Rodrigues Nunes (Sugar Tech, 2021)

Colletotrichum gloeosporioides sensu lato associated with anthracnose in Bauhinia forficata - Francisco Jorge Carlos de Souza Junior; Willie Anderson dos Santos Vieira; Josiene Silva Veloso; Ingrid Gomes Duarte; Ana Gabriele Gurgel Amaral; Delson Laranjeira; Valdir De Queiroz Balbino; Vinson P. Doyle; Marcos Paz Saraiva Câmara (European Journal of Plant Pathology, 2021)

[10]-Gingerol-Loaded Nanoemulsion and its Biological Effects on Triple-Negative Breast Cancer Cells - Ideli Zanesco-Fontes; Ana Carolina Lopes Silva; Patrícia Bento da Silva; Jonatas Lobato Duarte; Leonardo Delello Di Filippo; Marlus Chorilli; Marcia Regina Cominetti; Ana Carolina Baptista Moreno Martin (AAPS PharmSciTech, 2021)

Commercial raw materials from algaculture and natural stocks of Ulva spp. - Ana Carolina Calheiros; Lucas Pedra Maravilha Sales; Annibal Duarte Pereira Netto; Diana Negrão Cavalcanti; Beatriz Castelar; Renata Perpetuo Reis (Journal of Applied Phycology, 2021)

Case report of respiratory aspergillosis and candidiasis in wild Magellanic penguins (Spheniscus magellanicus), Brazil - Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Roberta Zamana-Ramblas; Pedro Enrique Navas-Suárez; Marco Aurélio Gattamorta; Priscilla Carla dos Santos-Costa; José Luiz Catão-Dias; Carlos Sacristán (Brazilian Journal of Microbiology, 2021)

Baseline Study of Trace Element Concentrations in Sediments of the Intertidal Zone of Amazonian Oceanic Beaches - Jéssica C. E. Vilhena; Ana Amorim; Lourenço Ribeiro; Bernardo Duarte; Maíra Pombo (Frontiers in Marine Science, 2021)
Analyzing the presence and quantifying trace elements is of paramount importance to understand natural environmental processes and monitor the degree of anthropogenic disturbance to mitigate impacts already caused. Here, we aimed to establish a baseline of the trace elements profile and concentrations in sandy sediments of intertidal areas of three Amazonian beaches (Brazil). For each beach, sediments were collected from three different sectors (south, center, and north) and five shoreline distance levels (from the high- to the low-water mark), totalizing 15 samples per beach. The concentration of the different trace elements (Mg, Al, P, S, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Br, Rb, Sr, Y, Zr, Cd, Sn, I, Hg, and Pb) was determined by Total reflection X-ray Fluorescence spectrometry. Sediment was also characterized for its grain size, organic matter, and pH. To assess possible enrichment due to anthropogenic activities we compared trace element levels with the values for the Earth’s crust and calculated pollution indexes: geoaccumulation index (Igeo), ecological risk index (RI), contamination factor (CF), pollution load index (PLI), and sediment quality guideline (SQG), threshold effects level (TEL) and probable effects level (PEL). Individual trace metal concentrations did not vary significantly between beaches, sectors, or sample levels, evidencing a homogeneity of trace elements composition and concentrations across this environment. Igeo indicated 62.2% of the sampling stations uncontaminated, 20.0% from uncontaminated to moderately contaminated, and 4.44% (two sampling stations) strongly contaminated, the same two areas classified as high ecological risk by RI. Most of the sampling points presented low CF. Cadmium and Hg were the only elements that showed moderate to very high values of CF. According to the SQGs, 77.7 and 8.8% of the sampling points presented values above the moderate threshold effect level (SQG-TEL) and probable effect level (SQG-PEL), respectively. All points were classified as non-polluted according to the PLI. Our results show that the three beaches present safe levels of almost of the elements demonstrating the good state of preservation. Most of the indexes classified the sampling points as non-polluted, except for Cd and Hg in a few specific sampling points.

The Choroid Plexus Is an Alternative Source of Prolactin to the Rat Brain - Ana R. Costa-Brito; Telma Quintela; Isabel Gonçalves; Ana C. Duarte; Ana R. Costa; Fernando A. Arosa; José E. Cavaco; Manuel C. Lemos; Cecília R. A. Santos (Molecular Neurobiology, 2021)

Recent genetic advances on boar taint reduction as an alternative to castration: a review - Darlene Ana Souza Duarte; Martine Schroyen; Rodrigo Reis Mota; Sylvie Vanderick; Nicolas Gengler (Journal of Applied Genetics, 2021)
Boar taint is an unpleasant odor in male pig meat, mainly caused by androstenone, skatole, and indole, which are deposited in the fat tissue. Piglet castration is the most common practice to prevent boar taint. However, castration is likely to be banished in a few years due to animal welfare concerns. Alternatives to castration, such as genetic selection, have been assessed. Androstenone and skatole have moderate to high heritability, which makes it feasible to select against these compounds. This review presents the latest results obtained on genetic selection against boar taint, on correlation with other traits, on differences in breeds, and on candidate genes related to boar taint. QTLs for androstenone and skatole have been reported mainly on chromosomes 6, 7, and 14. These chromosomes were reported to contain genes responsible for synthesis and degradation of androstenone and skatole. A myriad of work has been done to find markers or genes that can be used to select animals with lower boar taint. The selection against boar taint could decrease performance of some reproduction traits. However, a favorable response on production traits has been observed by selecting against boar taint. Selection results have shown that it is possible to reduce boar taint in few generations. In addition, modifications in diet and environment conditions could be associated with genetic selection to reduce boar taint. Nevertheless, costs to measure and select against boar taint should be rewarded with incentives from the market; otherwise, it would be difficult to implement genetic selection.

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

In vivo toxicometabolomics reveals multi-organ and urine metabolic changes in mice upon acute exposure to human-relevant doses of 3,4-methylenedioxypyrovalerone (MDPV) - Ana Margarida Araújo; Márcia Carvalho; Vera Marisa Costa; José Alberto Duarte; Ricardo Jorge Dinis-Oliveira; Maria de Lourdes Bastos; Paula Guedes de Pinho; Félix Carvalho (Archives of Toxicology, 2021)

Toxicity Going Nano: Ionic Versus Engineered Cu Nanoparticles Impacts on the Physiological Fitness of the Model Diatom Phaeodactylum tricornutum - Marco Franzitta; Eduardo Feijão; Maria Teresa Cabrita; Carla Gameiro; Ana Rita Matos; João Carlos Marques; Johannes W. Goessling; Patrick Reis-Santos; Vanessa F. Fonseca; Carlo Pretti; Isabel Caçador; Bernardo Duarte (Frontiers in Marine Science, 2020)
Increasing input of Metal Engineered Nano Particles (MeENPs) in marine ecosystems has raised concerns about their potential toxicity on phytoplankton. Given the lack of knowledge on MeENPs impact on these important primary producers, the effects of Copper Oxide (CuO) ENPs on growth, physiology, pigment profiles, fatty acid (FA) metabolism, and oxidative stress were investigated in the model diatom Pheodactylum tricornutum , to provide suitable biomarkers of CuO ENP exposure versus its ionic counterpart. Diatom growth was inhibited by CuO ENPs but not Ionic Cu, suggesting CuO ENP cytotoxicity. Pulse Modulated Amplitude (PAM) phenotyping evidenced a decrease in the electron transport energy flux, pointing to a reduction in chemical energy generation following CuO ENPs exposure, as well as an increase in the content of the non-functional Cu-substituted chlorophyll a (CuChl a ). A significant decrease in eicosapentaenoic acid (C20:5) associated with a significant rise in thylakoid membranes FAs reflected the activation of counteractive measures to photosynthetic impairment. Significant increase in the omega 6/omega 3 ratio, underline expectable negative repercussions to marine food webs. Increased thiobarbituric acid reactive substances reflected heightened oxidative stress by CuO ENP. Enhanced Glutathione Reductase and Ascorbate Peroxidase activity were also more evident for CuO ENPs than ionic Cu. Overall, observed molecular changes highlighted a battery of possible suitable biomarkers to efficiently determine the harmful effects of CuO ENPs. The results suggest that the occurrence and contamination of these new forms of metal contaminants can impose added stress to the marine diatom community, which could have significant impacts on marine ecosystems, namely through a reduction of the primary productivity, oxygen production and omega 6 production, all essential to sustain heterotrophic marine life.

Background concentrations and quality reference values for potentially toxic elements in soils of Piauí state, Brazil - Cácio Luiz Boechat; Lizandra de Sousa Luz Duarte; Antonny Francisco Sampaio de Sena; Clistenes Williams Araujo do Nascimento; Ygor Jacques Agra Bezerra da Silva; Yuri Jacques Agra Bezerra da Silva; Ana Clecia Campos Brito; Paloma Cunha Saraiva (Environmental Monitoring and Assessment, 2020)

Evaluation of BOX-PCR and REP-PCR as Molecular Typing Tools for Antarctic Streptomyces - Marcela Proença Borba; Ana Elisa Ballarini; Joao Paulo Duarte Witusk; Paris Lavin; Sueli Van Der Sand (Current Microbiology, 2020)

The Impact of Science-Unbased Measures Against COVID-19 in Clinical Decision-Making Process - João Vitor Cândido Pimentel; Thaíse Duarte Onofre Sabiá e Silva; Ana Beatriz Tavares Filgueiras; Modesto Leite Rolim Neto (AAPS PharmSciTech, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Antimicrobial Activity of Schinopsis brasiliensis Engler Extract-Loaded Chitosan Microparticles in Oral Infectious Disease - Pedro Henrique Sette-de-Souza; Cleildo Pereira de Santana; Lucas Amaral-Machado; Marta Cristina Teixeira Duarte; Francinalva Dantas de Medeiros; Germano Veras; Ana Cláudia Dantas de Medeiros (AAPS PharmSciTech, 2020)

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Phytochemical Characterization, Bioactivities Evaluation and Synergistic Effect of Arbutus unedo and Crataegus monogyna Extracts with Amphotericin B - Alexandra T. Coimbra; Ângelo F. S. Luís; Maria T. Batista; Susana M. P. Ferreira; Ana Paula C. Duarte (Current Microbiology, 2020)

Multiple and flexible roles of facultative anaerobic bacteria in microaerophilic oleate degradation - M. Salomé Duarte; Andreia F. Salvador; Ana J. Cavaleiro; Alfons J. M. Stams; M. Alcina Pereira; M. Madalena Alves (Environmental Microbiology, 2020)
Summary Anaerobic degradation of long‐chain fatty acids (LCFA) involves syntrophic bacteria and methanogens, but facultative anaerobic bacteria (FAB) might have a relevant role as well. Here we investigated oleate degradation by a syntrophic synthetic co‐culture of Syntrophomonas zehnderi (Sz) and Methanobacterium formicicum (Mf) and FAB (two oleate‐degrading Pseudomonas spp. I1 + I2). Sz + Mf were first cultivated in a continuous bioreactor under strict anaerobic conditions. Thereafter, I1 + I2 were inoculated and microaerophilic conditions were provided. Methane and acetate were the main degradation products by Sz + Mf in anaerobiosis and by Sz + Mf + I1 + I2 in microaerophilic conditions. However, acetate production from oleate was higher in microaerophilic conditions (5% O 2 ) with the four microorganisms together (0.41 ± 0.07 mmol day −1 ) than in anaerobiosis with Sz + Mf (0.23 ± 0.05 mmol day −1 ). Oleate degradation in batch assays was faster by Sz + Mf + I1 + I2 (under microaerophilic conditions) than by Sz + Mf alone (under strict anaerobic conditions). I1 + I2 were able to grow with oleate and with intermediates of oleate degradation (hydrogen, acetate and formate). This work highlights the importance of FAB, particularly Pseudomonas sp., in anaerobic reactors treating oleate‐based wastewater, because they accelerate oleate conversion to methane, by protecting strict anaerobes from oxygen toxicity and also by acting as alternative hydrogen/formate and acetate scavengers for LCFA‐degrading anaerobes.

Assessing the Distribution and Concentration of Heavy Metals in Soils of an Agricultural Frontier in the Brazilian Cerrado - Ana Clecia Campos Brito; Cácio Luiz Boechat; Antonny Francisco Sampaio de Sena; Lizandra de Sousa Luz Duarte; Clistenes Williams Araujo do Nascimento; Yuri Jacques Agra Bezerra da Silva; Ygor Jacques Agra Bezerra da Silva; Paloma Cunha Saraiva (Water, Air, & Soil Pollution, 2020)

The big picture of field hydrology studies in Brazil - Davi C. D. Melo; Jamil A. A. Anache; Cristiano das N. Almeida; Jaqueline V. Coutinho; Geraldo M. Ramos Filho; Lívia M. P. Rosalem; Natália S. Pelinson; Guilherme L. R. A. Ferreira; Dimaghi Schwamback; Kalyl G. Calixto; João P. G. Siqueira; Jean C. Duarte-Carvajalino; et al. (Hydrological Sciences Journal, 2020)

The Impact of Water from Sand Pit Lakes on Plant Growth, Soil, and Leachate - Fernanda Figueiredo Granja Dorilêo Leite; Guilherme Kangussu Donagemma; Paulo César Teixeira; Raquel Andrade Donagemma; Ana Carolina Barbosa do Canto; Fabiano de Carvalho Balieiro; Gabriel Souza Martins; Leonardo Duarte Batista da Silva (Water, Air, & Soil Pollution, 2020)

The Effect of Tailored Cognitive-Behavioral Therapy for Insomnia on Brain’s Resting-State Networks - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; José Moutinho dos Santos; Isabel Catarina Duarte; Gina Caetano; Miguel Castelo-Branco (Sleep and Vigilance, 2020)

Does Cognitive–Behavioral Therapy for Insomnia Change the Brain? A Case Series Study - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; José Moutinho dos Santos; Isabel Catarina Duarte; Gina Caetano; Miguel Castelo-Branco (Sleep and Vigilance, 2020)

Validated spectrophotometric method for quantification of total triterpenes in plant matrices - Alessandra Moraes Pedrosa; Whocely Victor de Castro; Ana Hortência Fonseca Castro; Joaquim M. Duarte-Almeida (DARU Journal of Pharmaceutical Sciences, 2020)

Comparative phylogeography of two free‐living cosmopolitan cyanobacteria: Insights on biogeographic and latitudinal distribution - Karine F. Ribeiro; Ana P. Ferrero; Leandro Duarte; Andreia C. Turchetto‐Zolet; Luciane O. Crossetti (Journal of Biogeography, 2020)
Aim Free‐living bacteria have long been assumed to have little biogeographic signature because of their high potential for passive dispersal. Raphidiopsis raciborskii and Microcystis aeruginosa are free‐living cosmopolitan cyanobacteria with a probable tropical origin, that frequently form toxic blooms and are considered invasive species in middle latitudes. Despite these similarities, their phylogeographic patterns have seldom been directly compared. Our aim was to reconstruct the phylogeographic histories of R. raciborskii and M. aeruginosa , in order to explore whether their current distributions could be attributed to the same biogeographic events. Location Global. Taxa Raphidiopsis raciborskii (Nostocales) and Microcystis aeruginosa (Chroococcales). Methods The phylogeography of these species was studied based on global genetic diversity patterns from a dataset of worldwide 16S rRNA gene sequences. Genetic diversity indices were measured globally and by latitude. Analyses based on distance matrices were performed to evaluate the correlation between genetic divergence, geographic distance and climatic conditions. Demographic history was investigated through neutrality tests and Bayesian Skyline Plot analysis. Results For both species, the genetic diversity is highest in tropical latitudes, and the data provided evidence of recent population expansions (in the last 2,500 years). R. raciborskii showed much lower genetic diversity than M. aeruginosa . A significant phylogeographic structure was found for R. raciborskii but not for M. aeruginosa . Climatic conditions had a significant influence on the genetic structure of both species, but this influence was stronger and varied according to latitude only for R. raciborskii . Main Conclusions Supporting the hypothesis of a tropical origin and recent dispersal to temperate habitats, both species had higher genetic diversity in tropical latitudes and showed evidence of recent population expansions. R. raciborskii populations showed a significant decline in genetic similarity with increasing geographic distance, indicating an interaction between drift and some dispersal limitation on its phylogeography. In contrast, M. aeruginosa seemed to have a high frequency of intercontinental dispersal. Finally, the particularities of each species, such as the ability to form akinetes in R. raciborskii and high genome plasticity and niche specialization in M. aeruginosa , may be associated with the lower genetic diversity of R. raciborskii when compared to M. aeruginosa .

The effect of different grazing heights on carcass and meat quality characteristics of Nellore cattle fattened in pastures of Convert grass - Thiago Trento Biserra; Ulysses Cecato; Sandra Galbeiro; Ana Maria Bridi; Henrique Jorge Fernandes; Camila Fernandes Domingues Duarte; Diogo Rodrigues Da Silva; João Vitor Rosa Vicente; Camila Piechnicki Rogel (Tropical Animal Health and Production, 2020)

Characterization and expression analysis of P5CS (Δ1-pyrroline-5-carboxylate synthase) gene in two distinct populations of the Atlantic Forest native species Eugenia uniflora L. - Débora Bublitz Anton; Frank Lino Guzman; Nicole Moreira Vetö; Felipe Augusto Krause; Franceli Rodrigues Kulcheski; Ana Paula Durand Coelho; Guilherme Leitão Duarte; Rogério Margis; Lúcia Rebello Dillenburg; Andreia Carina Turchetto-Zolet (Molecular Biology Reports, 2020)

Detection of Zika virus in paired urine and amniotic fluid samples from symptomatic and asymptomatic women and their babies during a disease outbreak: association with neurological symptoms in newborns - Danila Vedovello; Steven S. Witkin; Andrea Cristina Botelho Silva; Thamirys Cosmo Gillo Fajardo; Alexandra Siqueira Mello; Ana Paula Antunes Pascalicchio Bertozzi; Alify Bertoldo da Silva; Nemésio Florence Vieira Filho; Maria Manoela Duarte Rodrigues; Rosa Estela Gazeta; Antônio Fernandes Moron; Stéphanno Gomes Pereira Sarmento; et al. (Journal of NeuroVirology, 2020)
Paired maternal and newborn urine and amniotic fluid from 138 subjects collected during a Zika virus (ZIKV) outbreak was analyzed for ZIKV by gene amplification (RT-qPCR), and the findings were correlated with clinical symptoms and neurological anomalies in the babies. ZIKV was detected in 1 of 9 symptomatic women (11.1%) and in 19 of 129 asymptomatic women (14.7%). Neurological manifestations were present in 19 babies (13.7%), 10 of 20 (50%) positive and 9 of 119 (7.6%) negative ( p < 0.001) for ZIKV. Twelve (8.6%) urines collected during gestation were ZIKV-positive; only 2 remained positive for ZIKV postpartum. Six (4.1%) newborn urines collected within 1 day of delivery were ZIKV-positive cases. In 3 of these cases, ZIKV was detected in mother’s urine pre- and postpartum and in both mother’s urine and babies’ urine. Four of the amniotic fluid samples (2.9%) were ZIKV-positive. Among ZIKV-negative babies with neurological sequel, 87.5% were female; in contrast, 72.7% ZIKV-positive babies with neurological abnormalities were male ( p = 0.019). We conclude that during a ZIKV outbreak, clinical symptoms and ZIKV detection in biological fluids are poor predictors of infection and adverse neurologic sequel in newborns.

Arsenic in rice and rice products in Northwestern Mexico and health risk assessment - Leticia García-Rico; Martha Patricia Valenzuela-Rodríguez; María Mercedes Meza-Montenegro; Ana Lilia Lopez-Duarte (Food Additives & Contaminants Part B-Surveillance, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Production and Characterization of a New Sweet Sorghum Distilled Beverage - Ana Cláudia Alencar Lopes; Zlatina Genisheva; José Airton Rodrigues Nunes; Whasley Ferreira Duarte (Sugar Tech, 2019)

Autophagy Stimulation Decreases Dopaminergic Neuronal Death Mediated by Oxidative Stress - Marcela J. Ramirez-Moreno; Ana P. Duarte-Jurado; Yareth Gopar-Cuevas; Alfredo Gonzalez-Alcocer; Maria J. Loera-Arias; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2019)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

A blueprint of septin expression in human tissues - Luíza Zuvanov; Diogo Maciel Duarte Mota; Ana P. U. Araujo; Ricardo DeMarco (Functional & Integrative Genomics, 2019)

Spanish list of potentially inappropriate drugs in the elderly (ES-PIA project) - Magali Gonzalez-Colaço Harmand; Ana María Aldea-Perona; Carlos Boada-Fernández del Campo; Almudena Areosa-Sastre; Consuelo Rodríguez-Jiménez; Marcelino García Sánchez-Colomer; Eduardo Fernández Quintana; Mercedes Plasencia-Nuñez; Paula Masiero-Aparicio; Candelaria Grillo-Grillo; Andrés Orellana-Mobilli; Mar García Sáiz; et al. (European Journal of Clinical Pharmacology, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

Birth defects surveillance: experiences in Argentina and Colombia - Boris Groisman; Rosa Liascovich; María Paz Bidondo; Pablo Barbero; Santiago Duarte; Ana Laura Tellechea; Jorge Holguín; Catherine Rodríguez; Paula Hurtado-Villa; Natalia Caicedo; Gabriela Botta; Ignacio Zarante (Journal of Community Genetics, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Distillery Residues from Cistus ladanifer (Rockrose) as Feedstock for the Production of Added-Value Phenolic Compounds and Hemicellulosic Oligosaccharides - Júnia Alves-Ferreira; Luís C. Duarte; Ana Lourenço; Luísa B. Roseiro; Maria C. Fernandes; Helena Pereira; Florbela Carvalheiro (BioEnergy Research, 2019)

Biosynthesis and bioactivity of Cynara cardunculus L. guaianolides and hydroxycinnamic acids: a genomic, biochemical and health-promoting perspective - Patrícia A. B. Ramos; Ana M. Ferro; M. Margarida Oliveira; Sónia Gonçalves; Carmen S. R. Freire; Armando J. D. Silvestre; Maria F. Duarte (Phytochemistry Reviews, 2019)

Biotechnological tools for the effective management of plastics in the environment - Ana Paço; Jéssica Jacinto; João Pinto da Costa; Patrícia S. M. Santos; Rui Vitorino; Armando C. Duarte; Teresa Rocha-Santos (Critical Reviews in Environmental Science and Technology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

A biogeographical analysis using artisanal dredging fisheries discards of the northern Alboran Sea - Javier Urra Recuero; Pablo Marina Ureña; Alba Rojas García; Estefanía León Duarte; Helena Gallardo Roldán; Blanca Orue Montaner; Matias Lozano; José Miguel Serna; Ana Garrido Diaz; Alejandro Ibañez Yuste; Alejandro Terrón Sigler; Jorge Baro Domíngez; et al. (Frontiers in Marine Science, 2019)

Species gap analysis in DNA barcode reference libraries of marine non-indigenous species in the Azores archipelago - Sofia Duarte; Manuela Parente; Ana Costa; Filipe Costa (Frontiers in Marine Science, 2019)

Photo-Assisted Degradation, Toxicological Assessment, and Modeling Using Artificial Neural Networks of Reactive Gray BF-2R Dye - Graziele Elisandra do Nascimento; Daniella Carla Napoleão; Polyana Karynne de Aguiar Silva; Rayany Magali da Rocha Santana; Ana Maria Ribeiro Bastos; Léa Elias Mendes Carneiro Zaidan; Maiara Celine de Moura; Luana Cassandra Breitenbach Barroso Coelho; Marta Maria Menezes Bezerra Duarte (Water, Air, & Soil Pollution, 2018)

Prevalence of naturally occurring amino acid substitutions associated with resistance to hepatitis C virus NS3/NS4A protease inhibitors in São Paulo state - Regina Célia Moreira; Ana Paula de Torres Santos; Gaspar Lisboa-Neto; Maria Cássia Jacintho Mendes-Corrêa; Marcilio Figueiredo Lemos; Fernanda Mello Malta; Rúbia Anita Ferraz Santana; Gregório Tadeu Fernando Dastoli; Vanessa Fusco Duarte de Castro; João Renato Rebello Pinho (Archives of Virology, 2018)

Development and validation of a real-time PCR for the detection and quantification of porcine circovirus type 2 - Ana Margarida Henriques; Margarida Duarte; Sílvia Carla Barros; Teresa Fagulha; Fernanda Ramos; Tiago Luís; Miguel Fevereiro (VirusDisease, 2018)

The occurrence of wild cotton Gossypium mustelinum Miers ex Watt populations in the coast of Pernambuco, Northeastern Brazil - Edson Ferreira da Silva; Luiz Sergio Costa Duarte Filho; Ana Kelly dos Santos Maia; Allison Vieira da Silva; Ana Carolina Borges Lins e Silva (Genetic Resources and Crop Evolution, 2018)

Creation of a coastal evolution prognostic model using shoreline historical data and techniques of digital image processing in a GIS environment for generating future scenarios - Willamys R. N. de Sousa; Michael V. S. Souto; Stefanny S. Matos; Cynthia R. Duarte; Ana R. G. N. L. Salgueiro; Cláudio A. da Silva Neto (International Journal of Remote Sensing, 2018)

Publisher Correction to: Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

High waterborne Mg does not attenuate the toxic effects of Fe, Mn, and Ba on Na+ regulation of Amazonian armored catfish tamoatá (Hoplosternum litoralle) - Rafael M. Duarte; Ana Paula Benaduce; Luciano Garcia; Levy C. Gomes; Adriana Chippari Gomes; Adalberto L. Val; Bernardo Baldisserotto (Environmental Science and Pollution Research, 2018)

The influence of meteorological parameters on Alternaria and Cladosporium fungal spore concentrations in Beja (Southern Portugal): preliminary results - Elsa Almeida; Elsa Caeiro; Ana Todo-Bom; Raquel Ferro; Ana Dionísio; Ana Duarte; Luiz Gazarini (Aerobiologia, 2018)

Haplotype analysis of the germacrene A synthase gene and association with cynaropicrin content and biological activities in Cynara cardunculus - Ana Margarida Ferro; Patrícia Ramos; Ângela Guerra; Paula Parreira; Teresa Brás; Olinda Guerreiro; Eliana Jerónimo; Carmen Capel; Juan Capel; Fernando J. Yuste-Lisbona; Maria F. Duarte; Rafael Lozano; et al. (Molecular Genetics and Genomics, 2018)

Are General Physicians Prepared for Struggling Skin Cancer?—Cross-Sectional Study - Ana Filipa Duarte; Altamiro da Costa-Pereira; Veronique Del-Marmol; Osvaldo Correia (Journal of Cancer Education, 2018)

Genotype imputation performance of three reference panels using African ancestry individuals - Candelaria Vergara; Margaret M. Parker; Liliana Franco; Michael H. Cho; Ana V. Valencia-Duarte; Terri H. Beaty; Priya Duggal (Human Genetics, 2018)

How Big Data Fast Tracked Human Mobility Research and the Lessons for Animal Movement Ecology - Michele Thums; Juan Fernández-Gracia; Ana M. M. Sequeira; Víctor M. Eguíluz; Carlos M. Duarte; Mark G. Meekan (Frontiers in Marine Science, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

A panel of protein candidates for comprehensive study of Caprine Arthritis Encephalitis (CAE) infection - Rosivaldo Quirino Bezerra Júnior; Ângela Maria Xavier Eloy; João Ricardo Furtado; Raymundo Rizaldo Pinheiro; Alice Andrioli; Frederico Bruno Moreno; Marina Duarte Pinto Lobo; Ana Cristina O. Monteiro-Moreira; Renato de Azevedo Moreira; Tatiana Maria Farias Pinto; Maria Fátima da Silva Teixeira (Tropical Animal Health and Production, 2018)

Comparative study of the reproductive strategy of three bivalve species, Cerastoderma edule, Ruditapes decussatus, Ruditapes philippinarum from Lagoa de Óbidos, Leiria, Portugal - Emma Gomes; João Duarte; Ana Trindade; Isabel Duarte; Daniela Machado; Catarina Anjos; Domitília Matias; Simone Teixeira; Pedro Pires; Sandra Joaquim; SUSANA MENDES; Teresa Baptista (Frontiers in Marine Science, 2018)

Environmental factors influencing the settlement of Diplodus spp. juveniles in temperate marine rocky shores - Pedro Duarte-Coelho; Ruxanda Lungu; Joana Martins; Diana Vieira; Ana Coelho; José Neto; Sofia Sousa; Pedro Almeida; Frederico Almada (Frontiers in Marine Science, 2018)

Hg-Planktarctic - Unravelling the metabolic adaptations in phytoplankton continuously exposed to volcanic-mercury in Deception Island waters (Antarctica) - Bernardo Duarte; Carlos Cordeiro; Marta Sousa Silva; Andreia Figueiredo; Rui Rosa; João Canário; Isabel Caçador; João Marques; Maria Teresa Cabrita; Ana Rita Matos; Carla Gameiro (Frontiers in Marine Science, 2018)

Unlocking the hidden nutritional value of Portuguese edible halophytes cultivated under estuarine water irrigation schemes - Filipa Antunes; Bernardo Duarte; Márcia Pinto; Anabela Silva; Ana Rita Matos; Isabel Caçador; Carlos Brandão (Frontiers in Marine Science, 2018)

Emergence of rabbit haemorrhagic disease virus 2 in the archipelago of Madeira, Portugal (2016–2017) - Carina Luísa Carvalho; Sara Silva; Paz Gouveia; Margarida Costa; Elsa Leclerc Duarte; Ana Margarida Henriques; Sílvia Santos Barros; Tiago Luís; Fernanda Ramos; Teresa Fagulha; Miguel Fevereiro; Margarida Dias Duarte (Virus Genes, 2017)

Use of Hydrodynamic Cavitation for Algae Removal: Effect on the Inactivation of Microalgae Belonging to Genus Scenedesmus - Marylia Duarte Batista; Ana Carolina Borella Marfil Anhê; Julio Cesar de Souza Inácio Gonçalves (Water, Air, & Soil Pollution, 2017)

Evaluation of violations in water quality standards in the monitoring network of São Francisco River basin, the third largest in Brazil - Elizângela Pinheiro da Costa; Carolina Cristiane Pinto; Ana Luiza Cunha Soares; Livia Duarte Ventura Melo; Sílvia Maria Alves Corrêa Oliveira (Environmental Monitoring and Assessment, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Brain GLP-1/IGF-1 Signaling and Autophagy Mediate Exendin-4 Protection Against Apoptosis in Type 2 Diabetic Rats - Emanuel Candeias; Inês Sebastião; Susana Cardoso; Cristina Carvalho; Maria Sancha Santos; Catarina Resende Oliveira; Paula I. Moreira; Ana I. Duarte (Molecular Neurobiology, 2017)

Adenosine receptors: regulatory players in the preservation of mitochondrial function induced by ischemic preconditioning of rat liver - Filipe V. Duarte; João A. Amorim; Ana T. Varela; João S. Teodoro; Ana P. Gomes; Rodrigo A. Cunha; Carlos M. Palmeira; Anabela P. Rolo (Purinergic Signalling, 2017)

Unbalanced resting-state networks activity in psychophysiological insomnia - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; José Moutinho dos Santos; Isabel Catarina Duarte; Gina Caetano; Miguel Castelo-Branco (Sleep and Biological Rhythms, 2017)

Sorghum ( Sorghum bicolor L.): Nutrients, bioactive compounds, and potential impact on human health - Leandro de Morais Cardoso; Soraia Silva Pinheiro; Hércia Stampini Duarte Martino; Helena Maria Pinheiro-Sant'Ana (Critical Reviews in Food Science and Nutrition, 2017)

Spring stimulates leaf decomposition in moderately eutrophic streams - Ana Pereira; José Trabulo; Isabel Fernandes; Cláudia Pascoal; Fernanda Cássio; Sofia Duarte (Aquatic Sciences, 2017)

Effects of Hypericum perforatum hydroalcoholic extract, hypericin, and hyperforin on cytotoxicity and CYP3A4 mRNA expression in hepatic cell lines: a comparative study - Ana Martinho; Sara M. Silva; Sara Garcia; Ivo Moreno; Luiza Breitenfeld Granadeiro; Gilberto Alves; Ana Paula Duarte; Fernanda Domingues; Samuel Silvestre; Eugenia Gallardo (Medicinal Chemistry Research, 2016)

Protective Effect of the Sulfated Agaran Isolated from the Red Seaweed Laurencia aldingensis Against Toxic Effects of the Venom of the Snake, Lachesis muta - Ana Cláudia Rodrigues da Silva; Luciana Garcia Ferreira; Maria Eugênia Rabello Duarte; Mutue Toyota Fujii; Eladio Flores Sanchez; Miguel Daniel Noseda; André Lopes Fuly (Marine Biotechnology, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Fate and Analysis of Endocrine-Disrupting Compounds in a Wastewater Treatment Plant in Portugal - Ana Rita Carvalho; Vítor Cardoso; Alexandre Rodrigues; Maria João Benoliel; Elizabeth Duarte (Water, Air, & Soil Pollution, 2016)

Virtual Water Flows in the EU27: A Consumption‐based Approach - Ana Serrano; Dabo Guan; Rosa Duarte; Jouni Paavola (Journal of Industrial Ecology, 2016)
Summary The use of water resources has traditionally been studied by accounting for the volume of water removed from sources for specific uses. This approach focuses on surface and groundwater only and it ignores that international trade of products with substantial amounts of embodied water can have an impact on domestic water resources. Using current economic and environmental data, we conduct a consumption‐based assessment of virtual water flows in the European Union (EU27). We find that the total water footprint (WF) of 2,280 cubic meters (m 3 ) per capita for the EU27 mostly consists of green water use (precipitation stored as soil moisture), which is omitted in the conventional water accounting. Blue water (surface and groundwater.) and gray water use (the volume of freshwater needed to dilute pollutants to meet the applicable water quality standards), which are targeted by current EU water policies, only make up 32% of the total WF. We also find that Europeans imported 585 cubic kilometers (km 3 ) (10 9 m 3 ) of virtual water, or around 28% of global virtual water trade flows, in 2009. Within Europe, Germany is a key net importer of water through the trade of products in agriculture, the food industry, the chemical sector, and electricity generation. Countries in Southern and Eastern Europe have specialized in water‐intensive agriculture and are key exporters of virtual water despite experiencing physical scarcity of water. Our results suggest that there is a need to reconsider water policy in the EU to address water transfers occurring through trade and to grasp the interlinkages between green, blue, and gray water—which are likely to become more important in water‐scarce parts of Europe, with a changing climate.

Invasion by Artocarpus heterophyllus (Moraceae) in an island in the Atlantic Forest Biome, Brazil: distribution at the landscape level, density and need for control - Helena Godoy Bergallo; Ana Carolina Bergallo; Henrique Bergallo Rocha; Carlos Frederico Duarte Rocha (Journal of Coastal Conservation, 2016)

Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Paula Figueira; Bruno Henriques; Ana Teixeira; Cláudia B. Lopes; Ana T. Reis; Rui J. R. Monteiro; A. C. Duarte; M. A. Pardal; E. Pereira (Environmental Science and Pollution Research, 2016)

Social immunity of the family: parental contributions to a public good modulated by brood size - Ana Duarte; Sheena C. Cotter; Catherine E. Reavey; Richard J. S. Ward; Ornela De Gasperin; Rebecca M. Kilner (Evolutionary Ecology, 2016)

Globalization and natural resources: the expansion of the Spanish agrifood trade and its impact on water consumption, 1965–2010 - Rosa Duarte; Vicente Pinilla; Ana Serrano (Regional Environmental Change, 2016)

Effects of nickel on the fatty acid composition of the diatom Phaeodactylum tricornutum - Matos Ana Rita; Gameiro Carla; Duarte Bernardo; Caçador Isabel; Cabrita Maria Teresa (Frontiers in Marine Science, 2016)

Expression of recombinant sea urchin-inspired adhesive proteins: discovery, production and applications. - Da Costa Gonçalo; Toubarro Duarte; Marquês Joaquim; Viana Ana; Cordeiro Carlos; Cabral Henrique; Santos Romana (Frontiers in Marine Science, 2016)

Antimicrobial and Enzymatic activity of microorganisms isolated from the gut of sea cucumber (Holothuria forskali) - Duarte Ana Catarina; Perfeito Ana Catarina; Galante Joana; Oliveira Marta; Baptista Teresa; Violante Pombo Ana; Cristóvão Maria Manuel; Afonso Clélia (Frontiers in Marine Science, 2016)

Biochemical and biophysical tools for the detection of trace metal stress in the diatom model species Phaeodactylum tricornutum - Cabrita Maria Teresa; Duarte Bernardo; Gameiro Carla; Utkin Andrei; Matos Ana Rita; Caçador Isabel; Cartaxana Paulo (Frontiers in Marine Science, 2016)

Comparative analysis on natural spawning of F1 meagre, Argyrosomus regius, with wild broodstock spawns in Portugal - Florbela Soares; Laura Ribeiro; Margarida Gamboa; Sílvia Duarte; Ana Candeias Mendes; Sara Castanho; Marisa Barata; Tânia Margarida Lourenço; Pedro Pousão-Ferreira (Fish Physiology and Biochemistry, 2015)

Perennial Grass Production Opportunities on Marginal Mediterranean Land - Ana Luisa Fernando; Sara Boléo; Bruno Barbosa; Jorge Costa; Maria Paula Duarte; Andrea Monti (BioEnergy Research, 2015)

Phytoremediation of Heavy Metal-Contaminated Soils Using the Perennial Energy Crops Miscanthus spp. and Arundo donax L. - Bruno Barbosa; Sara Boléo; Sarah Sidella; Jorge Costa; Maria Paula Duarte; Benilde Mendes; Salvatore L. Cosentino; Ana Luisa Fernando (BioEnergy Research, 2015)

Tidal variation in a rocky inter‐tidal fish population: the case of white seabream Diplodus sargus juveniles - Ana Ribeiro Gonçalves; Liliana de Sousa; Pedro Duarte‐Coelho; Vitor Carvalho Almada (Marine Ecology, 2015)
The rocky inter‐tidal habitat is a harsh and fluctuating environment, subject to frequent disturbances. Field observations of juvenile white seabream Diplodus sargus in inter‐tidal rocky habitats were conducted to analyse the spatial distribution and feeding activity of this species in relation to the tidal cycle. The depth at which fish were observed did not change in most tidal phases while feeding activity changed with tidal level, showing the occurrence of tidal migrations and that feeding may be limited by habitat availability in shallow waters and thus be dependent on tidal changes. The present results show the exploitation of available feeding areas in the rocky inter‐tidal by juvenile white seabream, which corroborates the importance of these habitats for the first developmental stages of this fish species.

Plants of the Cerrado naturally selected by grazing sheep may have potential for inhibiting development of Haemonchus contortus larva - Franciellen Morais-Costa; Ana Cláudia Maia Soares; Gabriela Almeida Bastos; Yule Roberta Ferreira Nunes; Luciana Castro Geraseev; Fernão Castro Braga; Walter dos Santos Lima; Eduardo Robson Duarte (Tropical Animal Health and Production, 2015)

Environmental Footprints and Scenario Analysis for Assessing the Impacts of the Agri‐Food Industry on a Regional Economy: A Case Study in Spain - Ignacio Cazcarro; Rosa Duarte; Julio Sánchez‐Chóliz; Cristina Sarasa; Ana Serrano (Journal of Industrial Ecology, 2015)
Summary The study of the environmental footprints of various sectors and industries is increasingly demanded by institutions and by society. In this context, the regional perspective is becoming particularly important, and even more so in countries such as Spain, where the autonomous communities have the primary responsibility for implementing measures to combat environmental degradation and promote sustainable development, in coordination with national strategies. Taking as a case study a Spanish region, Aragon, and significant economic sectors, including agriculture and the food industry, the aim of this work is twofold. First, we calculate the associated environmental footprints (of emissions and water) from the dual perspectives of production (local impacts) and consumption (final destination of the goods produced by the agri‐food industry). Second, through a scenarios analysis, based on a general equilibrium model designed and calibrated specifically for the region, we evaluate the environmental implications of changes in the agri‐food industry (changes in the export and import pattern, as well as in consumer behavior). This model provides a flexible approximation to the environmental impacts, controlling for a wider range of behavioral and economic interactions. Our results indicate that the agri‐food industry has a significant impact on the environment, especially on water resources, which must be responsibly managed in order to maintain the differential advantage that a regional economy can have, compared to other territories.

Genetic diversity and biogeographical patterns of Caulerpa prolifera across the Mediterranean and Mediterranean/Atlantic transition zone - Elena Varela-Álvarez; Ana C. Balau; Núria Marbà; Julio Afonso-Carrillo; Carlos M. Duarte; Ester A. Serrão (Marine Biology, 2015)

Activation of IGF-1 and Insulin Signaling Pathways Ameliorate Mitochondrial Function and Energy Metabolism in Huntington’s Disease Human Lymphoblasts - Luana Naia; I. Luísa Ferreira; Teresa Cunha-Oliveira; Ana I. Duarte; Márcio Ribeiro; Tatiana R. Rosenstock; Mário N. Laço; Maria J. Ribeiro; Catarina R. Oliveira; Frédéric Saudou; Sandrine Humbert; A. Cristina Rego (Molecular Neurobiology, 2015)

Euphorbia and Momordica metabolites for overcoming multidrug resistance - Maria-José U. Ferreira; Noélia Duarte; Mariana Reis; Ana Margarida Madureira; Joseph Molnár (Phytochemistry Reviews, 2014)

The Impact of Uranium Mine Contamination of Soils on Plant Litter Decomposition - Ana C. Freitas; Dina Rodrigues; Teresa A. P. Rocha-Santos; Fernando Gonçalves; Armando C. Duarte; Ruth Pereira (Archives of Environmental Contamination and Toxicology, 2014)

Antioxidant and antifungal activities of Smilax campestris Griseb. (Smilacaceae) - Marcela Isis Morais; Maria Eduarda Amaral Pinto; Sthéfane Guimarães Araújo; Ana Hortência Fonsêca Castro; Joaquim Mauricio Duarte-Almeida; Luiz Henrique Rosa; Carlos Augusto Rosa; Susana Johann; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2014)

Earthworm (Pontoscolex corethrurus) survival and impacts on properties of soils from a lead mining site in Southern Brazil - Ana Paula Duarte; Vander Freitas Melo; George G. Brown; Volnei Pauletti (Biology and Fertility of Soils, 2014)

IGF-1 Intranasal Administration Rescues Huntington's Disease Phenotypes in YAC128 Mice - Carla Lopes; Márcio Ribeiro; Ana I. Duarte; Sandrine Humbert; Frederic Saudou; Luís Pereira de Almeida; Michael Hayden; A. Cristina Rego (Molecular Neurobiology, 2014)

Self-sterility and self-fertility of Passiflora L. (Passifloraceae) in the Cerrado of Central Brazil - Mariana Oliveira Duarte; Mariana Ferreira Alves; Marcela Yamamoto; Sueli Matiko Sano; Ana Angélica Almeida Barbosa; Paulo Eugênio Oliveira (Brazilian Journal of Botany, 2014)

Study of the physicochemical parameters and spontaneous fermentation during the traditional production of yakupa, an indigenous beverage produced by Brazilian Amerindians - Ana Luiza Freire; Cintia Lacerda Ramos; Euziclei Gonzaga de Almeida; Whasley Ferreira Duarte; Rosane Freitas Schwan (World Journal of Microbiology and Biotechnology, 2014)

Conspecific cues affect stage-specific molting frequency, survival, and claw morphology of early juvenile stages of the shore crab Carcinus maenas - Rafael C. Duarte; Ana Ré; Augusto A. V. Flores; Henrique Queiroga (Hydrobiologia, 2014)

Mapping Hotspots of Threatened Species Traded in Bushmeat Markets in the Cross–Sanaga Rivers Region - JULIA E. FA; MIGUEL ANGEL FARFÁN; ANA LUZ MARQUEZ; JESÚS DUARTE; JANET NACKONEY; AMY HALL; JEF DUPAIN; SARAH SEYMOUR; PAUL J. JOHNSON; DAVID W. MACDONALD; J. MARIO VARGAS (Conservation Biology, 2014)
Bushmeat markets exist in many countries in West and Central Africa, and data on species sold can be used to detect patterns of wildlife trade in a region. We surveyed 89 markets within the Cross–Sanaga rivers region, West Africa. In each market, we counted the number of carcasses of each taxon sold. During a 6‐month period (7594 market days), 44 mammal species were traded. Thirteen species were on the International Union for Conservation of Nature (IUCN) Red List or protected under national legislation, and at least 1 threatened species was traded in 88 of the 89 markets. We used these data to identify market groups that traded similar species assemblages. Using cluster analyses, we detected 8 market groups that were also geographically distinct. Market groups differed in the diversity of species, evenness of species, and dominant, prevalent, and characteristic species traded. We mapped the distribution of number of threatened species traded across the study region. Most threatened species were sold in markets nearest 2 national parks, Korup National Park in Cameroon and Cross River in Nigeria. To assess whether the threatened‐species trade hotspots coincided with the known ranges of these species, we mapped the overlap of all threatened species traded. Markets selling more threatened species overlapped with those regions that had higher numbers of these. Our study can provide wildlife managers in the region with better tools to discern zones within which to focus policing efforts and reduce threats to species that are threatened by the bushmeat trade. Mapeo de Sitios Críticos para Especies Amenazadas Comercializadas en Mercados de Vida Silvestre en la Región de los Ríos Cross‐Sanaga

Antistaphylococcal and biofilm inhibitory activities of gallic, caffeic, and chlorogenic acids - Ângelo Luís; Filomena Silva; Sónia Sousa; Ana Paula Duarte; Fernanda Domingues (Biofouling, 2014)

Phylogenetic origin of the endemic pigeons from Madeira (Columba trocaz) and Azores Islands (Columba palumbus azorica) - Catarina G. Dourado; Margarida Alexandra Duarte; Ana Rita Grosso; Cristiane Bastos-Silveira; Patricia Marrero; Paulo Oliveira; Octávio S. Paulo; Deodália Dias (Journal of Ornithology, 2014)

Palynofacies and TOC analysis of marine and non-marine sediments across the Middle–Upper Jurassic boundary in the central-northern Lusitanian Basin (Portugal) - Ricardo L. Silva; João G. Mendonça Filho; Ana C. Azerêdo; Luís V. Duarte (Facies, 2014)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

The Application of MnO2 in the Removal of Manganese from Acid Mine Water - Alice O. Aguiar; Rute A. Duarte; Ana Claudia Q. Ladeira (Water, Air, & Soil Pollution, 2013)

Aeromonas molluscorum Av27 is a potential tributyltin (TBT) bioremediator: phenotypic and genotypic characterization indicates its safe application - Andreia Cruz; Dário Areias; Ana Duarte; António Correia; Satoru Suzuki; Sónia Mendo (Antonie van Leeuwenhoek, 2013)

Influence of red wine fermentation oenological additives on inoculated strain implantation - Filomena L. Duarte; Ana Claudia Alves; Maria Filomena Alemão; M. Margarida Baleiras-Couto (World Journal of Microbiology and Biotechnology, 2013)

In Vitro Susceptibility of Environmental Isolates of Exophiala dermatitidis to Five Antifungal Drugs - Ana Paula Miranda Duarte; Fernando Carlos Pagnocca; Noemi Carla Baron; Marcia de Souza Carvalho Melhem; Gislene Aparecida Palmeira; Dejanira de Franceschi de Angelis; Derlene Attili-Angelis (Mycopathologia, 2013)

Propolis volatiles characterisation from acaricide-treated and -untreated beehives maintained at Algarve (Portugal) - Maria G. Miguel; Susana Nunes; Cláudia Cruz; João Duarte; Maria D. Antunes; Ana M. Cavaco; Marta D. Mendes; A. Sofia Lima; Luis G. Pedro; José G. Barroso; A. Cristina Figueiredo (Natural Product Research, 2013)

Uncovering the beginning of diabetes: the cellular redox status and oxidative stress as starting players in hyperglycemic damage - João Soeiro Teodoro; Ana Patrícia Gomes; Ana Teresa Varela; Filipe Valente Duarte; Anabela Pinto Rolo; Carlos Marques Palmeira (Molecular and Cellular Biochemistry, 2013)

Vitamin D receptor polymorphisms in hypertensive disorders of pregnancy - Vania B. Rezende; Valeria C. Sandrim; Ana C. Palei; Lorena Machado; Ricardo C. Cavalli; Geraldo Duarte; Jose E. Tanus-Santos (Molecular Biology Reports, 2012)

Chemical composition and antibacterial activity of the essential oils from the medicinal plant Mentha cervina L. grown in Portugal - Leandra Rodrigues; Aida Duarte; Ana Cristina Figueiredo; Luísa Brito; Generosa Teixeira; Margarida Moldão; Ana Monteiro (Medicinal Chemistry Research, 2012)

Treatment of Olive Oil Mill Wastewater by Silica–Alginate–Fungi Biocomposites - Kátia R. Duarte; Ana C. Freitas; Ruth Pereira; Jorge C. Pinheiro; Fernando Gonçalves; H. Azaari; Mohammed El Azzouzi; Abdallah Zrineh; Souad Zaydoun; Armando C. Duarte; Teresa A. P. Rocha-Santos (Water, Air, & Soil Pollution, 2012)

Removal of Arsenic from Aqueous Solutions by Sorption onto Sewage Sludge-Based Sorbent - Daniela S. Tavares; Cláudia B. Lopes; João P. Coelho; Marta E. Sánchez; Ana I. Garcia; Armando C. Duarte; Marta Otero; Eduarda Pereira (Water, Air, & Soil Pollution, 2012)

Evolution of self-organized division of labor in a response threshold model - Ana Duarte; Ido Pen; Laurent Keller; Franz J. Weissing (Behavioral Ecology and Sociobiology, 2012)

Effect of lifestyle on age-related mitochondrial protein oxidation in mice cardiac muscle - Ana Isabel Padrão; Rita Ferreira; Rui Vitorino; Renato M. P. Alves; Pedro Figueiredo; José Alberto Duarte; Francisco Amado (European Journal of Applied Physiology, 2012)

BMPRIB and BMPRII mRNA expression levels in goat ovarian follicles and the in vitro effects of BMP-15 on preantral follicle development - Isadora Machado T. Lima; Ivina R. Brito; Rafael Rossetto; Ana Beatriz G. Duarte; Giovanna Q. Rodrigues; Márcia Viviane A. Saraiva; José Jackson N. Costa; Mariana Aragão M. Donato; Christina A. Peixoto; José Roberto V. Silva; José Ricardo de Figueiredo; Ana Paula R. Rodrigues (Cell and Tissue Research, 2012)

Olive oil mill wastewaters before and after treatment: a critical review from the ecotoxicological point of view - Celine I. L. Justino; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Teresa S. L. Panteleitchouk; Armando C. Duarte (Ecotoxicology, 2012)

Exercise Pre-conditioning Reduces Brain Inflammation and Protects against Toxicity Induced by Traumatic Brain Injury: Behavioral and Neurochemical Approach - Bibiana Castagna Mota; Leticia Pereira; Mauren Assis Souza; Luiz Fernando Almeida Silva; Danieli Valnes Magni; Ana Paula Oliveira Ferreira; Mauro Schneider Oliveira; Ana Flávia Furian; Leidiane Mazzardo-Martins; Morgana Duarte da Silva; Adair Roberto Soares Santos; Juliano Ferreira; et al. (Neurotoxicity Research, 2012)

Sodium Fluxes in Tamoatá, Hoplosternum litoralle, Exposed to Formation Water from Urucu Reserve (Amazon, Brazil) - Bernardo Baldisserotto; Luciano O. Garcia; Ana Paula Benaduce; Rafael M. Duarte; Thiago L. Nascimento; Levy C. Gomes; Adriana R. Chippari Gomes; Adalberto L. Val (Archives of Environmental Contamination and Toxicology, 2012)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Roberta V. M. Bronzoni; Maria C. F. S. Madrid; Danilo V. B. Duarte; Vanessa O. A. Pellegrini; Carolina C. Pacca; Ana C. V. Carmo; Cleslei F. Zanelli; Sandro R. Valentini; Carolina Santacruz-Pérez; João A. R. G. Barbosa; Carol S. Lutz; Paula Rahal; et al. (Archives of Virology, 2011)

Evaluation of the Sub-lethal Toxicity of Bleached Kraft Pulp Mill Effluent to Carassius auratus and Dicentrarchus labrax - Mário S. Diniz; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Luisa Castro; Isabel Peres; Armando C. Duarte (Water, Air, & Soil Pollution, 2011)

Prevalence of the bla SHV Gene in Klebsiella pneumoniae Isolates Obtained from Hospital and Community Infections and from the Microbiota of Healthy Individuals in Recife, Brazil - Dyana Leal Veras; Luiz Carlos Alves; Fábio André Brayner; Duschinka Ribeiro Duarte Guedes; Maria Amélia Vieira Maciel; Cíntia Renata Costa Rocha; Ana Catarina de Souza Lopes (Current Microbiology, 2011)

Evaluation of tertiary treatment by fungi, enzymatic and photo-Fenton oxidation on the removal of phenols from a kraft pulp mill effluent: a comparative study - Celine Justino; Ana Gabriela Marques; Dina Rodrigues; Lurdes Silva; Armando Costa Duarte; Teresa Rocha-Santos; Ana Cristina Freitas (Biodegradation, 2011)

Assessment of Mercury in Water, Sediments and Biota of a Southern European Estuary (Sado Estuary, Portugal) - Ana I. Lillebø; Pedro J. Coelho; Pedro Pato; Mónica Válega; Rui Margalho; Mário Reis; José Raposo; Eduarda Pereira; Armando C. Duarte; Miguel A. Pardal (Water, Air, & Soil Pollution, 2011)

Allelochemical Effects of Volatile Compounds and Organic Extracts from Muscodor yucatanensis, a Tropical Endophytic Fungus from Bursera simaruba - Martha L. Macías-Rubalcava; Blanca E. Hernández-Bautista; Fabiola Oropeza; Georgina Duarte; María C. González; Anthony E. Glenn; Richard T. Hanlin; Ana Luisa Anaya (Journal of Chemical Ecology, 2010)

Are Great Tits (Parus major) Inhabiting the Vicinity of a Pulp Mill Healthy? Impacts on Physiology and Breeding Performance - Ana Cláudia Norte; B. C. Sheldon; J. P. Sousa; P. C. Tavares; M. E. Pereira; A. C. Duarte; J. A. Ramos (Archives of Environmental Contamination and Toxicology, 2010)

Effects of tertiary treatment by fungi on organic compounds in a kraft pulp mill effluent - Teresa Rocha-Santos; Filipe Ferreira; Lurdes Silva; Ana Cristina Freitas; Ruth Pereira; Mário Diniz; Luísa Castro; Isabel Peres; Armando Costa Duarte (Environmental Science and Pollution Research, 2010)

Subtidal stromatolites from the Sinemurian of the Lusitanian Basin (Portugal) - Ana C. Azerêdo; Ricardo L. Silva; Luís V. Duarte; M. Cristina Cabral (Facies, 2010)

Degradation of phenols in olive oil mill wastewater by biological, enzymatic, and photo-Fenton oxidation - Celine Justino; Ana Gabriela Marques; Kátia Reis Duarte; Armando Costa Duarte; Ruth Pereira; Teresa Rocha-Santos; Ana Cristina Freitas (Environmental Science and Pollution Research, 2010)

Identification of a Candida parapsilosis Strain Producing Extracellular Serine Peptidase with Keratinolytic Activity - Alane Beatriz Vermelho; Ana Maria Mazotto; Ana Cristina Nogueira de Melo; Flávia Helena Cardoso Vieira; Thalita Rodrigues Duarte; Andrew Macrae; Marília Martins Nishikawa; Elba Pinto da Silva Bon (Mycopathologia, 2010)

Lap4, a vacuolar aminopeptidase I, is involved in cadmium-glutathione metabolism - Paula D. B. Adamis; Sergio C. Mannarino; Cristiano J. Riger; Giselle Duarte; Ana Cruz; Marcos D. Pereira; Elis C. A. Eleutherio (BioMetals, 2009)

NADH oxidase activity of rat and human liver xanthine oxidoreductase: potential role in superoxide production - Luisa Maia; Rui O. Duarte; Ana Ponces-Freire; José J. G. Moura; Lurdes Mira (JBIC Journal of Biological Inorganic Chemistry, 2007)

Hierarchical status and colour preference in Nile tilapia (Oreochromis niloticus) - Ana Carolina Luchiari; Cristiane Regina do Amaral Duarte; Fúlvio Aurélio de Morais Freire; Kari Nissinen (Journal of Ethology, 2007)

Sardine (Sardina pilchardus) stress reactions to purse seine fishing - Ana Marçalo; Luísa Mateus; José Henrique Duarte Correia; Pedro Serra; Rob Fryer; Yorgos Stratoudakis (Marine Biology, 2006)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

Bacteriological Properties of a Sucrose-Fermenting Corynebacterium diphtheriae Strain Isolated from a Case of Endocarditis - Ana Luiza de Mattos-Guaraldi; Luiz Carlos Duarte Formiga (Current Microbiology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)